RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

Long-term impact of 3-D urban expansion on the thermal environment in the Yangtze River Delta region, China - Chenglong Yin; Ruishan Chen; Xiangming Xiao; Yi Yin; Tim Van de Voorde; Yinshuai Li; Nan Jia; Hong Wei; Li Pan; Fei Meng; Yanbin Chen; Bo Xiong; et al. (Land Use Policy, 2026)

Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Global comparison of different effective scattering albedo and soil roughness parameterization schemes for SMAP soil moisture and L-VOD retrieval - Yao Xiao; Xiaojun Li; Lei Fan; Andress Colliander; Ardeshir Ebtehaj; Jian Peng; Frédéric Frappart; Lanka Karthikeyan; Wei Zhao; Gabrielle De Lannoy; Patricia de Rosnay; Zanpin Xing; et al. (Remote Sensing of Environment, 2026)

Evolution of Micro-pore structure in saline agricultural soil driven by sand addition of specific particle sizes and its regulation mechanism on water and salt transport - Yi Meng; Shuanhu Li; Chi Li; Bing Zhang; De Yao; Xiaorong Wang (Journal of Contaminant Hydrology, 2026)

Thermodynamically favored fluorine refilling stabilizes oxygen vacancies for ultrafast and wide-temperature aqueous zinc-ion batteries - Daming Chen; Yang Ming; Jimin Fu; Chuanwei Zhi; Zijian Li; Wei Cai; Hanbai Wu; Xin Hu; Rujun Yu; Shou Shi; Jing Liu; De-Yi Wang; et al. (Chemical Engineering Journal, 2026)

Comparative assessment of endogenous, integrated, and exogenous biomethanation strategies: performance, microbial community and metabolic pathways - Yali Zhu; Jo De Vrieze; Yu Li; Siqi Wang; Daoyu Li; Zongqin Zhang; Renjie Dong; Xin Li (Bioresource Technology, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Expansion deformation characteristics of interbedded weakly expansive rock and soil foundations - Jing Jiang; Tingting Wang; Yuchen Li; De Chen (Transportation Geotechnics, 2026)

Astrochronology of the Ediacaran Period reveals the temporal heterogeneity and sea-level pacing of Shuram excursion - Naihua Xue; Wei Wang; David De Vleeschouwer; Chengguo Guan; Mingsong Li; Meng Wang; Xunlai Yuan; Philippe Claeys (Precambrian Research, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Development of an ultrasensitive magnetic biosensing platform using SERS and aptamer for the ratio detection of chlorpyrifos in tea - Chenxi Jin; Min Cao; Geqi Li; Jiaqi Wang; Chongyang Qin; Pu Wang; Fei Guo; Dejiang Ni; Zhi Yu; De Zhang; Pei Liang (Food Chemistry, 2026)

Future climate change reshapes agroclimatic resources and intensifies waterlogging impacts on crop production - Chunhu Wang; Rui Yang; Matthew Tom Harrison; De Li Liu; Puyu Feng; Meixue Zhou; Yunbo Zhang; Jiangwen Nie; Ke Liu (European Journal of Agronomy, 2026)

Nicotinamide enhances lipid deposition and thermogenesis in goat brown adipocytes - Jing Ke; Langda Suo; Ji De; Die Li; Xin Dai; Linjie Wang (Domestic Animal Endocrinology, 2026)

Bio-upcycling of microbe-toxic-food-waste to sophorolipids via evolved Starmerella bombicola - Yahui Miao; Na Li; Siqi Wang; Huaimin Wang; Guneet Kaur; Sofie De Maeseneire; Stijn Bovijn; Wim Soetaert; Sophie L.K.W. Roelants; Carol Sze Ki Lin (Chemical Engineering Journal, 2026)

Microphase-separated block copolymer nanodomains regulate Li+ transport, polysulfide conversion, and flame retardancy for LiS batteries - Shanzhe Li; Xiaoyu Zhang; Weilong Shao; Shuang Li; Dongxuan Guo; Bo Liu; De-Yi Wang; Ying Wang; Chunling Zhang (Chemical Engineering Journal, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

A novel fever prevalence indicator for early warning of acute respiratory infections using wastewater-based epidemiology and machine learning - Xue-Ting Shao; Hao-Yang Li; Jing-Bo Guan; Xin-Dong Ma; De-Gao Wang (Environmental Research, 2026)

The emerging high entropy materials for energy storage and conversion: Recent advances and future perspectives - Fangfei Lin; Runzhe Yao; Liyi Liu; Mengli Zhao; Junheng Wang; Fei Kang; De Li; Daming Chen; Panpan Zhang; Xing Lu; Yong Chen; Yaqing Wei (Chemical Engineering Journal, 2026)

Hierarchical Porous Biochar/Geopolymer Composite Derived from Hemp Straw for Enhanced Cadmium Remediation in Aqueous and Soil Environments - Yibin Wang; Shaorui De; Qianyu Wang; Peng Li; Yingchao Li (Water, Air, & Soil Pollution, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Targeted domestication of Enterobacter-dominated consortia for enhanced uranium immobilization via phosphate-mediated biomineralization - Jinxin Li; Jianhong Ma; Guicheng He; Qinglin Zhang; Han Qin; De Li; Rui Wang; Wei Zhang; Hui Zhang; Yongdong Wang; Feng Li; Yongmei Li (Journal of Hazardous Materials, 2026)

White kidney bean episperm polysaccharides improve cognitive impairment in D-galactose-induced aging mice via modulation of oxidative stress, neuroinflammation, and the gut-brain axis - Shiqi Liao; Yimei Hu; Xinyang Li; Zirui Guo; Yong Wang; Chunli Kong; Bei Wang; Paul de Vos (Food Research International, 2026)

The abiotic drivers of soil system perturbation by metallic nanomaterials: a critical review bridging interfacial processes to environmental risks - Mengcheng Zhang; Xue Li; Yongchao Zhao; De'an Chen; Na Tian; Wenrui Zhang; Dongle Cheng; Guang Yang; Xiaoqiang Cao; Yanlong Wang; Huaqing Liu; Jian Zhang (Environmental Research, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Comprehensive evaluation of water inrush intensity for “Jiaojia type” gold mining – a case study of Jiaojia Gold Mine - Ying Wang; Dai-Ting Zhai; Qing-Lu Meng; Huigong Niu; Chao Xie; Qing-Mei Li; Yu-Zhen Jia; De-Long Tian (Geosciences Journal, 2026)

Sulfur and copper isotope fractionation during planetesimal collisions: Insights from shock metamorphism in ordinary chondrites - Ming-Yang Li; Dan Zhu; De-Liang Wang; Shi-Jie Li; Xiong-Yao Li; Jian-Zhong Liu; Ying-Kui Xu (Acta Geochimica, 2026)

A Protective Role for Melatonin: Enhancing Heat Tolerance in Alisma plantago-aquatica Seedlings - Wen-hui Chen; Jiao Wang; Ke-yu Wang; De-qiang Li; Zi-zhong Tang; Yang-er Chen; Shu Yuan; Lu Zhang; Ming Yuan (Journal of Plant Growth Regulation, 2026)

UAV-based crop pest and disease monitoring: A review of multi-source sensing and intelligent methods - Jie Guo; Jin-Hai Li; Le Dong; Shun-Yu Wang; Guang-Yue Wu; Yu-Peng Zhang; Chang-Yong Tao; De-Hua Gao; Shu-Ming Yang; Yu-Tan Wang (Computers and Electronics in Agriculture, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

AI-designed crop populations for sustainable intensification - Ning Luo; Junhan Wang; Morten Graversgaard; Renan C. Umburanas; De Li Liu; Qirui Li; Jonathan Storkey; Simon Willcock; Pu Wang; Qingfeng Meng (Trends in Plant Science, 2026)

Advancing the understanding of drought propagation in glacierized catchments by accounting for meltwater and catchment control in a newly introduced bi-stage framework - Yunan Ling; Yue Huang; Xiaohui Pan; Xiaofei Wang; Tie Liu; Chanjuan Zan; Zhengyang Li; Xi Chen; Philippe De Mayer; Amaury Frankl (Journal of Hydrology, 2026)

Novel non-thermal plasma based strategy to synthesize high-performance multistage mesoporous cobalt-ceria oxides for plasma-catalytic decomposition of environmentally hazardous acetone - Lu Liu; Jian-hua Liu; Zhen-yun Wang; Guang-cai Shao; Yan-gang Hu; Karen Leus; Jian-li Mi; Chuan-long Ma; Rui-tang Guo; Qing-shan Wang; Anton Nikiforov; Pascal Van Der Voort; et al. (Journal of Hazardous Materials, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Research on high efficiency operation and low pollutant emission collaborative control of gas engine driven heat pump - Fengguo Liu; Shiyang Wang; Dongfang Zhao; De Wu; Chenglong Liu; Xinjie Li (International Journal of Refrigeration, 2026)

In situ gas-foaming strategy to construct nitrogen-doped porous hollow carbon spheres for ultra-broadband microwave absorbers - Youjun Jiang; De-Zhuang Wang; Mengqian Zhang; Yuerong Li; Yazhong Chen; Jun Yang; Xianlong Zhang; Qingfeng Liu; Xueping Wu (Chemical Engineering Journal, 2026)

Spatiotemporal activity patterns of urban residents and nonlinear built-environment associations: Evidence from Shanghai using GPS traces and time-use diaries - Jing Guo; De Wang; Longxu Yan; Jing Xia; Lingting Mu; Yinong Liu; Jun Liu; Yuan Li (Applied Geography, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Contributions of SARA fractions to asphalt fume composition via experiment and ReaxFF-molecule dynamics - Ming Jia; Hui Li; Xue Zhang; Yu Cheng; Ivan Miguel De Cachinho Cordeiro; A.C.Y. Yuen; Wei Wang; Cheng Wang; Guan Heng Yeoh (Fuel, 2026)

Structure–function relationships in chitosan films containing ZIF-8-confined Ligusticum jeholense essential oil: pH-triggered release and apple ring rot control - Xiao-Yi Tong; Yun-Feng Liu; Zhi-Hong Xu; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An; Fei Cao (Food Chemistry, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Atomic condensation of Na and K vapor followed by oxidation in lunar impact glass beads revealed by Chang’E-6 - Ming-Yang Li; Ying-Kui Xu; Dan Zhu; De-Liang Wang; Yi-Cao Zhou; Bing Mo; Shi-Jie Li; Yang Li; Xiong-Yao Li; Jian-Zhong Liu; Wei Du; Yun Liu (Earth and Planetary Science Letters, 2026)

Co-activation of CO2 and N2 in plasma-electrochemical system for direct urea production from flue gas - Mayuresh Janpandit; Xiaoli Ge; Binelka S. Siriwardana; Pratahdeep Gogoi; Jayanti Sharma; Shwetha Prakash; Gina DelMonache; Janiennid Alicea Tirado; Luis Velarde; Luis R. De Jesús Báez; Ziyun Wang; Yuguang C. Li (Chemical Engineering Journal, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Evaluation of satellite-derived methane emissions from coal mines using the Gaussian plume model in a topographically complex area - Yuanyuan Gao; Cheng Fan; Zhengqiang Li; Gerrit de Leeuw; Jieying Ding; Yinghui Han; Zhuo He; Yingqian Zhao; Zhihao Wang; Yuanxun Zhang; Ying Zhang; Ronald van der A (Atmospheric Environment, 2026)

Natural cadinane-type sesquiterpenoids and their bioactivity: a review (2015–2025) - Sheng-Zhi Wang; Hong Zhu; Xiao-Po Zhang; De-Li Chen (Phytochemistry, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Quality assessment and geographical origin traceability of Gastrodia elata based on machine vision, flash GC e-nose, HPLC, and machine learning algorithms - Qi Zhao; Yicheng Zhou; Cong Wang; Mingxuan Li; Shan Zhu; Chang Xue; De Ji; Yuwen Qin; Chengxi Jiang (Food Research International, 2026)

High-entropy strategy towards structurally stable garnet solid electrolyte for ultra-long lifespan solid-state lithium batteries - Shiyu Yu; Shihao Fu; Pingmei Li; Mingxin Zhang; Yaqing Wei; De Li; Liang Yang; Daming Chen; Ning Wang; Yong Chen (Chemical Engineering Journal, 2026)

Overt physiological responses and atypical behavior evoked in adult zebrafish in the novel tank test by two acute ‘survival’ stressors - Yunzhe Song; Jiahao Cui; Huiling Cai; Yunqian Zhang; Yixin Qin; Zhaowen Zhou; Haoyu Feng; Shulei He; Kai He; Yucheng Liu; Jiyi Wang; Jiayou Jiang; et al. (Behavioural Processes, 2026)

Opportunities to enhance sugarcane yield and gross margin under climate change through irrigation and planting date adaptation - Shijin Yao; De Li Liu; Bin Wang; Siyi Li; Jonathan K. Webb; Keyu Xiang; Alfredo Huete; Lihong Wu; Hao Quan; Qiang Yu (Irrigation Science, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Removal, transformation and toxicity changes of halobenzoquinones by digestive enzymes - Liu He; De-Xiu Wu; Wen-Min Wang; Xiao Xiao; Wei-Yu Li; Wen-Long Wang; Qian-Yuan Wu (Water Research, 2026)

Ice-covered lakes, hidden threats: Seasonal fate and risks of antibiotics and PAHs - Jie li; Peixin Wang; Lili Jiang; Hanyu Ju; Xuemei Liu; Guangxin Zhang; Erik de Goede; Jingjie Zhang (Water Research, 2026)

Molecular signatures of UV/PMS oxidation of bromide-containing secondary effluent: Size reduction of DOM and accumulation of high-risk brominated byproducts - Wei-Yu Li; Shao-Yu Wang; De-Xiu Wu; Yi-Yuan Liu; Liu He; Wen-Long Wang; Qian-Yuan Wu (Journal of Hazardous Materials, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Bioinspired interfacial anchoring enables durable ultra-black photothermal coatings based on silica-coated carbon nanotubes - Jian Li; Yan Wang; Xiaolong Wu; Chao Li; De-Rong Sun; Peng Wang; Zimu Li; Xue-Qing Liu (Chemical Engineering Journal, 2026)

Geospatial patterns of concurrent thermal stress and multi-pollutant exposure in China - Fuxing Li; Weimiao Li; Shiyao Wang; Gerrit de Leeuw; Yang Wang; Wei Wang; Cheng Fan; Zhengqiang Li (Atmospheric Environment, 2026)

New Potato-Life Cycle Loci Identified by Using an StCDF1-Fixed Population - Ernst-Jan Eggers; Li Shi; Xulan Wang; Marian Oortwijn; Sybille Ursula Mittmann; Richard G. F. Visser; Michiel E. de Vries; Pim Lindhout; Christian W. B. Bachem; Sara Bergonzi (Potato Research, 2026)
Photoperiodic insensitivity has been the selected trait that allowed cultivation of potato outside its centre of origin, to the northern latitudes of Europe and North America. More than a decade ago, Solanum tuberosum CYCLING DOF FACTOR 1 ( StCDF1 ) was identified as the maturity locus, regulating both above and below-ground maturity traits, also referred to as life cycle length and tuberization onset. Following its identification, several genomic studies contributed to the inventorization of the StCDF1 alleles carried by potato cultivars and their wild relatives. At the same time, the role of StCDF1 beyond plant development has started to be elucidated. While the importance of this locus has been widely shown, the presence of this strong QTL hotspot has hampered the identification of additional QTL and genes. Here, we report the use of a StCDF1 -fixed biparental population to map minor QTL for developmental and generative traits. Remarkably, we identified another region on Chr5 controlling several of the analyzed traits, i.e., tuberization onset, anthesis and senescence traits, and harbouring promising candidate genes for further characterization. Furthermore, the study dissected the contribution of self-compatibility to berry and seed set in a field setting prone to open pollination. The use of an StCDF1 -fixed population resulted in a straightforward and cost-effective approach to identify additionally agronomically relevant loci that could be used in future potato breeding.

Feeding and fecundity of leaf beetle Monolepta hieroglyphica on different tissues of corn and three weed plants - Yu-Wei Wu; Lin-Hao Zheng; Jia-Liang Xu; Jing-Wen Wang; De-Wei Meng; Fei-Wu Li; Wen-Jing Xu (Arthropod-Plant Interactions, 2026)
The double-spotted leaf beetle (DLB), Monolepta hieroglyphica (Coleoptera: Chrysomelidae), is a polyphagous pest that causes considerable damage to corn in China. However, there is limited knowledge regarding the influence of host plants on the biology of this beetle. This study assessed the feeding of DLB on three corn tissues and three weed species, as well as the impact of host plants/tissues on DLB fecundity. The Feeding rate of DLB was significantly affected by interaction between host plants/tissues and sex, indicating sex-specific patterns of feeding choice. The feeding levels of DLB adults were affected only by host plants/tissues, following the order: common knotgrass > corn silk > corn leaf > Asian copperleaf > white goosefoot > corn kernel. The fecundity of single female adults fed on common knotgrass was the highest (44.70 ± 11.47 eggs), whereas that fed on corn leaf was the lowest (2.00 ± 0.88 eggs). These results underscore the significance of weeds as alternative DLB hosts in corn agroecosystems, improving our understanding of DLB biology and offering valuable insights for establishing and providing an integrated pest management (IPM) program.

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Immobilized Bacillus in polyvinyl alcohol-sodium alginate-biochar for petroleum-contaminated soil remediation - Fenglei Han; Zhoutong Liu; Lihan Ren; Biao Wang; Fan Yang; Feng Yao; Xiaodong Zhao; Xiuxia Zhang; Kang Xiong; De Li; Wenhao Zuo (Environmental Sustainability, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Modelling material flows and cost-benefit of sorting PLA packaging waste in material recovery facilities under different market penetration scenarios - Wang Li; Alexandra Schmuck; Louis Van Caelenberg; Virginie Decottignies; Hy Boui Chang; Adeline Dupas; Peter Ragaert; Shreyash Anil Gujar; Marcel C P van Eijk; Steven De Meester (Resources, Conservation and Recycling, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Human activity intensifies land subsidence in the Yellow River Delta - Hui Xu; De Wang; Rongrong Ning; Xiaoyong Li; Xinpeng Tian; Xiaoli Bi; Zixiang Zhou; Yongwei Zhang (Estuarine, Coastal and Shelf Science, 2026)

Constructing a hierarchical hydro-confinement network for strong, water-retaining, and multifunctional soybean flour adhesives - Qiangsong Jiang; Zechang Wei; De Li; Yongning Tu; Xiaohong Yu; Zhinan Wang; Hong Lei (Chemical Engineering Journal, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Projecting shifts in drought-induced thresholds for wheat yield loss under climate change in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Fangzheng Chen; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (Agricultural and Forest Meteorology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The Lithosphere-Atmosphere-Ionosphere coupling (LAIC) processes around the 2024 Wushi (China) Mw7.1 earthquake - Xuemin Zhang; Angelo De Santis; Pan Xiong; Gianfranco Cianchini; Aisa Yisimayili; Saioa A. Campuzano; Na Yang; Serena D’Arcangelo; Jing Liu; Mariagrazia De Caro; Xinyan Li; Cristiano Fidani; et al. (Journal of Asian Earth Sciences, 2026)

Synergistic degradation of polycyclic aromatic hydrocarbons by Fusarium and Priestia in saline environments: From kinetic characterization to multi-omics dissection - Fenglei Han; Zhoutong Liu; Xiuxia Zhang; Fan Yang; Biao Wang; Feng Yao; De Li; Kang Xiong; Lihan Ren (International Biodeterioration & Biodegradation, 2026)

Future climate change increases the risk of wheat yield loss due to agricultural drought in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (European Journal of Agronomy, 2026)

Effects of rising CO2 concentrations on water dynamics and yields for C3 and C4 crops under both irrigated and dryland conditions in the Texas High Plains - Na Wen; Junyu Qi; Yue Wang; Gary W. Marek; Srinivasulu Ale; Puyu Feng; De Li Liu; Raghavan Srinivasan; Yong Chen (Environmental Modelling & Software, 2026)

Rational design of high entropy metal phosphide anode for highly reversible lithium storage - Liyi Liu; Xuhao Liu; Jianqiu Zhu; Zhihui Huo; Bin Chen; Wei Liang; Mingeng Li; Fangfei Lin; Mengli Zhao; De Li; Daming Chen; Zhen Wang; et al. (Chemical Engineering Journal, 2026)

Tailoring confinement and edge effects for enhancing performance in ultrahigh resolution quantum dot LEDs - Lihua Lin; Xingjie Yang; Jie Wang; Haolin Luo; De'er Li; Lingxia Zeng; Hailong Hu; Tailiang Guo; Fushan Li (Chemical Engineering Journal, 2026)

A novel polyphenol-metal chelation-based structure enabling epoxy with outstanding flame retardancy, toughening effect, smoke suppression performance and recyclability - Yao Deng; Hang-Ping Fang; Qing-Qing Bi; Ying-Ming Li; De-Yi Wang (Chemical Engineering Journal, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Erratum to “Molecular insights into anammox inhibition induced by environmentally relevant sulfamonomethoxine and functional recovery via voltage stimulation” [Bioresour. Technol. 436 (2025) 133018] - Zhan-Ling Wang; Bin Yang; Jing Cao; De-Peng Wang; Xu-Xiang Zhang; Mei Li (Bioresource Technology, 2026)

Correction: Research on the mise-à-la-masse method based on multi-frequency pseudo-random signals: a case study in the Baiquan Spring region, Jinan, China - Yang Yang; Zhi-de Li; Heng Zhang; Lin Wang; Jia-feng Mi (Hydrogeology Journal, 2026)

Moderate grazing strengthens the responses of plant diversity and ANPP to climatic factors in semi-arid grasslands - Jing Hou; Jun Liu; Zhiyu Liu; Yunmeng Tang; Chen Liu; Xuekai Sun; Kaimeng Wang; Huimei Zhang; Siyu Li; Ling Wang; Deli Wang; De-Hui Zeng; et al. (Agriculture, Ecosystems & Environment, 2026)

Phyllosphere to soil: How long-term fencing reshapes grassland microbial community construction and the functional genes - Jian Li; Yu Zhu; Daniel F. Petticord; David W. Frey; Lijie Huang; Ming-Kang Jin; Michiel Op de Beeck; Quan-Hui Ma; Shu-Huan Jin; Hong Ying; Xi-Mei Xue; Ling Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Activated autophagy drives the adaptive response to LPS-evoked lung pyroptosis in adolescent mice - Hao Li; Hua Wang; Ye-Xin Luo; Tian-Tian Wang; Kong-Wen Ouyang; Xin-Mei Zheng; Xin-Xin Zhang; Qing Ling; Yong-Wei Xiong; De-Xiang Xu; Hua-Long Zhu; Hua Wang (Toxicology and Applied Pharmacology, 2026)

Master genetic switches controlling sexual development in Leptinotarsa decemlineata - Jiangjie Li; Yimeng Chen; Jing Wang; Clauvis NT. Taning; Kristof De Schutter (Insect Biochemistry and Molecular Biology, 2026)

Rational design of zeolite-based composite catalysts in catalytic cracking of polyethylene - Yan Li; Zhe Ma; Jingyuan Shang; Ting Wang; Xingong Zhang; Peng Xu; Chenzhao Wang; Xiang Feng; De Chen; Chaohe Yang; Xiaobo Chen (Fuel, 2026)

Integration of UHPLC/QTOF-MS and GC–MS to decipher the subtle component difference between raw and bran-roasted Myristica fragrans (nutmeg) - Yijin Yang; Min Zhang; Huizhen Cheng; Yiqing Yao; Xue Li; Lingli Ma; Lili Hong; Mengyao Chen; Yadan Zou; Xin Chai; Qinhua Chen; Simiao Wang; et al. (Food Chemistry, 2026)

Study on browning mechanism of Antarctic krill meal during storage: based on the model system approach - Chao Guo; Xiang-Bo Zeng; Chang-Qiang Leng; De-Yang Li; Qian Wang; Fa-Wen Yin; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Promoting aerobic denitrification in the rhizosphere by vertical spatial stress: A strategy to enhance nitrogen conversion efficiency in constructed wetlands - Sheng-Jing Zhang; Hao-Qi Lu; Lei Yang; Li-De Wang; Bi-Han Zhang; Chao-Wen Deng; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

Silica microbubble powders from freeze-dried Pickering emulsions - Qimeng Wang; Albert T. Poortinga; Yuan Li; Elke Scholten; Renko de Vries (Chemical Engineering Journal, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Inhalation associated health risk assessment of atmospheric gaseous and size-resolved particulate PAHs in a large temperature range of 50 °C - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Chang-Yu Weng; Wan-Li Ma (Atmospheric Pollution Research, 2026)

Presence of Astrocytic S1R/5-HT1A Heterocomplex in the mPFC: A Putative Link to S1R Activation Mediated Faster Antidepressant-Like Effects - Peng Ren; Jing-Ya Wang; Meng-Jie Xu; Han Ni; Shuang Zhang; Chen-Xing Yue; De-Yi Yang; Yun-Feng Li (Molecular Neurobiology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Climate warming enhances sugarcane yield and increases annual harvest frequency in northern coastal New South Wales, Australia - Shijin Yao; De Li Liu; Bin Wang; Jonathan K. Webb; Siyi Li; Alfredo Huete; Keyu Xiang; Qiang Yu (Agricultural Systems, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

1-NP hijacks endocrine-metabolic checkpoints and disrupts testicular steroidogenesis by suppressing the cAMP-PKA-CREB-HMGCR axis - Xin-xin Zhu; Wei-wei Zhang; Ming-yue Hao; Zheng-ya Chen; Bai-fan Wan; Ming-hui Niu; Xiu-liang Li; Jian-hua Wei; Su-ya Liu; Shuang-ling Mi; Hua Wang; De-xiang Xu; et al. (Toxicology Letters, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

Assessing a dynamic CO2 input and response module in SWAT for simulating climate-induced phosphorus loss and economic costs - Na Wen; Yue Wang; Beibei Ding; Yiwen Han; Junyu Qi; Srinivasulu Ale; Puyu Feng; De Li Liu; Raghavan Srinivasan; Yong Chen (Journal of Hydrology, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Effect of lipid oxidation on the color deterioration of ready-to-eat oysters: Discussion based on the model system - Ying Luo; Jie Xu; Ying-Chen Fan; Zong-Han Wang; Yuan-Yuan Hu; De-Yang Li; Yu-Xin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Reducing curing temperature of multifunctional sucrose / tannic acid-based wood adhesive via catalysis method for improved water resistance and bonding strength - De Li; Bo Cai; Zhinan Wang; Qiangsong Jiang; Changying Ren; Jiawei Wang; Zechang Wei; Zhigang Wu; Hong Lei (Chemical Engineering Journal, 2025)

MUC1 in the upper–lower airway inflammatory continuum: an endotype-centered perspective - Linghui Meng; Jing Liu; Hsiao Hui Ong; De-Yun Wang; Li Shi (Inflammation Research, 2025)

Residue return and nitrogen application optimization can not balance crop yield increase and reducing emission in semi-arid region - Yinan Gao; De Li Liu; Bin Wang; Shaoqing Chen; Kelin Hu; Puyu Feng (Agricultural Systems, 2025)

Mitochondrial dysfunction-associated cellular senescence is partially involved in bleomycin-induced pulmonary fibrosis in mice - Ya-Xin Yao; Xue Lu; Zhao Li; Hao-Yu Liao; Zhi-Bing Liu; Hui Zhao; Hua Wang; De-Xiang Xu; Zhu-Xia Tan (Toxicology and Applied Pharmacology, 2025)

Genome-wide selective sweep analysis of plateau-type Tibetan and Zhashijia Sheep: Insights into adaptation, growth, and meat production traits - Dehui Liu; Xue Li; Jincai Zhao; Lei Wang; Quanbang Pei; De Sun; Qianben Ren; Guoxiang Bao; Buying Han; Wenkui Zhang; Song Wang; Fei Tian; et al. (Small Ruminant Research, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Theoretical simulation-guided design and fabrication of molecularly imprinted hydrogels for selective osteopontin separation - Shichao Xuan; Wenhao Ding; Fengzhi Qiao; Yanbin Li; Shaolei Wang; Zhe Zhang; Changhong Ma; Huaxi Yi; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Research International, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Bi-directional pH-responsive cellulose nanocrystals-based pesticide microcapsules for sustainable agriculture - Jia-wei Ding; Li-na Guo; Shu-heng Li; Qin Gao; Wang Wu; De-qiang Li; Jun Li (Carbohydrate Polymers, 2025)

Molecular insights into anammox inhibition induced by environmentally relevant sulfamonomethoxine and functional recovery via voltage stimulation - Zhan-Ling Wang; Bin Yang; Jing Cao; De-Peng Wang; Xu-Xiang Zhang; Mei Li (Bioresource Technology, 2025)

Pollution characteristic and temporal trend of PM2.5-bound heavy metals in a megacity of Northeast China: Implication for the effect of air pollution control policy - Jin-Wen He; Li-Yan Liu; Chang-Yu Weng; De-Qi Wang; Shi-Ming Jia; Wan-Li Ma (Atmospheric Pollution Research, 2025)

Identifying the optimum irrigation strategies to maximize canola yield and profitability under climate change in Guanzhong Plain, China - Qaisar Saddique; De Li Liu; Ali Ajaz; Bin Wang; Xiaobo Gu; Muhammad Adnan; Puyu Feng; Yunfei Wang; Yufeng Zou; Huanjie Cai (Irrigation Science, 2025)
Climate change has a substantial impact on Chinese canola production, introducing a high level of uncertainty regarding future climatic conditions and their potential impact on canola production and gross margins. This study focused on identifying the optimal irrigation strategy to enhance the profitability of canola production in the Guanzhong Plain under future climate change conditions. In this study, we used the calibrated Agricultural Production Systems sIMulator (APSIM)-Canola model with the downscaled daily climate projections from 27 general circulation models (GCMs). These simulations were conducted under two Shared Socio-economic Pathways scenarios (SSP245 and SSP585) to assess the impact of climate change on canola phenology, rainfed and irrigated crop yield. We also conducted a gross margin analysis to assess the profitability dynamics of supplying irrigation to rainfed canola crop. An increase in rainfed canola yield was observed for all simulation periods, with an average increase of 11%, 15%, and 17% for the 2030s, 2060s, and 2090s, respectively. Supplementary irrigation using a threshold of 10–60% of plant available water capacity (PAWC) was found to be effective. Overall, it led to a 28% increase in yield for rainfed and an 85% improvement in gross margin. Beyond the threshold of 60% PAWC, additional irrigation did not result in statistically significant increases in yield and gross margin. We identified the optimal amount of irrigation for achieving maximum water productivity (WP) ranges from 85 to 150 millimeters. By avoiding irrigation when the soil’s plant available water capacity (PAWC) is over 60%, up to 44% of water can be saved. These findings could be useful for policymakers and farmers in planning for sustainable and enhanced canola production in the region.

How waterbird communities respond to seasonal and environmental factors in rice fields adjacent to a Ramsar wetland - Yu Zheng; Yu Chen; Yunwei Song; Guangyao Wang; Yong Zhang; Xinsheng Chen; Chunlin Li; Willem F. de Boer (Agriculture, Ecosystems & Environment, 2025)

Evaluating dextrorphan as a wastewater biomarker for cough suppressant use: A longitudinal study in China - Xue-Ting Shao; Xin-Dong Ma; Jing-Long Li; Jake W. O’Brien; Kevin Thomas; De-Gao Wang (Water Research, 2025)

No deformation propagation outward of the plateau across the Yalong Thrust Belt in Southeast Tibet - P. Pitard; A. Replumaz; P.H. Leloup; M.-L. Chevalier; S. Wang; M. Bai; X. Ou; M. Bernet; M. Balvay; E.R. Sobel; A. Vezinet; C. Gautheron; et al. (Tectonophysics, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Evolution of global O3-NOx-VOCs sensitivity before and after the COVID-19 from the ratio of formaldehyde to NO2 from satellite observations - Dakang Wang; Dongchuan Pu; Isabelle De Smedt; Lei Zhu; Xiankun Yang; Wenfu Sun; Hui Xia; Zhaolong Song; Xicheng Li; Juan Li; Aoxing Zhang; Xu Feng; et al. (Journal of Environmental Sciences, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Biphasic continuously composite electrolyte design for high-performance solid-state Li–CO2 batteries - Qian-Cheng Zhu; Shu-Jian Li; Zi-Yuan Wang; Fu-Li Zhang; Jin-Hao Xie; De-Yu Mao (Chemical Engineering Journal, 2025)

Insights into excitonic dynamics in conformational distorted porphyrinic covalent organic frameworks for efficient selective photooxidation - Wang-Kang Han; Jiayu Li; Kang Deng; Jing-Dong Feng; Ruo-Meng Zhu; Ming-De Li; Zhi-Guo Gu (Chemical Engineering Journal, 2025)

Biomass-derived organic aerogels endowed flexible polyurethane foam with excellent flame retardance, smoke suppression, bacteriostasis and enhanced mechanical property - Ying-Ming Li; Yao Deng; Hang-Ping Fang; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

The role of evaporites in Kiruna-type iron oxide-apatite deposits in the Northern Norrbotten region, Sweden: Evidence from in situ halogen analyses of scapolite - Li-Ping Zeng; Carl Spandler; Ying-Ying Liu; Johannes Hammerli; Wang Liao; Hao Hu; Sanna Olsson; De-Xian Zhang; Tao He; Jian-Wei Li; Xin-Fu Zhao (Chemical Geology, 2025)

Projection of climate change and extreme climate events during cropping seasons in Northwest Bangladesh - Md Belal Hossain; Ketema Zeleke; De Li Liu; K. M. Shamsul Haque; Bin Wang (Theoretical and Applied Climatology, 2025)
Understanding cropping season-specific changes in future climate variables and extremes is crucial for formulating effective adaptation strategies. This research investigated the future changes in climate variables and extreme events in the northwest Bangladesh using multiple climate models downscaled from Couple Model Intercomparison Project Phase-6 under four shared socioeconomic pathways: SSP126, SSP245, SSP370, and SSP585 for three locations viz. Rangpur, Bogura, and Rajshahi. We analyzed relative changes in maximum and minimum temperatures, rainfall, heat stress days, accumulated growing degree days (AGDD), total rainy days, and heavy rainfall days for the near future (NF, 2031–2065) and far future (FF, 2066–2100) relative to base period (1988–2022) during the growing period of rainfed rice, irrigated rice, wheat, maize, and potato. Results indicate that seasonal maximum (T max ) and minimum (T min ) temperatures are expected to rise consistently across all emission scenarios except SSP126, which shows a downward trend after 2070. The greatest T max rise is projected during Potato, while the least in rainfed rice. However, the T min rise is anticipated to outweigh T max , with the highest T min rise for wheat and potato under SSP585. Rainfall is expected to increase notably during rainfed rice but decline during potato season. All crops are projected to face more heat stress days and AGDD compared to base period. Furthermore, heavy rainfall days is projected to increase during rainfed rice period, while number of rainy days are expected to decline, suggesting higher rainfall intensity in the future. Further research is needed to assess crop yield impacts and develop adaptation strategies to address climate risk in the region.

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Long-term cadmium stress influenced the immune response of Pardosa pseudoannulata by modulating its gut microbiota and hemolymph metabolome - Jinjin Li; Yuan-de Peng; Rong Zhou; Jie Peng; Qingling She; Xinyi Yang; Juan Wang; Zhi Wang; Qisheng Song (Journal of Environmental Sciences, 2025)

Evolution of rock mass stress, movement, and deformation during injection-production processes in coal mines that have been converted into natural gas storage facilities - Xuejie Deng; Xiaoming Shi; Zhide Wu; Yuan An; Jichu Wang; Shicong Li; Xifeng Liang; Benjamin de Wit (Geomechanics for Energy and the Environment, 2025)

Sensory characteristics and key odor-active compounds of oxidized Antarctic krill oil: A comparative study with oxidized fish oil - Gui-Mei Dong; Rui-Ying Wang; Fa-Wen Yin; De-Yang Li; Lei Qin; Da-Yong Zhou (Food Chemistry, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Soil organic carbon improvement for mitigating crop yield losses under global warming - Qinsi He; Linchao Li; Yu Shi; Puyu Feng; Ke Liu; Shengwei Zhang; De Li Liu; Zikui Wang; Matthew Tom Harrison; Sien Li; Qiang Yu; Kadambot H.M. Siddique (European Journal of Agronomy, 2025)

Polyethylene biodegradation by gut microbiota of Lasioderma serricorne: Isolation, identification, and mechanistic insights - Ming-Fei Wu; Pan-Pan Jia; Ling He; Li-Ping Ma; Yan Li; Lan-Chen Zhang; Dong-Mei Xie; Xiao-Bing Li; Tian-Nv Wang; De-Sheng Pei (Chemical Engineering Journal, 2025)

Characteristics, sources and risk assessment of volatile organic compounds in a subway environment - A case study in Xi’an, China - Meng Xiu; Yan Cheng; Shuting Liu; Yu Huang; Yonggang Xue; Yan Li; Yanan Meng; Rohan Jayaratne; Xianyu Wang; Phong K. Thai; Alma Lorelei de Jesus; Lidia Morawska (Building and Environment, 2025)

Understanding fear generalization in adult zebrafish in predator-based assays - Jiayou Jiang; Jiyi Wang; Daniil D. Martynov; Nikita I. Golushko; Yixin Qin; Yunqian Zhang; Chonguang Zhao; Chaoming Wang; Yucheng Liu; Haoyu Feng; Huiling Cai; Kai He; et al. (Behavioural Processes, 2025)

Vibration mechanics involved in buzz pollination lead to size-dependent associations between bumblebees and Pedicularis flowers - Yuanqing Xu; Bentao Wu; Mario Vallejo-Marín; Peter Bernhardt; Mark Jankauski; De-Zhu Li; Stephen Buchmann; Jianing Wu; Hong Wang (Science China Life Sciences, 2025)

Research on the mise-à-la-masse method based on multi-frequency pseudo-random signals: a case study in the Baiquan Spring region, Jinan, China - Yang Yang; Zhi-de Li; Heng Zhang; Lin Wang; Jia-feng Mi (Hydrogeology Journal, 2025)

Spectral characteristics of the digital filter for electromagnetic field decomposition in 3D MCSEM - Shu-Ming Wang; Qing-Yun Di; Yun-xin Xiao; Qi-chao Fang; De-shan Li (Applied Geophysics, 2025)

Collagen alpha-5(IV) chain activation by nuclear factor 1/C promotes nasopharyngeal carcinoma progression - Ying Cao; Peibei Wang; Peng Li; Kai Wei; Xinle Kang; Xiao Han; De Huai; Bing Fei (Human Cell, 2025)

Efficient remediation and synchronous recovery of uranium by phosphate-functionalized magnetic carbon-based flow electrode capacitive deionization - De Wang; Jing Wang; Di Zhang; Jiaxing Li (Water Research, 2025)

Annual growth bands in the late Carboniferous reef-building colonial rugose coral Ivanovia and their environmental significance - Yong-Li Zhang; Wen-Tao Huang; En-Pu Gong; Guan-Ming Lai; Mark A. Wilson; Jun-Jie Wang; Ning-Feng Du; De-Peng Li (Palaeoworld, 2025)

A new fossil record of Adiantum (Pteridaceae) from Oligocene of Qaidam Basin, Northwest China and its palaeoenvironmental implications - Hong-Yu Chen; Tao Yang; Ya Li; Dieter Uhl; Lei Han; Jia-Hao Cai; Li Zhang; Yong-Dong Wang; De-Fei Yan (Palaeoworld, 2025)

Pathways of organic carbon mineralization and benthic fluxes of alkalinity and dissolved inorganic carbon in sediments of large inland seas: The Bohai Sea and North Yellow Sea - Jian-Hua Ren; Mao-Xu Zhu; De-Yan Wang; Qing-Qing Li; Tie Li (Journal of Marine Systems, 2025)

Functional nucleic acid-stabilized selenium nanotechnology enable synergistic healing of diabetic chronic wounds - Si-Wei Yang; Jing Wang; Yan Tan; Xiao Jing; Chen-Yu Wang; Zhi-Li Yao; Wen-Hui Wang; Yong-Ji Li; Hao-Rui Li; Yan Zhao; De-Ming Kong; Qi-Liang Cai (Chemical Engineering Journal, 2025)

Structural design and solid electrolyte interphase modulation of SiOC-based anodes via N-doping for fast-charging lithium-ion batteries - Juan Wang; Yaqian Li; Siwen Jin; Xiuhui Zheng; Juncong Yuan; Debin Kong; Han Hu; Xiang Feng; De Chen (Chemical Engineering Journal, 2025)

Improving electrochemical performance of silicon-carbon anode for lithium-ion batteries via one-step etching - Huai-Min Wang; Ying Zhou; Bi-Rong Luo; De-Jun Li; Bo Zhang (Chemical Engineering Journal, 2025)

Rainfall nowcasting models: state of the art and possible future perspectives - Davide Luciano De Luca; Francesco Napolitano; Dongkyun Kim; Christian Onof; Daniela Biondi; Li-Pen Wang; Fabio Russo; Elena Ridolfi; Benedetta Moccia; Flavia Marconi (Hydrological Sciences Journal, 2025)

The patterns of the Populus euphratica forest and cropland changes upstream of the Tarim River under the policy-driven human activities during 1960–2023 - Haoyu Wang; Junli Li; Yingming Ke; Yihan Zhang; Chenghu Zhou; Chunxia Wei; Zhanfeng Shen; Philippe De Maeyer; Tim Van de Voorde (International Journal of Remote Sensing, 2025)

Risk prioritization and experimental validation of per- and polyfluoroalkyl substances (PFAS) in Chaohu Lake: Based on nontarget and target analyses - Wei Chang; Shen-Dong Xu; Ting Liu; Lan-Lan Wu; Si-Ting Liu; Gang Liu; Jian Sun; Ye-Xin Luo; Lei Gao; Hao Li; Qi Lu; Zhi Yuan; et al. (Journal of Hazardous Materials, 2025)

Evaluating the environmental impact of polylactic acid plastics in agriculture: Microbial degradation and plant interaction insights - Jiaxi Liu; Yifan Duan; Tianjiao Song; Qing Liu; Peiyuan Wang; Lijun Hou; Yufan Wang; Yiqiong Zhang; Jinyi Zhang; Li Li; Caroline de Tender; Yanbing Lin (Journal of Environmental Management, 2025)

Correction for calcium interference in the 40Ar/39Ar dating method - Wan-Feng Zhang; Jun-Jie Wang; De-Wen Zheng; Ming Xiao; Jia Zhang; Jun-Jie Li; Yu-Lian Zhang; Ying-De Jiang; Fei Su; Li Li; Yi-Gang Xu (Icarus, 2025)

Effect of air frying on in vitro digestion and transport properties of scallop (Patinopecten yessoensis) adductor muscles: Insights from peptidomics analyses - Zi-Ye Wang; Qian Wang; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2025)

Zn-alloying induced spectral narrowing in wurtzite CuInS2 quantum dots for deep-red light-emitting diodes - Haoran Chen; Haofeng Li; Bohua Dong; Lei Hou; Dechao Yu; Weigao Wang; Xiaobin Xie; Celso de Mello Donega; Lixin Cao; Chenghui Xia (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Gut microbiota modulation: a narrative review on a novel strategy for prevention and alleviation of ovarian aging - Wei Lyu; De-Feng Li; Shu-Ying Li; Hua Hu; Jian-Yun Zhou; Ling Wang (Critical Reviews in Food Science and Nutrition, 2025)

Identification and functional characterization of grass carp TRPV1 in facilitating GCRV infection - Zi-Yu Xie; Yang Xu; Qiu-Shi Zhang; Zhi-Ming Liu; Liang Hu; Wei Wang; Tiao-Yi Xiao; De-Liang Li; Xin-Yu Liang; Jun-Hua Li (Aquaculture, 2025)

Low-dose tire wear chemical 6PPD-Q exposure elicit fatty liver via promoting fatty acid biosynthesis in ICR mice - Lili Wang; Weitian Tang; Nan Sun; Jia Lv; Jiayue Hu; Lin Tao; Cheng Zhang; Hua Wang; Li Chen; De-Xiang Xu; Yihao Zhang; Yichao Huang (Journal of Hazardous Materials, 2025)

Optimizing stubble returning rate in mulched farmland to balance trade-offs between greenhouse gas emission and maize yield under climate change - Lihong Wu; Bin Wang; Hao Quan; De Li Liu; Hao Feng; Fangzheng Chen; Lianhai Wu; Qiang Yu (Field Crops Research, 2025)

Amine-Functionalized SiC nanowires aerogel synchronizes high capacity and ultra-rapid kinetics for CO2 capture - Yanni Ran; Kang Peng; Ziyan Li; Xingwang Guo; Honglin Chen; Shengxuan Cai; Lei Su; Min Niu; De Lu; Hongjie Wang (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Dire need for quantification of environmental impacts associated with breeding climate-resilient crops - Chunhu Wang; Matthew Tom Harrison; De Li Liu; Rui Yang; Meixue Zhou; Yunbo Zhang; Ke Liu (Agricultural Systems, 2025)

Method for calculating the bearing capacities of caisson foundations considering the effects of caisson construction - De-jie Li; Xu-tao Zeng; Chong Shi; Lie-wang Qiu (Marine Georesources & Geotechnology, 2025)

Unlocking soil health: Are microbial functional genes effective indicators? - Jiyu Jia; Ron de Goede; Yizan Li; Jiangzhou Zhang; Guangzhou Wang; Junling Zhang; Rachel Creamer (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Rapid identification and evolution analysis of flash droughts in the eastern coast of China - Chuan-hao Yang; De-kui Li; Xiao-tong Zhou; Cui-fang Zhang; Ke Zheng; Qian Wang (Journal of Hydrology, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Ferrosilicon alloy as both reactant and catalyst for hydrogenation of SiCl4: Thermodynamics, mechanism, and kinetics studies - Zheng-Peng Wang; Zi-Yi Chi; Huai-Qiang Dou; Xue-Gang Li; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Polygonatum cyrtonema Hua polysaccharide alleviates ulcerative colitis via gut microbiota-independent modulation of inflammatory immune response - Jin-Yang Shi; Yong-Jian Wang; Qian-Wen Bao; Ya-Min Qin; Pei-Pei Li; Qiao-Qiao Wu; Cheng-Kai Xia; De-Ling Wu; Song-Zi Xie (Carbohydrate Polymers, 2025)

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

A feasibility study on cortisol and cortisone as biomarkers for psychological stress in wastewater-based epidemiology - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Jian-Guo Lin; De-Gao Wang (Water Research, 2025)

Piperidine and bis-piperidine alkaloids from the peels of Areca catechu and their monoamine oxidases inhibitory activity - Song Wang; De-Zhi Wang; Xia Zhang; Zi-Wei Li; Dong-Hao Lu; Zheng-Jin Jiang; Min Ma; Min Song; Xiao-Qi Zhang (Phytochemistry, 2025)

Impact load identification of ship panels under tire drop action based on the data-driven regression with regularization - Gui-jie Shi; De-yu Wang; Da-wei Gao; Qiang Li (Ocean Engineering, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

Antifungal Susceptibility of Melanized Fungi Isolated from CARD9 Deficient Patients: Implications for Treatment of Refractory Infections - Ying Ji; Yalong Li; Weiwei Wu; Sybren de Hoog; Zhe Wan; Qian Wang; Hao Zhang; Jin Yu; Xueke Niu; Ruoyu Li; Wei Liu; Yinggai Song (Mycopathologia, 2025)

Climate and biological factors jointly shape microbial community structure in the Yarlung Zangbo River during the dry season - Zhao Hao; Yanhong Wang; Enyong Chen; Xueyan Mu; Jiawei Li; Qiong La; Ji De; Yixuan Liu; Shuaishuai Huang; Weiguo Fang; Pengxi Cao; Junwei Wang; et al. (Science of The Total Environment, 2025)

Retrieval of 1 km surface soil moisture from Sentinel-1 over bare soil and grassland on the Qinghai-Tibetan Plateau - Zanpin Xing; Lin Zhao; Lei Fan; Gabrielle De Lannoy; Xiaojing Bai; Xiangzhuo Liu; Jian Peng; Frédéric Frappart; Kun Yang; Xin Li; Zhilan Zhou; Xiaojun Li; et al. (Remote Sensing of Environment, 2025)

Overlooked importance: The supporting roles of satellite wetlands for waterbirds around the Yangtze-connected lakes, China - Guangyao Wang; Chengrong Pan; Shilong Yu; Sheng Xu; Shuheng Dai; Jingjing Ding; Xiangrong Song; Chunlin Li; Yong Zhang; Willem F. de Boer (Journal of Environmental Management, 2025)

Effects of refrigeration and freezing on milk fat globule membrane lipids in stored breast milk: Insights from non-targeted lipidomics - Shaolei Wang; Pengyue Wang; Xia Ma; Fengzhi Qiao; Zhe Zhang; Jiadong Li; Huaxi Yi; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

Designing virtual maize cultivars with optimal planting date and density can improve yield and water use efficiency under plastic mulching conditions - Lihong Wu; Bin Wang; Hao Quan; De Li Liu; Hao Feng; Fangzheng Chen; Lianhai Wu (Field Crops Research, 2025)

Assessing the impact of climate variability on Australia’s sugarcane yield in 1980–2022 - Shijin Yao; Bin Wang; De Li Liu; Siyi Li; Hongyan Ruan; Qiang Yu (European Journal of Agronomy, 2025)

Soil with high plant available water capacity can mitigate the risk of wheat growth under drought conditions in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Yanmin Yang; Siyi Li; Mingxia Huang; Alfredo Huete; Qiang Yu (European Journal of Agronomy, 2025)

An efficient superhydrophilic photothermal membrane of graphene-decorated TiO2 nanotube arrays for solar desalination - Fei Liu; Liang Wang; De Sun; Bingbing Li; Hui Tian; Zhi Qi; Shenglan Zhou (Desalination, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Evaluation of enzyme activity predictions for variants of unknown significance in Arylsulfatase A - Shantanu Jain; Marena Trinidad; Thanh Binh Nguyen; Kaiya Jones; Santiago Diaz Neto; Fang Ge; Ailin Glagovsky; Cameron Jones; Giankaleb Moran; Boqi Wang; Kobra Rahimi; Sümeyra Zeynep Çalıcı; et al. (Human Genetics, 2025)

Experimental and numerical study of dynamic compressive stress wave propagation across geological lithological layers - Wenxin Li; Changdi He; Xiao Wang; Chunguang Wang; Tulio Dias De Almeida; Lianjun Chen; Brijes Mishra (Bulletin of Engineering Geology and the Environment, 2025)

Delaying sowing time and increasing sowing rate with plastic mulching can enhance wheat yield and water use efficiency under future climate change - Lihong Wu; Hao Quan; Hao Feng; Dianyuan Ding; Lina Wu; De Li Liu; Bin Wang (Agricultural and Forest Meteorology, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Color-neutral WO3-I2 complementary electrochromic device based on reversible iodine electrodeposition - Xianglin Guo; Yingyu Chen; Shanlin Li; Lu Chen; Shengbin Xia; Qizhi Wang; De Li; Zhen Wang; Xiaoyu Wang (Chemical Engineering Journal, 2025)

Functional design of caprolactam for aliphatic polyamide with enhanced flame retardancy, mechanical robustness, and chemical recyclability - Feng-Ming He; Yan-Fang Xiao; Qin Zhang; Min Jiang; Xin Li; De-Ming Guo; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Enhancement of the yield of poly (ethylene terephthalate) hydrolase production using cell membrane protection strategy - Xiao-Qian Chen; De-Ming Rao; Xing-Yu Zhou; Yang Li; Xiao-min Zhao; De-min Kong; Han Xu; Chu-Qi Feng; Lei Wang; Ling-Qia Su; Zheng-Fei Yan; Jing Wu (Bioresource Technology, 2025)

Outdoor space design and its effect on mental work performance in a subtropical climate - Yilu Luo; Xintong Ma; Jinmin Li; Chunxiao Wang; Richard de Dear; Shuai Lu (Building and Environment, 2025)

Maize kernel nutritional quality—an old challenge for modern breeders - Decui Li; Anqi Hao; Wen Shao; Weiwei Zhang; Fuchao Jiao; Haiyan Zhang; Xueyan Dong; Yuan Zhan; Xia Liu; Chunhua Mu; Zhaohua Ding; De Xue; et al. (Planta, 2025)

Uncovering the mechanisms of diosmin in treating obesity-related kidney injury based on network pharmacology, molecular docking, and in vitro validation - Jun-Xing Zhu; Fan Chu; Wen-Man Zhao; Rui Shi; Zhi-Juan Wang; Xun-Liang Li; Yu-Yu Zhu; De-Guang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Geochemistry and Sr–Nd–Pb isotope geology of intraplate cenozoic basaltic volcanism of NE Brazil: remnant of an aborted mid-ocean ridge? - Zorano Sérgio de Souza; Frederico Castro Jobim Vilalva; Jean-Michel Lafon; Chao Wang; Xiao-Dong Deng; Jian-Wei Li; Elton Luiz Dantas; Rafael Gonçalves da Motta; Joyce Lorena Oliveira (Contributions to Mineralogy and Petrology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Two new 2-arylbenzo[ b ]furans from Itea indochinensis and their anti-hepatocellular carcinoma and anti-oxidant effects - Fang-Fang Xu; Jin-Zhen Jian; Yi-Jv Li; Zhi-Wei Wang; Guo-Yong Luo; Wu-De Yang (Natural Product Research, 2025)

Texture, Sensory, and Fillet Color Differences Among Commercially Available United States Farmed Channel Catfish ( Ictalurus punctatus ) and Hybrid Catfish (Channel Catfish ♀ × Blue Catfish ( Ictalurus furcatus ) ♂) and Imported Vietnamese Swai ( Pangasianodon hypophthalmus ) - Andrew Johnson; Amit Morey; Baofeng Su; Michael Coogan; Darshika Hettiarachchi; De Xing; Jinhai Wang; Shangjia Li; Tasnuba Hasin; Wenwen Wang; Mei Shang; Logan Bern; et al. (Journal of Aquatic Food Product Technology, 2025)

Identification of driving factors for heavy metals and polycyclic aromatic hydrocarbons pollution in agricultural soils using interpretable machine learning - Jun Wang; Yirong Deng; Zaoquan Huang; De’ an Li; Xiaolu Zhang (Science of The Total Environment, 2025)

Aspongpyridiniums A−J, amino acid-derived pyridinium salts from insect species Aspongopus chinensis - Jinchun Nie; Shuang Guo; Didi Wang; Zhenwei Li; Daidi Zhang; Wei Li; De-an Guo (Phytochemistry, 2025)

Multi-stage magma emplacement in the western end of the Jinchuan Ni Cu sulfide deposit, NW China, and mineral exploration strategy based on exploration data - Long-Jiao Li; Xian-Cheng Mao; Zhan-Kun Liu; Xin-Ming Duan; Yun-Qi Wang; Qi-Xing Ai; De-Xian Li (Journal of Geochemical Exploration, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Tailoring the surface islands to modulate the diffusion of guest molecules over the TS-1 zeolites for enhanced selectivity in the 1-hexene epoxidation - Juncong Yuan; Yaqi Dong; ZePing Wang; Xuliang Deng; Ruiying Li; Jiaxu Wang; Yuchang Zhu; Zhe Ma; Yibin Liu; De Chen; Chaohe Yang; Xiang Feng (Chemical Engineering Journal, 2025)

Combinational delivery of TLR4 and TLR7/8 agonist enhanced the therapeutic efficacy of immune checkpoint inhibitors to colon tumor - Mengjiao Wang; Quan Wan; Chenglv Wang; Qianyu Jing; Yujie Nie; Xiangyan Zhang; Xin Chen; De Yang; Runsang Pan; Linzhao Li; Lan Zhu; Huan Gui; et al. (Molecular and Cellular Biochemistry, 2025)

Evaluation of metagenomic next-generation sequencing (mNGS) combined with quantitative PCR: cutting-edge methods for rapid diagnosis of non-invasive fungal rhinosinusitis - Xiao Liu; Shaoqin Zhou; Rong Yan; Caifeng Xia; Ruoning Xue; Zhe Wan; Ruoyu Li; Sybren de Hoog; Sarah A. Ahmed; Quangui Wang; Yinggai Song (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The increasing rate of net carbon uptake in Eurasia has been declining since the early 2000s - Mingjuan Xie; Geping Luo; Amaury Frankl; Kwinten Van Weverberg; Yuanyuan Huang; Xiaofei Ma; Yuangang Wang; Chaofan Li; Xiuliang Yuan; Olaf Hellwich; Wenqiang Zhang; Yu Zhang; et al. (Science of The Total Environment, 2024)

Screening potential biomarkers for acute respiratory infectious diseases from antipyretics, antiviral, and antibiotics in wastewater - Xue-Ting Shao; Hao-Yang Li; Zhen-Fang Gong; Jian-Guo Lin; De-Gao Wang (Science of The Total Environment, 2024)

Magmatic differentiation of peralkaline granites: Constraints from iron isotope fractionation between Fe-bearing minerals - De-Hong Du; Xiao-Lei Wang; Hang Xu; Shuo Wang; Ying-Ze Zhang; Weiqiang Li (Lithos, 2024)

Synthesis of magnetically recyclable FeCeO nanocrystals with heterojunction between Fe2O3 and CeO2 via one-step method toward efficient organic dyes degradation by activating peroxymonosulfate - Liang Li; Chao-qun Wu; De-xiang Sun; Nan Zhang; Ting Huang; Yong Wang (Journal of Cleaner Production, 2024)

Enhanced 2,4-dichlorophenol degradation by remodeling of crude soil microbial community structure using carbon-based immobilized microorganisms - Kangning Dong; Xiuxia Zhang; Lihan Ren; De Li; Kang Xiong; Ruirui Wang; Yupeng Zhang; Shuai Zuo (Journal of Environmental Chemical Engineering, 2024)

Durable underwater superoleophobic hydrogels for oil- and Cu(II)-containing water purification - Chang-Lian Xu; Na Ji; Xingyue Wu; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Pietro Paolo de Oliveira e Silva; Guochun Lv; Junzhuo Cai; et al. (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

Effects of particle breakage on rockslide deposition formations: insights from rigid finite element modelling - Hui Jiang; Jing-Jing Zhu; Wen-Jie Zhang; Jin-Ting Wang; Yuan-De Zhou; Xiu-Li Du (Bulletin of Engineering Geology and the Environment, 2024)

Concurrent measurements of bark and xylem water contents in Malus pumila Mill. stems using improved flexible sensors - Xianglin Cheng; Xiaofei Yan; Zhongyi Wang; Junhui Li; Ricardo F. de Oliveira; Taisheng Du; Qiang Cheng (Agricultural and Forest Meteorology, 2024)

Improved identification and monitoring of meteorological, agricultural, and hydrological droughts using the modified nonstationary drought indices in the Yellow River Basin of China - Ben Niu; Yi Li; De Li Liu; Lulu Xie; Lei Wang; Xiaohui Jiang; Hao Feng; Qiang Yu; Jianqiang He; Haixia Lin (Journal of Hydrology, 2024)

Hierarchically porous and flexible chitin-fiber/melamine-sponge composite filter with high-loading of PdAu nanoparticles for effective hydrodechlorination of chlorophenols - De-Chang Li; Zhengbin Tian; Xianliang Huang; Wan Zhang; Wenquan Wang; Qian Zhang; Xiaohui Deng; Guang-Hui Wang (Journal of Hazardous Materials, 2024)

Size-resolved gas-particle partitioning of polycyclic aromatic hydrocarbons in a large temperature range of 50 ℃ - De-Qi Wang; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

Significant implications of diversity and stability for ecosystem sustainability necessitate differentiated management strategies: A case study of the urban agglomeration around Hangzhou Bay, China - De Zhou; Shanshan Pan; Siyuan Li; Huan Li; Qingying Ding; Li Wang (Journal of Environmental Management, 2024)

Investigating the role of membrane lipid composition differences on spray drying survival in Lactobacillus bulgaricus using non-targeted Lipidomics - Fengzhi Qiao; Shaolei Wang; Jian He; Weilian Hung; Xia Ma; Pimin Gong; Jiadong Li; Ting Sun; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Bio-derived modified halloysite nanotubes as eco-friendly flame retardants to endow epoxy with high thermal stability, mechanical performance and flame retardancy - Qing-Qing Bi; Ying-Ming Li; Lu He; De-Yi Wang (Chemical Engineering Journal, 2024)

Uranium electrolytic deposition with regenerable Se2− active sites at low cell voltage - Ranran Jiao; Hongyan Zhou; De Wang; Suyuan Zeng; Jiaxing Li (Chemical Engineering Journal, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Fire-safe and multifunctional epoxy/layered double hydroxide composites via an interfacial catalysis - Zhi Li; Guan-Bin Huang; Han Li; Lei Zhang; Zhiqi Liu; Jimena De La Vega; Raquel Sánchez Díaz; Qingwen Zeng; De-Yi Wang (Applied Clay Science, 2024)

Identifying the best fertilization practices by many-objective optimization to mitigate nitrous oxide emissions from tea field in the subtropics in Central China - Meihui Wang; Yong Li; Chujie Liao; De Li Liu; Jianlin Shen; Jinshui Wu (Agriculture, Ecosystems & Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Modelling the impacts of future climate change on mixed farming system in southeastern Australia - Muhuddin Rajin Anwar; Bin Wang; Aaron Simmons; Neville Herrmann; De Li Liu; Annette Cowie; Cathy Waters (European Journal of Agronomy, 2024)

Two-dimensional migration characteristics of contaminant through composite liner with arbitrarily distributed defects - Tianyi Li; De’an Sun; Zheng Chen; Yang Chen; Xianlei Fu; Lei Wang (Computers and Geotechnics, 2024)

Pyrene-4,5,9,10-tetraone-based covalent organic framework/carbon nanotube composite as sodium-ion cathodes with high-rate capability - Lei Chen; Yuke Li; Yuemiao Zhang; Shi-Bin Ren; Jinhai Bi; Xinxian Xue; De-Man Han; Di Wu; Yujing Wang; Xianlang Chen; Yingpeng Wu (Chemical Engineering Journal, 2024)

No-tillage facilitates soil organic carbon sequestration by enhancing arbuscular mycorrhizal fungi-related soil proteins accumulation and aggregation - Hongbo Yang; Guangshuai Wang; Jun Wang; Qiong Xiao; Zhongyang Li; Caroline De Clerck; Jeroen Meersmans; Gilles Colinet; Wenju Zhang (CATENA, 2024)

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Biogenic Selenium Nanoparticles Synthesized by L. brevis 23017 Enhance Aluminum Adjuvanticity and Make Up for its Disadvantage in Mice - Zheng Zhang; Xinqi De; Weijiao Sun; Runhang Liu; Yifan Li; Zaixing Yang; Ning Liu; Jingyi Wu; Yaxin Miao; Jiaqi Wang; Fang Wang; Junwei Ge (Biological Trace Element Research, 2024)

An improved meteorological variables-based aerosol optical depth estimation method by combining a physical mechanism model with a two-stage model - Fuxing Li; Xiaoli Shi; Shiyao Wang; Zhen Wang; Gerrit de Leeuw; Zhengqiang Li; Li Li; Wei Wang; Ying Zhang; Luo Zhang (Chemosphere, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Modeling soil water and salt dynamics in cotton-sugarbeet intercropping and their monocultures with biochar application - Xiaofang Wang; Yi Li; Asim Biswas; Honghui Sang; Jianqiang He; De Li Liu; Qiang Yu; Hao Feng; Kadambot H.M. Siddique (Soil and Tillage Research, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Biotransformation of chenodeoxycholic acid by human intestinal fungi and the agonistic effects on FXR - Xuemei Wei; Changliang Yao; Xin He; Jiayuan Li; Yulu Wang; Chao Wang; Qinhua Chen; Xiaochi Ma; De-an Guo (Phytochemistry, 2024)

Exposure to 1-nitropyrene after weaning induces anxiety-like behavior partially by inhibiting steroid hormone synthesis in prefrontal cortex - Xiao-Xi Chen; Bo Wang; Wei Cai; Yi-Hao Zhang; Li Shen; Yan-Yan Zhu; Tao Wang; Xiu-Hong Meng; Hua Wang; De-Xiang Xu (Journal of Hazardous Materials, 2024)

Sphingobium sp. SJ10-10 encodes a not-yet-reported chromate reductase and the classical Rieske dioxygenases to simultaneously degrade PAH and reduce chromate - Ze-Shen Liu; Ke-Huan Wang; Qun Han; Cheng-Ying Jiang; Shuang-Jiang Liu; De-Feng Li (Journal of Hazardous Materials, 2024)

Granular activated carbon supported polyethylene glycol modified nano-zero-valent iron immobilized microbial removal of 2,4-dichlorophenol in water - Kangning Dong; Xiuxia Zhang; Kang Xiong; De Li; Lihan Ren; Yanyan Gao; Ruirui Wang; Shuai Zuo; Yupeng Zhang (Journal of Environmental Chemical Engineering, 2024)

Effects of air frying on protein digestive properties in scallop (Patinopecten yessoensis) adductor muscles and the mechanisms involved - Zi-Ye Wang; Ying Luo; Rui Zheng; Shuo Lv; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

Enhanced separation flux and compressive strength for oil-water separation by adding sodium lignosulphonate - Hui Jiang; Jun Li; Chao Wu; Zi-wei Xiong; Jia-wei Ding; Hui-fen Su; Ya-hui Li; Wen-bo Luo; Liu-jie Yuan; Si-yi Lv; Lu-xiang Wang; De-qiang Li (Chemical Engineering Journal, 2024)

Structuring restricted amorphous molecular chains in the reinforced cellulose film by uniaxial stretching - Jing Wang; Shi-Peng Chen; De-Long Li; Lin Zhou; Jia-Xin Ren; Li-Chuan Jia; Gan-Ji Zhong; Hua-Dong Huang; Zhong-Ming Li (Carbohydrate Polymers, 2024)

TaMYB44-5A reduces drought tolerance by repressing transcription of TaRD22-3A in the abscisic acid signaling pathway - De Peng; Liqun Li; Aosong Wei; Ling Zhou; Bingxin Wang; Mingliu Liu; Yanhong Lei; Yanzhou Xie; Xuejun Li (Planta, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

Pollution characteristics, source apportionment and absorption spectra of size-resolved PAHs in atmospheric particles in a cold megacity of China - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Zi-Feng Zhang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Global climate change: Effects of future temperatures on emergency department visits for mental disorders in Beijing, China - Yan-Lin Niu; Feng Lu; Xue-Jiao Liu; Jun Wang; De Li Liu; Qi-Yong Liu; Jun Yang (Environmental Research, 2024)

Prenatal exposure to fenvalerate causes depressive-like behavior in adulthood by inhibiting brain-derived 5-HT synthesis - Hui-Min Zhu; Bo Wang; Tao Wang; Jing Shao; Hui-Ru Chen; Chi Zhang; Li-Hua Xu; Jing-Jing Li; Min Wang; De-Xiang Xu; Xiu-Hong Meng (Environmental Pollution, 2024)

m6A-methylated Lonp1 drives mitochondrial proteostasis stress to induce testicular pyroptosis upon environmental cadmium exposure - Kong-Wen Ouyang; Tian-Tian Wang; Hua Wang; Ye-Xin Luo; Yi-Fan Hu; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Yong-Wei Xiong; Jin Zhang; Wei Chang; Yu-Feng Zhang; et al. (Science of The Total Environment, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Superhydrophobic stretchable conductive composite textile with weft-knitted structure for excellent electromagnetic interference shielding and Joule heating performance - Tai-Bao Yang; Ji-You Zong; De-Zhuang Jia; Ling Xu; Yue-Yi Wang; Li-Chuan Jia; Ding-Xiang Yan; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2024)

Deep-injected straw incorporation enhances subsoil quality and wheat productivity - Jun Ling; Jie Zhou; Gong Wu; De-Qiang Zhao; Zhi-Tong Wang; Yuan Wen; Shun-Li Zhou (Plant and Soil, 2024)

Epidemiology, pathogenesis, immune evasion mechanism and vaccine development of porcine Deltacoronavirus - Xueting Shan; Rui Li; Xiang Ma; Guoqiang Qiu; Yi Xiang; Xiaojun Zhang; De Wu; Lu Wang; Jianhong Zhang; Tao Wang; Weifen Li; Yun Xiang; et al. (Functional & Integrative Genomics, 2024)

Hydrogen-bond tuned conjugated architectures for nitric oxide sensing in single-benzene framework: Advances and mechanistic insights - Feng-Zao Chen; Cun-Bin Du; Yi-Chao Wang; Jie Zhu; Ge Cheng; Kai-Bin Li; De-Man Han; Xiao-Yu Wu (Analytica Chimica Acta, 2024)

Berberine improves cognitive impairment by alleviating brain atrophy and promoting white matter reorganization in diabetic db/db mice: a magnetic resonance imaging-based study - Xin-yu Yang; Chun-jing Yang; Xiao-fang Wang; Lei Zhang; Zheng-yuan Shi; De-chun Jiang; Man-zhong Li (Metabolic Brain Disease, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

MitoQ protects against carbon tetrachloride-induced hepatocyte ferroptosis and acute liver injury by suppressing mtROS-mediated ACSL4 upregulation - Li Tao; Yu-Feng Xue; Fei-Fei Sun; Xue He; Hong-Qian Wang; Cheng-Cheng Tong; Cheng Zhang; De-Xiang Xu; Xi Chen (Toxicology and Applied Pharmacology, 2024)

Paraflavitalea pollutisoli sp. nov., Pollutibacter soli gen. nov. sp. nov., Polluticoccus soli gen. nov. sp. nov., and Terrimonas pollutisoli sp. nov., four new members of the family Chitinophagaceae from polluted soil - Ze-Shen Liu; Xiao-Kang Wang; Ke-Huan Wang; Mei-Ling Yang; De-Feng Li; Shuang-Jiang Liu (Systematic and Applied Microbiology, 2024)

Assessing territorial space conflicts in the coastal zone of Wenzhou, China: A land-sea interaction perspective - De Zhou; Xingyu Zhao; Pu Li; Fengzhi Jin; Siyuan Li; Huan Li; Junfeng Wang (Science of The Total Environment, 2024)

Modelling changes in vegetation productivity and carbon balance under future climate scenarios in southeastern Australia - Bin Wang; Benjamin Smith; Cathy Waters; Puyu Feng; De Li Liu (Science of The Total Environment, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Time series retrieval of Multi-wavelength Aerosol optical depth by adapting Transformer (TMAT) using Himawari-8 AHI data - Lu She; Zhengqiang Li; Gerrit de Leeuw; Weile Wang; Yujie Wang; Lu Yang; Zixian Feng; Chen Yang; Yun Shi (Remote Sensing of Environment, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

In-situ synthesis of MEMS compatible Al/Cu2HIO6/PVDF Metastable composites film with high combustion performance - De-Yun Tang; Chuanhao Xu; Heng Ding; Haifeng Yang; Xiaodong Li; Weimiao Wang; Rui Li; Zhiqiang Qiao; Guangcheng Yang (Chemical Engineering Journal, 2024)

Fabrication of Al@AIH@PVDF metastable composite film with enhanced laser ignition ability and combustion performance - De-Yun Tang; Heng Ding; Weimiao Wang; Xiaodong Li; Haifeng Yang; Rui Li; Zhiqiang Qiao; Guangcheng Yang (Chemical Engineering Journal, 2024)

Analysis of heavy metal and polycyclic aromatic hydrocarbon pollution characteristics of a typical metal rolling industrial site based on data mining - De’an Li; Yirong Deng; LiLi Liu; Jun Wang; Zaoquan Huang; Xiaolu Zhang (Environmental Geochemistry and Health, 2024)

Bowl effect of irreversible primary salinization driven by geology in Hetao irrigation area, China - Shuanhu Li; Chi Li; De Yao; Xiaorong Wang; Yu Gao (Science of The Total Environment, 2024)

A food-energy-water-carbon nexus framework informs region-specific optimal strategies for agricultural sustainability - Qinsi He; De Li Liu; Bin Wang; Zikui Wang; Annette Cowie; Aaron Simmons; Zhenci Xu; Linchao Li; Yu Shi; Ke Liu; Matthew Tom Harrison; Cathy Waters; et al. (Resources, Conservation and Recycling, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Variation of chalcophile elements in base metal sulfide minerals from the Jinchuan magmatic Ni–Cu sulfide deposit, NW China: Implications for mineral exploration - Long-Jiao Li; Xian-Cheng Mao; Zhan-Kun Liu; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Yun-Qi Wang (Journal of Geochemical Exploration, 2024)

Deciphering the genetic relationship between W and Au in a W-Au co-mineralized system: Trace elements of pyrite and sulfur isotopes of sulfides from the Yangwuchang W-Au deposit, North Qinling, China - Jize Li; Jiajun Liu; Jeffrey de Fourestier; Degao Zhai; Di Hao; Zhanlin Ge; Fangfang Zhang; Yinhong Wang; Jianping Wang (Journal of Asian Earth Sciences, 2024)

PM2.5 induces a senescent state in mouse AT2 cells - Peiyong Cheng; Yongqi Chen; Jianhai Wang; Ziyu Han; De Hao; Yu Li; Feifei Feng; Xuexin Duan; Huaiyong Chen (Environmental Pollution, 2024)

Effect of beta-cypermethrin on the reproductive capacity of female mice in advanced age - Qian-Feng Qiao; Li-Qing Wang; De-E. Yu; Na Li; Qiong-Jun Xu; Yong-Jiang Zhou (Environmental Toxicology and Pharmacology, 2024)

A recipe for making potassium-rich magmas in collisional orogens: New insights from K and Fe isotopes - De-Hong Du; Xiang-Long Luo; Xiao-Lei Wang; Martin R. Palmer; E.Yalçın Ersoy; Weiqiang Li (Earth and Planetary Science Letters, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Impact of ecological migration village construction on vector mosquito and mosquito-borne disease in the southern Yunnan Province, China - Mei-De Liu; Chun-Xiao Li; Xue-Zhong Wang; Yan-De Dong; Tong-Yan Zhao (International Journal of Tropical Insect Science, 2024)
To evaluate the influence of ecological migration village construction on mosquito vector populations and mosquito-borne diseases in southern Yunnan Province. Two vicinal villages in Mengla County, the southern part of Yunnan Province, a native village, and a newly built village, were selected as study sites. Malaria and Japanese Encephalitis vector mosquito population divergence between the two villages were studied. Malaria and Japanese Encephalitis (JE) cases in the two villages were also compared. Anopheles minimus was the dominant population in houses in the newly built village, and An . jeyporiensis dominated the native village. Accordingly, there were nine malaria cases in the new village compared with zero cases in the native village. Culex tritaeniorhynchus , the chief JE vector in the study area, displayed no difference between the two villages; however, there was a higher density of the local secondary JE vector ( Cx. pseudovishnui ) in the native village than in the new one. The JE cases in the villages corresponded to zero. From the vector-borne disease perspective, our results suggest that local community should pay more attention to malaria and An . minimus during the construction of an ecological migration village in the new Chinese Western Developing Plan (CWDP) in southern Yunnan Province.

An ensemble framework-based approach for modeling stability of expansive soil slopes: fusion of machine learning algorithms and protection structure disease data - Chao Li; Lei Wang; De’an Sun; Yang Chen (Environmental Science and Pollution Research, 2024)

Influence of calcium concentration on the re-assembly of sodium caseinate into casein micelles and on their renneting behavior - Teng Wang; Yadong Li; Fien De Witte; Ferre Rebry; Hao Li; Pieter Vermeir; Koen Dewettinck; Paul Van der Meeren (Food Research International, 2024)

Impact of plastic mulching and residue return on maize yield and soil organic carbon storage in irrigated dryland areas under climate change - Hao Quan; Bin Wang; Lihong Wu; Hao Feng; Lina Wu; Lianhai Wu; De Li Liu; Kadambot H.M. Siddique (Agriculture, Ecosystems & Environment, 2024)

Compositional changes with incremental growth of the Quxu granite batholith, southern Tibet: Evidence from geochronology and geochemistry - Ying-Ze Zhang; Xiao-Lei Wang; Yue Guan; Xiu-Mian Hu; Jun-Yong Li; De-Hong Du; Di Wang (Lithos, 2024)

Insights into the long-term immobilization performances and mechanisms of CMC-Fe0/FeS with different sulfur sources for uranium under anoxic and oxic aging - Qi Fang; Yanling Tan; Ran Yan; De Zhang; Mi Li; Xiaoyan Wu; Yilong Hua; Wenjing Xue; Rongzhong Wang (Journal of Environmental Management, 2024)

Covalently linked MOF@COF direct Z-scheme heterojunction for visible light-driven photocatalytic degradation of flotation agents - Hong-Xia Zhang; Sheng-Hua Ma; Hai-Xian Wang; Shao-Cong Li; Hai-Yun Shen; De-Ming Kong; Feng-Ying Wang; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Hydrothermal synthesis of lanthanum oxide nanoparticles modified pumice: High lanthanum oxide loading ratio and efficiency phosphate removal - Yi-Fan Xiao; Yong Zhang; De-Cai Wang; Yu-Ming Su; Jing Wu; Jia-Qi Liu; Li-Li Yang; Zhen Jin (Journal of Environmental Chemical Engineering, 2024)

Tracing magmatic differentiation of peralkaline granites by using K stable isotopes - Hang Xu; Weiqiang Li; Xiao-Lei Wang; Jun Mu; De-Hong Du; Jiao-Long Zhao; Ding-Yi Xiong (Geochimica et Cosmochimica Acta, 2024)

Di-(2-ethylhexyl) phthalate exacerbates abnormalities of testicular development in F1 males via inhibition the Wnt/β-catenin signaling pathway - Nan Li; De-Ming Sun; Yong-Zhang Chang; Xue-Nan Li; Jin-Long Li; Tian-Qi Wang (Environmental Pollution, 2024)

Can agronomic options alleviate the risk of compound drought-heat events during the wheat flowering period in southeastern Australia? - Siyi Li; Bin Wang; De Li Liu; Chao Chen; Puyu Feng; Mingxia Huang; Xiaofang Wang; Lijie Shi; Cathy Waters; Alfredo Huete; Qiang Yu (European Journal of Agronomy, 2024)

Chemical constituents from the whole plant of Odontites vulgaris Moench and their chemotaxonomic significance - Yanan Liu; Tieqiang Zong; Mengjie Wang; De Yang; Jinfeng Sun; Wei Zhou; Gao Li (Biochemical Systematics and Ecology, 2024)

Feeding Broiler Chicks with Bacillus subtilis, Clostridium butyricum, and Enterococcus faecalis Mixture Improves Growth Performance and Regulates Cecal Microbiota - De Xin Dang; Qiangqiang Zou; Yunhe Xu; Yan Cui; Xu Li; Yingying Xiao; Tieliang Wang; Desheng Li (Probiotics and Antimicrobial Proteins, 2024)

Stability of the Stratification of Water Bodies in the North Passage of the Yangtze River Estuary Based on the EFDC Model - De’an Wu; Xin Li; Yigang Wang (Journal of Ocean University of China, 2024)

Insight into the flame-retardant mechanism of different organic-modified layered double hydroxide for epoxy resin - Xiao-Hui Shi; Xue-Lin Li; Hong Shi; Qing-Yun Liu; Wei-Min Xie; Shi-Jie Wu; Nan Zhao; De-Yi Wang (Applied Clay Science, 2024)

Four pairs of tautomers from rhizomes of Acorus calamus and fruits of Cornus officinalis - Zhi-You Hao; Meng Yang; Yan Wang; Yan-Fei Liu; Shi-Qi Zhou; Meng Li; Yan-Gang Cao; Xiao-Ke Zheng; Wei-Sheng Feng; De-Quan Yu (Natural Product Research, 2024)

7-Methoxy-13-dehydroxypaxilline: New indole diterpenoid from an endophytic fungus Penicillium sp. Nb 19 - Jing Yu; Jia-Peng Wang; Shi-Fang Liu; Cui-Yun Yin; De-Ying Tang; Yi-Hang Li; Li-Xia Zhang (Natural Product Research, 2024)

Two new anthraquinone derivatives from Saprosma crassipes H. S. Lo - Xin-Shu Ji; De-Cai Dai; Yi-Tong Wang; Jing-Yi Cui; Hai-Xiang Li; Xin-Ming Song; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

FUNDC1-mediated mitophagy triggered by mitochondrial ROS is partially involved in 1-nitropyrene-evoked placental progesterone synthesis inhibition and intrauterine growth retardation in mice - Jian Li; Xin Dong; Jia-Yu Liu; Lan Gao; Wei-Wei Zhang; Yi-Chao Huang; Yan Wang; Hua Wang; Wei Wei; De-Xiang Xu (Science of The Total Environment, 2024)

Dichapetalin-type triterpenoids from Dichapetalum longipetalum and their anti-inflammatory activity - Dong-Li Zhang; Yue Wang; Jing-Bo Liu; Qian Chen; Shao-Yong Li; De-Jun Jin; Sheng-An Tang (Phytochemistry, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Floating photovoltaic systems homogenize the waterbird communities across subsidence wetlands in the North China Plain - Xiangrong Song; Tengteng Liu; Guangyao Wang; Yong Zhang; Chunlin Li; de Boer Willem F (Journal of Environmental Management, 2024)

Effects of hydroxy methionine zinc on growth performance, immune response, antioxidant capacity, and intestinal microbiota of red claw crayfish (Procambarus clarkii) - De-Hua Kong; Yu-Xiang Ji; Bao-Yuan Zhang; Kuo-Chen Li; Zi-Yan Liao; Hao Wang; Jing-Xiang Zhou; Qiu-Ju Wang (Fish & Shellfish Immunology, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

FTase inhibitors and cancer: prospects for use in targeted therapies - Ming-tao Xia; Ling Yu; Zhi-wei Yan; You-de Wang; Li-ying Zhang; Guang-xin Miao; Shuai Li (Medicinal Chemistry Research, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Establishment of a tilapia lake virus (TiLV)-susceptible cell line for anti-TiLV Chinese herbal compound screening - Song Zhu; Bo Miao; Yu-Zhou Zhang; Qin Yang; Xun-Teng Deng; Li-Hong Gao; Ji-Shu Zheng; De-Cheng Pu; De-Shou Wang; Sheng-Qi Su (Aquaculture, 2023)

Surveillance of COVID-19 and influenza A(H1N1) prevalence in China via medicine-based wastewater biomarkers - Xue-Ting Shao; Yan-Song Wang; Zhen-Fang Gong; Yan-Ying Li; Dong-Qin Tan; Jian-Guo Lin; Wei Pei; De-Gao Wang (Water Research, 2023)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Electrosorption of uranium (VI) by sulfonic acid‑decorated FeOOH nanorods - Ranran Jiao; Zheng Chen; Suyuan Zeng; De Wang; Jiaxing Li (Journal of Environmental Chemical Engineering, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Coupling strength between omnivory loops and their one-species-delete subloops drives real food web stability - Jianfeng Feng; Shengpeng Li; Xiaoxiao Li; Yueming Jiang; Ruyue Wang; Xianhao Meng; Wei Yang; Tao Sun; Peter C. de Ruiter; Yongtang Shi; Nils Chr. Stenseth (Theoretical Ecology, 2023)

Prioritizing agronomic practices and uncertainty assessment under climate change for winter wheat in the loess plateau, China - Tengcong Jiang; Bin Wang; Xiaoning Duan; De Li Liu; Jianqiang He; Liang He; Ning Jin; Hao Feng; Qiang Yu (Agricultural Systems, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Integration of alligator cathelicidin gene via two CRISPR/Cas9-assisted systems enhances bacterial resistance in blue catfish, Ictalurus furcatus - Jinhai Wang; Baofeng Su; Jacob Al-Armanazi; Allison L. Wise; Mei Shang; Logan Bern; Shangjia Li; De Xing; Andrew Johnson; Wenwen Wang; Darshika U. Hettiarachchi; Michael Coogan; et al. (Aquaculture, 2023)

Supervised machine learning improves general applicability of eDNA metabarcoding for reservoir health monitoring - Huan Hu; Xing-Yi Wei; Li Liu; Yuan-Bo Wang; Huang-Jie Jia; Ling-Kang Bu; De-Sheng Pei (Water Research, 2023)

Study on controllable preparation of high performance andradite based glass-ceramics by harmful iron-rich waste slag - Xiaomin Liu; Yufeng Wu; De'an Pan; Bin Li; Wei Wang (Science of The Total Environment, 2023)

Field-scale assessment of direct and indirect effects of soil texture on organic matter mineralization during a dry summer - Haichao Li; Astrid Françoys; Xiaolin Wang; Shengmin Zhang; Orly Mendoza; Stefaan De Neve; Kevin Dewitte; Steven Sleutel (Science of The Total Environment, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Phosphate-functionalized magnetic calcium alginate for the engineering remediation of uranium-contaminated water and soil - De Wang; Jianfeng Zhang; Jiaxing Li (Chemical Engineering Journal, 2023)

Microbiome predators in changing soils - Shunran Hu; Guixin Li; Alejandro Berlinches de Gea; Joliese Teunissen; Stefan Geisen; Rutger A. Wilschut; Arne Schwelm; Yuxin Wang (Environmental Microbiology, 2023)
Microbiome predators shape the soil microbiome and thereby soil functions. However, this knowledge has been obtained from small‐scale observations in fundamental rather than applied settings and has focused on a few species under ambient conditions. Therefore, there are several unaddressed questions on soil microbiome predators: (1) What is the role of microbiome predators in soil functioning? (2) How does global change affect microbiome predators and their functions? (3) How can microbiome predators be applied in agriculture? We show that there is sufficient evidence for the vital role of microbiome predators in soils and stress that global changes impact their functions, something that urgently needs to be addressed to better understand soil functioning as a whole. We are convinced that there is a potential for the application of microbiome predators in agricultural settings, as they may help to sustainably increase plant growth. Therefore, we plea for more applied research on microbiome predators.

Preparation of basic magnesium carbonate nanosheets modified pumice and its adsorption of heavy metals - Yong Zhang; Yi-Fan Xiao; Guang-Song Xu; Min-Da Xu; De-Cai Wang; Zhen Jin; Jia-Qi Liu; Li-Li Yang (Environmental Science and Pollution Research, 2023)

CRISPR/Cas9 microinjection of transgenic embryos enhances the dual-gene integration efficiency of antimicrobial peptide genes for bacterial resistance in channel catfish, Ictalurus punctatus - Jinhai Wang; Baofeng Su; Timothy J. Bruce; Allison L. Wise; Peng Zeng; Guanqun Cao; Rhoda Mae C. Simora; Logan Bern; Mei Shang; Shangjia Li; De Xing; Wenwen Wang; et al. (Aquaculture, 2023)

Assessment of 9 km SMAP soil moisture: Evidence of narrowing the gap between satellite retrievals and model-based reanalysis - Zanpin Xing; Xiaojun Li; Lei Fan; Andreas Colliander; Frédéric Frappart; Patricia de Rosnay; Roberto Fernandez-Moran; Xiangzhuo Liu; Huan Wang; Lin Zhao; Jean-Pierre Wigneron (Remote Sensing of Environment, 2023)

Short-term PM2.5 exposure induces transient lung injury and repair - Yu Li; Bencheng Lin; De Hao; Zhongchao Du; Qi Wang; Zhaoyu Song; Xue Li; Kuan Li; Jianhai Wang; Qiuyang Zhang; Junping Wu; Zhuge Xi; et al. (Journal of Hazardous Materials, 2023)

Attenuation effects of ZVI/PDS pretreatment on propagation of antibiotic resistance genes in bioreactors: Driven by antibiotic residues and sulfate assimilation - Qi Zhao; Qing-Lian Wu; Hua-Zhe Wang; Qi-Shi Si; Lu-Shi Sun; De-Nian Li; Nan-Qi Ren; Wan-Qian Guo (Journal of Hazardous Materials, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Fabrication of organic P-N aerogel towards simultaneously super thermal insulation, enhanced compressive strength, flame retardancy and smoke suppression for the rigid polyurethane foam - Ying-Ming Li; Wen-Juan Hu; Shuang-Lin Hu; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2023)

Optimizing Mo-C coordination for enhanced low-temperature water-gas shift activity over α-MoC1-x catalysts: An experimental and theoretical study - Ruiying Li; Xiuhui Zheng; Fei Wang; Hao Yan; Xin Zhou; Yongxiao Tuo; Yibin Liu; Xiang Feng; Xiaobo Chen; De Chen; Chaohe Yang (Chemical Engineering Journal, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Effects of water supply on plant stoichiometry of C, N, P in Inner Mongolia grasslands - Yongjie Liu; Guoe Li; Mingxia Wang; Chunyan Ma; Hans J. De Boeck; Fujiang Hou; Zhenqing Li (Plant and Soil, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Association of air pollutants and meteorological factors with tuberculosis: a national multicenter ecological study in China - Qian Wang; Yan-lin Li; Ya-ling Yin; Bin Hu; Chong-chong Yu; Zhen-de Wang; Yu-hong Li; Chun-jie Xu; Yong-bin Wang (International Journal of Biometeorology, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Loss of Atg5 in Sertoli cells enhances the susceptibility of cadmium-impaired testicular spermatogenesis in mice - Yong-Wei Xiong; Dai-Xin Li; Zheng-Jia Ling; Lu-Lu Tan; Yu-Feng Zhang; Jin Zhang; Hao Li; Wei Chang; Hua-Long Zhu; Jun Zhang; Lan Gao; De-Xiang Xu; et al. (Food and Chemical Toxicology, 2023)

Integrating machine learning and environmental variables to constrain uncertainty in crop yield change projections under climate change - Linchao Li; Yan Zhang; Bin Wang; Puyu Feng; Qinsi He; Yu Shi; Ke Liu; Matthew Tom Harrison; De Li Liu; Ning Yao; Yi Li; Jianqiang He; et al. (European Journal of Agronomy, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Current status of the biological control of the fall armyworm Spodoptera frugiperda by egg parasitoids - Tian-Hao Li; Adeney de Freitas Bueno; Nicolas Desneux; Lisheng Zhang; Zhenying Wang; Hui Dong; Su Wang; Lian-Sheng Zang (Journal of Pest Science, 2023)

Modelling interactions between cowpea cover crops and residue retention in Australian dryland cropping systems under climate change - Qinsi He; De Li Liu; Bin Wang; Annette Cowie; Aaron Simmons; Cathy Waters; Linchao Li; Puyu Feng; Yi Li; Peter de Voil; Alfredo Huete; Qiang Yu (Agriculture, Ecosystems & Environment, 2023)

CNN-based automated trace editing method using Hough transform - Yang Shen; Xiao-lin Hu; Tong-dong Wang; Jia-jia Cui; Si-hao Tao; Ao Li; Qiang Lu; De-zhi Zhang; Wei-guo Xiao (Applied Geophysics, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Reduction of PSII photosynthetic performance by low temperature is the reason for the growing inhibition of Kobresia pygmaea Clarke - Shengbo Shi; Rui Shi; Dangwei Zhou; Tiancai Li; Kejia De; Xiuzhen Gao; Jialin Ma; Fanglin Wang (Brazilian Journal of Botany, 2023)
Kobresia pygmaea Clarke is mainly distributed in the alpine region from 3800 to 4500 m elevation on the Qinghai-Tibet Plateau. It is excellent in low-temperature tolerance and trampling resistance and plays an important role in maintaining the stability of regional ecological environments. Mainly based on the chlorophyll fluorescence imaging technique, using grass sods blocks with a size of 20 × 20 cm 2 collected from K. pygmaea forb meadow, simulated a low-temperature treatment in cultural room with 8 °C/4 °C (day/night) at diurnal photoperiod, we analyzed the effects of low temperature on PSII photochemical efficiency and non-photochemical quenching, as well as the interaction between low temperature and light intensity. The results showed that low temperature could significantly decrease the maximum quantum efficiency of PSII photochemistry ( F v / F m ) and inhibit the leaf growth of K. pygmaea . The light response curve of PSII relative linear electron transport rate was reduced by low temperature, while it recovered to almost normal level after two days of removing adversity. Further experiments under steady-state actinic light confirmed that light intensity was the main factor affecting the PSII photochemical efficiency, and its reduction caused by the low temperature showed a certain degree of reversibility. The non-photochemical quenching (NPQ) was significantly affected by light intensity, and its fast and slow components (NPQ f and NPQ s ) in NPQ accounted for 36% and 64% of NPQ, respectively. The decrease in NPQ f and corresponding increase in NPQ s slowly recovered after relieving from low-temperature condition. The relative inhibition of photosynthesis ( P inh ) was significantly enhanced by low temperature and reduced after removal of adversity. Strong light intensity could intensify the adverse effect of low temperature on PSII operating efficiency F q ′/ F m ′ and efficiency factor F q ′/ F v ′, as well as NPQ. In conclusion, low temperature was one of the main reasons limiting the photosynthetic performance of K. pygmaea on the Qinghai-Tibet Plateau and could aggravate photosynthetic photoinhibition. The adversity of low temperature frequently occurring in the plant growing season on the Qinghai-Tibet Plateau was constituted of the main factor of the low productivity level in alpine meadow.

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Contrasting effects of different light regimes on the photoreactivities of allochthonous and autochthonous chromophoric dissolved organic matter - Wen-Zhuo Zhu; Shu-Heng Wang; De-Zhong Wang; Wei-Hua Feng; Bo Li; Hong-Hai Zhang (Chemosphere, 2023)

Effects of thermal treatments on the extraction and in vitro fermentation patterns of pectins from pomelo (Citrus grandis) - Yuxin Wang; Jiaxin Liu; Li chen; Shuang Jin; Can An; Long Chen; Bao Yang; Henk A. Schols; Paul de Vos; Weibin Bai; Lingmin Tian (Food Hydrocolloids, 2023)

Influence of deflector on the impact dynamics of debris flow against rigid barrier - C.W.W. Ng; Z. Li; Y.D. Wang; H. Liu; S. Poudyal; W.A.R.K. De Silva (Engineering Geology, 2023)

Structural classification of EZH2 inhibitors and prospects for the treatment of tumor: a review - Ling Yu; Ming-tao Xia; You-de Wang; Zhi-wei Yan; Li-ying Zhang; Shuai Li (Medicinal Chemistry Research, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

CRISPR/Cas9-mediated knock-in of masu salmon (Oncorhyncus masou) elongase gene in the melanocortin-4 (mc4r) coding region of channel catfish (Ictalurus punctatus) genome - Michael Coogan; De Xing; Baofeng Su; Veronica Alston; Andrew Johnson; Mohd Khan; Karim Khalil; Ahmed Elaswad; Shangjia Li; Jinhai Wang; Cuiyu Lu; Wenwen Wang; et al. (Transgenic Research, 2023)

A global lithospheric magnetic field model between ± 65° latitude derived from CSES satellite scalar data - Jie Wang; Xuhui Shen; Yanyan Yang; Zhima Zeren; Bin Zhou; Magnes Werner; Angelo De Santis; Jianping Huang; Changli Yao; Zelin Li; Yuanman Zheng; Shufan Zhao; et al. (Physics of the Earth and Planetary Interiors, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Chemoreceptors from the commensal gut Roseburia rectibacter bind to mucin and trigger chemotaxis - Hong‐He Chen; Yu‐Xin Wang; De‐Feng Li; Chang Liu; Shuang‐Yu Bi; Cheng‐Ying Jiang; Shuang‐Jiang Liu (Environmental Microbiology, 2023)
Chemotaxis is crucial for bacterial adherence and colonization of the host gastrointestinal tract. Previous studies have demonstrated that chemotaxis affects the virulence of causative pathogens and the infection in the host. However, the chemotactic abilities of non‐pathogenic and commensal gut bacteria have rarely been explored. We observed that Roseburia rectibacter NSJ‐69 exhibited flagella‐dependent motility and chemotaxis to a variety of molecules, including mucin and propionate. A genome‐wide analysis revealed that NSJ‐69 has 28 putative chemoreceptors, 15 of which have periplasmic ligand‐binding domains (LBDs). These LBD‐coding genes were chemically synthesized and expressed heterologously in Escherichia coli . Intensive screening of ligands revealed four chemoreceptors bound to mucin and two bound to propionate. When expressed in Comamonas testosteroni or E. coli , these chemoreceptors elicited chemotaxis toward mucin and propionate. Hybrid chemoreceptors were constructed, and results showed that the chemotactic responses to mucin and propionate were dependent on the LBDs of R. rectibacter chemoreceptors. Our study identified and characterized R. rectibacter chemoreceptors. These results will facilitate further investigations on the involvement of microbial chemotaxis in host colonization.

Maximizing colonization and proliferation of blue catfish (Ictalurus furcatus) donor stem cells for the creation of xenogenic catfish: Identifying the best host age of triploid channel catfish (I. punctatus) - Darshika Udari Hettiarachchi; Veronica N. Alston; Logan Bern; Baofeng Su; Mei Shang; Jinhai Wang; De Xing; Shangjia Li; Matthew K. Litvak; Rex A. Dunham; Ian A.E. Butts (Aquaculture, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Preparation of Fe2O3 porous microspheres modified pumice and its adsorption performance on phosphate removal - Yong Zhang; Yi-Fan Xiao; Guang-Song Xu; De-Cai Wang; Jie Li; Jian Huang; Zhen Jin (Journal of Environmental Chemical Engineering, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Effect of gradual increase and decrease in temperature on innate, cellular and humoral immunity in striped hamsters - De-Li Xu; Yuhui Wang (Mammalian Biology, 2023)

Inoculation with Rhizophagus intraradices Confers Drought Stress Tolerance in Oat by Improving Nitrogen and Phosphorus Nutrition - Bin Zhang; Yu-Feng Lv; Yue Li; Li Li; Ju-Qing Jia; Mei-Chen Feng; Chao Wang; Xiao-Yan Song; Wu-De Yang; Fahad Shafiq; Mei-Jun Zhang (Journal of Soil Science and Plant Nutrition, 2023)

In Silico Genome-Wide Mining and Analysis of Terpene Synthase Gene Family in Hevea Brasiliensis - Jiahao Liang; De Wang; Xin Li; Weiwen Huang; Chun Xie; Minghui Fu; Hongmei Zhang; Qiong Meng (Biochemical Genetics, 2023)

Dietary aromatase inhibitor treatment converts XY gsdf homozygous mutants to sub-fertile male in Nile tilapia (Oreochromis niloticus) - Sen Fan; Hong-Juan Shi; You-Xing Peng; Yuan-Qing Huang; Mou-Yan Jiang; Guang-Li Li; De-Shou Wang; Dong-Neng Jiang (Aquaculture, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Shock-induced potassium and zinc isotope fractionation in ordinary chondrites and its implications - Ying-Kui Xu; Zhi Li; Shi-Jie Li; Ze-Zhou Wang; De-Liang Wang; Yan Fan; Xiong-Yao Li; Jian-Zhong Liu; Dan Zhu (Geochimica et Cosmochimica Acta, 2023)

Improving flavor, bioactivity, and changing metabolic profiles of goji juice by selected lactic acid bacteria fermentation - Wenhui Duan; Qijie Guan; Hui-Ling Zhang; Fang-Zhou Wang; Ran Lu; De-Mao Li; Yan Geng; Zheng-Hong Xu (Food Chemistry, 2023)

Conjugated microporous polyimide cathodes for sodium/lithium-ion batteries with ultra-long cycling performance - Lei Chen; Yuke Li; Xuefan Wang; Juncheng Wu; Yijiao Ding; Shi-Bin Ren; Li Zhang; Zhenwei Xu; Bingwei Chen; De-Man Han; Ying-peng Wu (Chemical Engineering Journal, 2023)

The electrosorption of uranium (VI) onto the modified porous biocarbon with ammonia low-temperature plasma: Kinetics and mechanism - De Wang; Jian Zhou; Yingzi Zhang; Jianfeng Zhang; Jiawei Liang; Jiahao Zhang; Jiaxing Li (Chemical Engineering Journal, 2023)

Mitoquinone protects against acetaminophen-induced liver injury in an FSP1-dependent and GPX4-independent manner - Xue He; Shi-Min Liang; Hong-Qian Wang; Li Tao; Fei-Fei Sun; Yan Wang; Cheng Zhang; Yi-Chao Huang; De-Xiang Xu; Xi Chen (Toxicology and Applied Pharmacology, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Effect of air frying and baking on physicochemical properties and digestive properties of scallop (Patinopecten yessoensis) adductor muscle - Zi-Ye Wang; Zi-Xuan Wu; Guan-Hua Zhao; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Electrodeposition cobalt sulfide nanosheet on laser-induced graphene as capacitive deionization electrodes for uranium adsorption - Ruya Cao; Jianfeng Zhang; De Wang; Fuwei Sun; Nian Li; Jiaxing Li (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

High efficiency NOx synthesis and regulation using dielectric barrier discharge in the needle array packed bed reactor - Yao Li; Liang Qin; Hong-Li Wang; Si-Si Li; Hao Yuan; De-Zheng Yang (Chemical Engineering Journal, 2023)

Exposure to acute waterborne cadmium caused severe damage on lipid metabolism of freshwater fish, revealed by nuclear lipid droplet deposition in hepatocytes of rare minnow - Xiao-Hong Liu; Xu Pang; Li Jin; De-Yong Pu; Zhi-Jian Wang; Yao-Guang Zhang (Aquatic Toxicology, 2023)

Ultrasensitive fluorescence detection of multiple DNA methyltransferases based on DNA walkers and hyperbranched rolling circle amplification - Siqi Zhang; Huahao Shao; Kai-Bin Li; Wei Shi; Yichao Wang; De-Man Han; Jinggang Mo (Analytica Chimica Acta, 2023)

CRISPR/Cas9-mediated precision integration of fat-1 and fat-2 from Caenorhabditis elegans at long repeated sequence in channel catfish (Ictalurus punctatus) and the impact on n-3 fatty acid level - De Xing; Mei Shang; Shangjia Li; Wenwen Wang; Tasnuba Hasin; Darshika Hettiarachchi; Veronica Alston; Logan Bern; Zhenkui Qin; Baofeng Su; Rex Dunham (Aquaculture, 2023)

Cascading effects of Pb on the environmental and symbiotic microbiota and tadpoles' physiology based on field data and laboratory validation - Wei Zhu; Yan Lv; Qun-De Zhang; Li-Ming Chang; Qi-Heng Chen; Bin Wang; Jian-Ping Jiang (Science of The Total Environment, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Manipulating the severe shoot topping delays the harvest date and modifies the flavor composition of Cabernet Sauvignon wines in a semi-arid climate - Hao-Cheng Lu; Li Hu; Yao Liu; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Porcine endogenous retrovirus: classification, molecular structure, regulation, function, and potential risk in xenotransplantation - Yu Liu; Yifan Niu; Xiang Ma; Yun Xiang; De Wu; Weifen Li; Tao Wang; Dong Niu (Functional & Integrative Genomics, 2023)

Identification and pathogenetic study of tilapia lake virus (TiLV) isolated from naturally diseased tilapia - Tao He; Yu-Zhou Zhang; Li-Hong Gao; Bo Miao; Ji-Shu Zheng; De-Cheng Pu; Qing-Qing Zhang; Wei-Wei Zeng; De-Shou Wang; Sheng-Qi Su; Song Zhu (Aquaculture, 2023)

Bacterial resistance to antibacterial agents: Mechanisms, control strategies, and implications for global health - Ting Li; Zhenlong Wang; Jianhua Guo; Cesar de la Fuente-Nunez; Jinquan Wang; Bing Han; Hui Tao; Jie Liu; Xiumin Wang (Science of The Total Environment, 2023)

Size-resolved environmentally persistent free radicals in cold region atmosphere: Implications for inhalation exposure risk - Shi-Ming Jia; De-Qi Wang; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma (Journal of Hazardous Materials, 2023)

Behaviour of double-corrugated steel plates under cyclic in-plane shear loading: An experimental study - Ran Deng; Jun-De Yang; Yuan Gao; Yu-Hang Wang; Qi-Qi Li (Engineering Structures, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Impact of climate change and planting date shifts on growth and yields of double cropping rice in southeastern China in future - Ziya Zhang; Yi Li; Xinguo Chen; Yanzi Wang; Ben Niu; De Li Liu; Jianqiang He; Bakhtiyor Pulatov; Ishtiaq Hassan; Qingtao Meng (Agricultural Systems, 2023)

H3K4me3 as a target of di(2-ethylhexyl) phthalate (DEHP) impairing primordial follicle assembly - Ming-Hao Li; Jun-Jie Wang; Yan-Qin Feng; Xuan Liu; Zi-Hui Yan; Xiao-Jun Zhang; Ya-Xin Wen; Hao-Wei Luo; Lan Li; Massimo De Felici; Ai-Hong Zhao; Wei Shen (Chemosphere, 2023)

CFD modeling of traffic tidal flow: Assessment of pollutant dispersion - Zhengtong Li; Tingzhen Ming; Tianhao Shi; Hao Zhang; Chih-Yung Wen; Yongjia Wu; Caixia Wang; Kui Yin; Renaud de Richter; Wei Li (Urban Climate, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Occurrence and distribution of microplastics in coastal plain soils under three land-use types - De Bi; Beibei Wang; Zhu Li; Yabing Zhang; Xin Ke; Chengwang Huang; Wuxing Liu; Yongming Luo; Peter Christie; Longhua Wu (Science of The Total Environment, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

High-performance flame-retardant aliphatic polyamide via enhanced chain entanglement - Min Jiang; Bo-Wen Liu; Feng-Ming He; Qin Zhang; Ao Wang; De-Ming Guo; Hai-Bo Zhao; Li Chen; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Improving capacitive deionization performance by using O2 plasma modified carbon black - Ruya Cao; Jian Zhou; De Wang; Jianfeng Zhang; Yingzi Zhang; Hongjian Zhou; Jiaxing Li (Chemical Engineering Journal, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Abietane diterpenoids with neuroprotective activities from Phlegmariurus carinatus - Yang Liu; Qiang Wang; Dong-Kun Zheng; De Zhang; Zhen Xie; Jia-Wei Hu; Xin-Hua Xie; Jing Li; Shu-Ping Jiang (Natural Product Research, 2022)

Fine-mapping and candidate gene analysis of qFL-c10-1 controlling fiber length in upland cotton (Gossypium hirsutum L.) - Ruiting Zhang; Chao Shen; De Zhu; Yu Le; Nian Wang; Yuanxue Li; Xianlong Zhang; Zhongxu Lin (Theoretical and Applied Genetics, 2022)

Scaling-up and proteomic analysis reveals photosynthetic and metabolic insights toward prolonged H2 photoproduction in Chlamydomonas hpm91 mutant lacking proton gradient regulation 5 (PGR5) - Peng Liu; De-Min Ye; Mei Chen; Jin Zhang; Xia-He Huang; Li-Li Shen; Ke-Ke Xia; Xiao-Jing Xu; Yong-Chao Xu; Ya-Long Guo; Ying-Chun Wang; Fang Huang (Photosynthesis Research, 2022)
Clean and sustainable H 2 production is crucial to a carbon–neutral world. H 2 generation by Chlamydomonas reinhardtii is an attractive approach for solar-H 2 from H 2 O. However, it is currently not large-scalable because of lacking desirable strains with both optimal H 2 productivity and sufficient knowledge of underlying molecular mechanism. We hereby carried out extensive and in-depth investigations of H 2 photoproduction of hpm91 mutant lacking PGR5 (Proton Gradient Regulation 5) toward its up-scaling and fundamental mechanism issues. We show that hpm91 is at least 100-fold scalable (up to 10 L) with continuous H 2 collection of 7287 ml H 2 /10L-HPBR in averagely 26 days under sulfur deprivation. Also, we show that hpm91 is robust and active during sustained H 2 photoproduction, most likely due to decreased intracellular ROS relative to wild type. Moreover, we obtained quantitative proteomic profiles of wild type and hpm91 at four representing time points of H 2 evolution, leading to 2229 and 1350 differentially expressed proteins, respectively. Compared to wild type, major proteome alterations of hpm91 include not only core subunits of photosystems and those related to anti-oxidative responses but also essential proteins in photosynthetic antenna, C/N metabolic balance, and sulfur assimilation toward both cysteine biosynthesis and sulfation of metabolites during sulfur-deprived H 2 production. These results reveal not only new insights of cellular and molecular basis of enhanced H 2 production in hpm91 but also provide additional candidate gene targets and modules for further genetic modifications and/or in artificial photosynthesis mimics toward basic and applied research aiming at advancing solar-H 2 technology.

Characteristic pollutants risk assessment of modified manganese residue utilization in sintered product - Chao-qiang Wang; Ke Liu; De-ming Huang; Qi-cong Huang; Pei-xin Wang; Xu-dong Mei; Shu-chun Li (Environmental Science and Pollution Research, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

CAF-derived midkine promotes EMT and cisplatin resistance by upregulating lncRNA ST7-AS1 in gastric cancer - Ke-Da Yang; Ying Wang; Fan Zhang; Qing-Ling Li; Bai-Hua Luo; De-Yun Feng; Zhi-Jun Zeng (Molecular and Cellular Biochemistry, 2022)

Improved Growth and High Inheritance of Melanocortin-4 Receptor (mc4r) Mutation in CRISPR/Cas-9 Gene-Edited Channel Catfish, Ictalurus punctatus - Michael Coogan; Veronica Alston; Baofeng Su; Karim Khalil; Ahmed Elaswad; Mohd Khan; Andrew Johnson; De Xing; Shangjia Li; Jinhai Wang; Rhoda M. C. Simora; Cuiyu Lu; et al. (Marine Biotechnology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Correction to: New cretaceous fossil mantispids highlight the palaeodiversity of the extinct subfamily Doratomantispinae (Neuroptera: Mantispidae) - Hongyu Li; De Zhuo; Leran Cao; Bo Wang; George Poinar; Michael Ohl; Xingyue Liu (Organisms Diversity & Evolution, 2022)

New Cretaceous fossil mantispids highlight the palaeodiversity of the extinct subfamily Doratomantispinae (Neuroptera: Mantispidae) - Hongyu Li; De Zhuo; Leran Cao; Bo Wang; George Poinar; Michael Ohl; Xingyue Liu (Organisms Diversity & Evolution, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Recent advances in structural types and medicinal chemistry of PARP-1 inhibitors - Ling Yu; Zhi-wei Yan; You-de Wang; Hao Miao; Jing-yi Zhao; Chong Pang; Shuai Li (Medicinal Chemistry Research, 2022)

Molecular and biochemical characterization of two 4-coumarate: CoA ligase genes in tea plant (Camellia sinensis) - Mingzhuo Li; Lili Guo; Yeru Wang; Yanzhi Li; Xiaolan Jiang; Yajun Liu; De-Yu Xie; Liping Gao; Tao Xia (Plant Molecular Biology, 2022)

Brevibacillus dissolubilis sp. nov., Isolated from Fresh Water - Wei Li; Zhao-Xuan Wang; Fu Ma; Zhi-Da Zi; Han-Yi Chen; De Zhou; Jie Lv (Current Microbiology, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

CRISPR/Cas9-Mediated Transgenesis of the Masu Salmon (Oncorhynchus masou) elovl2 Gene Improves n-3 Fatty Acid Content in Channel Catfish (Ictalurus punctatus) - De Xing; Baofeng Su; Shangjia Li; Max Bangs; David Creamer; Michael Coogan; Jinhai Wang; Rhoda Simora; Xiaoli Ma; Darshika Hettiarachchi; Veronica Alston; Wenwen Wang; et al. (Marine Biotechnology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development and characterization of a rat brain metastatic tumor model by multiparametric magnetic resonance imaging and histomorphology - Shuncong Wang; Lei Chen; Yuanbo Feng; Ting Yin; Jie Yu; Frederik De Keyzer; Ronald Peeters; Chantal Van Ongeval; Guy Bormans; Johan Swinnen; Jeroen Soete; Martine Wevers; et al. (Clinical & Experimental Metastasis, 2022)

Electrical resistivity imaging in Shibaozhai area using magnetotelluric sounding: Enlightenment of hydrocarbon reservoirs on the eastern edge of the Sichuan Basin - Shu-Ming Wang; Qing-Yun Di; Gui-An Zou; Xiao-Lu Su; Cai Qian; Ruo Wang; De-Shan Li (Applied Geophysics, 2022)

Citrus flavonoids and their antioxidant evaluation - Yue Wang; Xiao-Juan Liu; Jie-Biao Chen; Jin-Ping Cao; Xian Li; Chong-De Sun (Critical Reviews in Food Science and Nutrition, 2022)

Study on shear behavior of coral reef limestone–concrete interface - De-jie Li; Chong Shi; Huai-ning Ruan; Bing-yi Li; Wang-yang Li; Xiang-chuan Yao (Marine Georesources & Geotechnology, 2022)

Projecting future changes in extreme climate for maize production in the North China Plain and the role of adjusting the sowing date - Dengpan Xiao; Huizi Bai; De Li Liu; Jianzhao Tang; Bin Wang; Yanjun Shen; Jiansheng Cao; Puyu Feng (Mitigation and Adaptation Strategies for Global Change, 2022)

Seismic high-resolution processing method based on spectral simulation and total variation regularization constraints - Guo Xin; Gao Jian-Hu; Yin Xun-De; Yong Xue-Shan; Wang Hong-Qiu; Li Sheng-Jun (Applied Geophysics, 2022)

Morphological and Molecular Characterization of Paragonimus skrjabini Complex from Yunnan, China: A Brief Report - Qiu-Hong Shu; Shu-De Li; Ming Tian; Yong Meng; Shu-Mei-Qi He; Min Zhu; Miao-Miao Wang; Wen-Lin Wang (Acta Parasitologica, 2022)
Purpose To perform environmental sampling and molecular identification of Paragonimus in endemic regions, which may help in minimizing transmission among humans. Methods Mountain crabs from the genus Potamiscus were collected and the encysted metacercariae were extracted and subjected to morphological identification, followed by animal inoculation in Sprague–Dawley (SD) rats. After 112 days of infection, animals were killed and adult worms were extracted from lungs and muscles. The morphology of adult worms was characterized by microscopy and molecular identification was done by polymerase chain reaction, followed by sequencing of cox1 and ITS2 genes. Phylogenetic analysis was done by maximum parsimony method. Results A total of 447 crabs were captured from the streams of Tongchang Town, Jinping County, Yunnan Province, China. The infection rate was found to be 41% (186 out of 447 crabs). The metacercariae of Paragonimus skrjabini was identified by the characteristics round or spherical encysted form measuring 410 to 460 × 400 to 460 µm. After animal infection in SD rats, adults were presumptively confirmed to be P. skrjabini , which was also confirmed by gene amplification and sequence analysis of cox1 and ITS2 regions. Paragonimus skrjabini clustered with previously reported P. skrjabini from Yunnan and Vietnam. The confidence values of their branches were > 95%. Phylogenetic analysis of the ITS2 region revealed two distinct clusters with distinct geographical grouping. Phylogenetic analysis with the combined data sets reiterated the geographical grouping with P. skrjabini from Yunnan clustering with strains from Vietnam. Conclusion Metacercariae of P. skrjabini was discovered in freshwater crabs in Yunnan province, China, and the strains were phylogenetically related to P. skrjabini from Vietnam.

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Experimental investigation of unconsolidated undrained shear behaviour of peat - Di Wang; Dongqiang Xu; Eileen McCarthy; Romain Rodrigues de Amorim; Zili Li (Bulletin of Engineering Geology and the Environment, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

Implantation of Bone Marrow Mesenchymal Stem Cells into Small Intestinal Submucosa Improves Bile Duct Injury in Rabbits - Ying Li; Piao Wang; Xiao-dong Hu; Jing-da Zeng; Cheng Fang; Yu Gan; Fang-yi Peng; Xiao-li Yang; De Luo; Bo Li; Song Su (Tissue Engineering and Regenerative Medicine, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Cytotoxic sesquiterpenoid quinones from South China Sea sponge Dysidea sp - Xiangchao Luo; Pinglin Li; Kunya Wang; Nicole J. de Voogd; Xuli Tang; Guoqiang Li (Natural Product Research, 2021)

Comparison of pramipexole and levodopa/benserazide combination therapy versus levodopa/benserazide monotherapy in the treatment of Parkinson’s disease: a systematic review and meta-analysis - De-Qi Jiang; Qing-Min Zang; Li-Lin Jiang; Yan Wang; Ming-Xing Li; Jing-Yi Qiao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Human Methylmercury Exposure and Potential Impacts in Central Tibet: Food and Traditional Tibetan Medicine - Menghan Cheng; Maodian Liu; Dou Li; Qing Luo; Zhihao Zhang; Liuliang Yuan; Chenghao Yu; Han Xie; Huiming Lin; Qianru Zhang; De Ji; Xuejun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Marine alkaloids as the chemical marker for the prey–predator relationship of the sponge Xestospongia sp. and the nudibranch Jorunna funebris - Qihao Wu; Song-Wei Li; Nicole J. de Voogd; Hong Wang; Li-Gong Yao; Yue-Wei Guo; Xu-Wen Li (Marine Life Science & Technology, 2021)
The dietary relationship study between marine sponge Xestospongia sp. and its nudibranch predators Jorunna funebris based on the discovery of isoquinolinequinones has long been studied. In this study, chemical investigation of the sponge Xestospongia sp. and nudibranch J. funebris from the South China Sea yielded a new marine alkaloid neopetroside C ( 1 ), together with nine known alkaloids ( 2 – 10 ). The chemical structures of all the compounds were elucidated by extensive spectroscopic analysis. Neopetroside C ( 1 ) featured a riboside of nicotinic acid with a rare α - N glycosildic linkage and an acyl residue of ( Z )-2-methylbut-2-enoic acid attached to C-5′. The plausible chemical ecology relationship between sponge Xestospongia sp. and its nudibranch predator J. funebris was proposed based on the biogenetic relationship of the common marine alkaloids. The observation of two structural fragments, ( Z )-2-methylbut-2-enoyloxy and trigonelline groups in both sponge and nudibranch, indicated that nudibranch might uptake chemicals from sponge and then modify and transform them into chemical weapons to defend against predators.

Characterization of AV422 from Haemaphysalis flava ticks in vitro - Lei Liu; Hao Tang; De-yong Duan; Jin-bao Liu; Jie Wang; Li-li Feng; Tian-yin Cheng (Experimental and Applied Acarology, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Global patterns and drivers of rainfall partitioning by trees and shrubs - Kai Yue; Pieter De Frenne; Dario A. Fornara; Koenraad Van Meerbeek; Wang Li; Xin Peng; Xiangyin Ni; Yan Peng; Fuzhong Wu; Yusheng Yang; Josep Peñuelas (Global Change Biology, 2021)
Spatiotemporal redistribution of incident rainfall in vegetated ecosystems results from the partitioning by plants into intercepted, stemflow, and throughfall fractions. However, variation in patterns and drivers of rainfall partitioning across global biomes remains poorly understood, which limited the ability of climate models to improve the predictions of biome hydrological cycle under global climate change scenario. Here, we synthesized and analyzed the partitioning of incident rainfall into interception, stemflow, and throughfall by trees and shrubs at the global scale using 2430 observations from 236 independent publications. We found that (1) globally, median levels of relative interception, stemflow, and throughfall accounted for 21.8%, 3.2%, and 73.0% of total incident rainfall, respectively; (2) rainfall partitioning varied among different biomes, due to variation in plant composition, canopy structure, and macroclimate; (3) relative stemflow tended to be driven by plant traits, such as crown height:width ratio, basal area, and height, while relative interception and throughfall tended to be driven by plant traits as well as meteorological variables. Our global assessment of patterns and drivers of rainfall partitioning underpins the role of meteorological factors and plant traits in biome‐specific ecohydrological cycles. We suggest to include these factors in climate models to improve the predictions of local hydrological cycles and associated biodiversity and function responses to changing climate conditions.

Study on strength characteristics and mechanism of loess stabilized by F1 ionic soil stabilizer - Jian-dong Li; Xu Wang; Yan-jie Zhang; Dai-jun Jiang; De-ren Liu; Jing-long Wang (Arabian Journal of Geosciences, 2021)

Ground roll separation method via threshold filtering and constraint of seismic wavelet support in curvelet domain - De-ying Wang; Li-hua Chen; Lie-qian Dong; Li-hong Zhao; Ren-wei Ding; Cheng-zhen Ding (Applied Geophysics, 2021)

Multiple diversity facets of crucial microbial groups in biological soil crusts promote soil multifunctionality - Hua Li; Youxin Chen; Gongliang Yu; Federico Rossi; Da Huo; Roberto De Philippis; Xiaoli Cheng; Weibo Wang; Renhui Li (Global Ecology and Biogeography, 2021)
Aim Microbial diversity is one of the most important factors for maintaining the performance of multiple functions in soils (multifunctionality). However, existing studies typically consider the taxonomic richness or Shannon diversity of the entire community. We know little about the connection network of taxonomic and phylogenetic facets of diversity and their collective impact on multifunctionality. In this study, the linkages of effects of diversity within functional groups were disentangled in drylands. Location The central Tibetan Plateau. Time period Present. Major taxa studied Phototrophs and diazotrophs (mainly cyanobacteria). Methods Given the carbon‐ and nitrogen‐limited nature of drylands, we conducted a high‐throughput sequencing of C/N‐fixing functional groups from biocrusts and evaluated multiple facets of diversity (i.e., richness, evenness and phylogeny‐related trait dissimilarity), together with seven crucial variables of soil functioning to calculate multifunctionality. The relationships between multifaceted diversity and abundance with individual functions and multifunctionality were validated by a set of solid statistical analyses. Results We found that the integrated biodiversity index was a stronger predictor of multifunctionality than richness. The divergent performance of different facets of diversity determined the idiosyncratic effect of each functional group on soil multifunctionality. Moreover, the evaluation of functional significance at the species level gave important clues on the trade‐offs and redundancy in each functional group, explaining the distinct patterns of effects of diversity. Richness was the dominant factor for diazotrophs to maximize multifunctionality, whereas phylogenetic dissimilarity was the essential one for phototrophs. Main conclusions Our study demonstrated that multiple facets of diversity should be considered when assessing the effects of biodiversity. In contrast to the community level, within‐functional group measures might adequately capture the features of diversity that are most correlated with soil multifunctionality. Our results provide a perspective to bridge the gap between taxonomic and trait‐based approaches for elucidating the biodiversity–ecosystem function relationship.

Two novel diterpenes from the stems and leaves of tropical seagrass Enhalus acoroides in the South China sea - Xiao-Bing Wang; Zhong-Hao Sun; Li-Xia Fan; Yang-Yang Liu; Jian Feng; Guo-Xu Ma; De-Li Chen (Natural Product Research, 2021)

Di-(2-ethylhexyl) phthalate induces testicular endoplasmic reticulum stress and germ cell apoptosis in adolescent mice - Bin-Bin Zhu; Zhi-Cheng Zhang; Jian Li; Xing-Xing Gao; Yuan-Hua Chen; Hua Wang; Lan Gao; De-Xiang Xu (Environmental Science and Pollution Research, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Air permeability of biochar-amended clay cover - Ming-Yu Li; Wen-Jing Sun; Ye-Jiao Wang; De-An Sun; Yun-Zhi Tan (Arabian Journal of Geosciences, 2021)

Complex microbial communities inhabiting natural Cordyceps militaris and the habitat soil and their predicted functions - Xiao-Mei Zhang; De-Xiang Tang; Qing-Qing Li; Yuan-Bing Wang; Zhi-Hong Xu; Wen-Jun Li; Hong Yu (Antonie van Leeuwenhoek, 2021)

Improved seismoacoustic analysis model and its application to source parameter inversion of near-surface small-yield chemical explosions - Zhang Liang-Yong; Li Xin; Liang Xu-Bin; Wang Tong-Dong; Tang Shi-Ying; Zhang De-Zhi; Zeng Xin-Wu (Applied Geophysics, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Comparative Genomic and Transcriptomic Analyses Revealed Twenty-Six Candidate Genes Involved in the Air-Breathing Development and Function of the Bighead Catfish Clarias macrocephalus - Xiaoli Ma; Baofeng Su; Max Bangs; Veronica Alston; Nathan J. C. Backenstose; Rhoda Mae Simora; Wenwen Wang; De Xing; Shangjia Li; Zhi Ye; Anthony G. Moss; Thuy-Yen Duong; et al. (Marine Biotechnology, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

PapA , a peptidoglycan‐associated protein, interacts with OmpC and maintains cell envelope integrity - Yun‐Hao Wang; Hong‐He Chen; Zhou Huang; Xiao‐Jing Li; Nan Zhou; Chang Liu; Cheng‐Ying Jiang; De‐Feng Li; Shuang‐Jiang Liu (Environmental Microbiology, 2021)
Summary The bacterial cell envelope is critical to support and maintain cellular life. In Gram‐negative bacterial cells, the outer membrane and the peptidoglycan layer are two important parts of the cell envelope and they harbour abundant proteins. Here, we report the identification and characterization of a previously unknown p eptidoglycan‐ a ssociated p rotein, PapA, from the Gram‐negative Comamonas testosteroni . PapA bound peptidoglycan with its C‐terminal domain and interacted with the outer‐membrane porin OmpC. The PapA‐OmpC complex riveted the outer membrane and the peptidoglycan layer, and played a role in maintaining cell envelope integrity. When papA was disrupted, the mutant CNB‐1Δ papA apparently had an outer membrane partly separated from the peptidoglycan layer. Phenotypically, the mutant CNB‐1Δ papA lost chemotactic responses and had longer lag‐phase of growth, less flagellation and higher sensitivity to harsh environments. Totally, 1093 functionally unknown PapA homologues were identified from the public NR protein database and they were mainly distributed in Burkholderiales of Betaproteobacteria. Our finding provides a clue that the PapA homologous proteins might function as a rivet to maintain cell envelope integrity in those Gram‐negative bacteria.

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Effects of seismic force and pore water pressure on stability of 3D unsaturated hillslopes - Long Wang; Wenhua Liu; Wei Hu; Wugang Li; De’an Sun (Natural Hazards, 2021)

Characterizing spatiotemporal rainfall changes in 1960–2019 for continental Australia - De Li Liu; Jin Teng; Fei Ji; Muhuddin R. Anwar; Puyu Feng; Bin Wang; Linchao Li; Cathy Waters (International Journal of Climatology, 2021)
Understanding changes in rainfall at a continental scale can inform adaptation and resilience in all sectors that are sensitive to rainfall. This study examined spatiotemporal changes in annual and seasonal rainfall, extreme and non‐extreme rainfall, and their probability and intensity over the period from 1960 to 2019 across Australia for six rainfall zones (RZs) using high‐quality daily rainfall from 7,593 climate stations. The results revealed statistically significant changes in long‐term rainfall, with an increasing trend in Northern and Central Australia, and a decreasing trend across Southern Australia where the main agricultural areas are located. The cross‐wavelet power spectrum analysis denoted strong coherent resonance cycles in spring–summer or autumn–winter seasons with varying phase differences across six RZs. More specifically, summer rainfall occurred more regularly in the summer‐dominant and arid RZs, whereas winter rainfall became more unreliable in the winter‐ and winter‐dominant RZs. The changes in regional rainfall were characterized by changes in probability and/or intensity of extreme and non‐extreme rainfall revealed through the Spearman Rank correlation. The upward trend in summer‐dominant and arid RZs appears to be a result of increased extreme rainfall intensity and probability, and non‐extreme rainfall probability, especially in summer. The decreased rainfall in the rest of the RZs can be attributed to decreased extreme rainfall probability and non‐extreme rainfall intensity. These results can help decision makers in the agricultural and water resources management sectors identify risks and opportunities, and to devise strategic plans to mitigate droughts through land use planning and construction of infrastructure.

Multi‐model ensemble of CMIP6 projections for future extreme climate stress on wheat in the North China plain - Huizi Bai; Dengpan Xiao; Bin Wang; De Li Liu; Puyu Feng; Jianzhao Tang (International Journal of Climatology, 2021)
Future extreme climate events will become more intense and frequent with global warming, which is a great threat to wheat productivity in the North China Plain (NCP). Projecting future changes in extreme climate events is an important prerequisite for exploring crop adaptation measures to climate variation. In this study, we calculated 11 extreme climate indices at different wheat growth stages that are sensitive to wheat yield across NCP. The future climate projections were sourced from thirteen Global Climate Models (GCMs) from the Coupled Model Inter‐comparison Project phase 6 (CMIP6) under two emission scenarios of future societal development pathway (SSP) 245 and SSP585. Daily climate data of thirteen GCMs were generated by using a statistically downscaled method. Two multi‐model ensemble methods, that is, arithmetic mean and independence weighted mean (IWM), were used to assess the performance of thirteen GCMs in reproducing historical changes of extreme climate indices. The IWM ensemble results could better reproduce historical changes of extreme climate indices than multi‐model arithmetic mean and any individual GCM. We found that the frequency and intensity of heat extremes were projected to increase over the 21st century for both scenarios, but those of cold extremes will decrease. Heat stress intensity (HSI) increases around 1.0°C for SSP245 scenario and 1.6°C for SSP585 scenario by the end of the 21st century. There was no significant change in extreme precipitation indices across the NCP, but the changes of extreme precipitation had strong spatial heterogeneity. Overall, wheat production in the NCP might have a higher frequency of exposure to extreme climate, especially under heat stress. Therefore, adopting effective adaptation measures to mitigate heat stress for wheat is the first priority in the NCP.

Enhanced potential ecological risk induced by a large scale water diversion project - Meixiu Yu; Paul Wood; Nick van de Giesen; Xiaolong Liu; Qiongfang Li; Guoqing Wang; Jianyun Zhang (Stochastic Environmental Research and Risk Assessment, 2020)

Analyzing adaptation strategies for maize production under future climate change in Guanzhong Plain, China - Qaisar Saddique; Huanjie Cai; Jiatun Xu; Ali Ajaz; Jianqiang He; Qiang Yu; Yunfei Wang; Hui Chen; Muhammad Imran Khan; De Li Liu; Liang He (Mitigation and Adaptation Strategies for Global Change, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Identification of AP2/ERF genes in apple (Malus × domestica) and demonstration that MdERF017 enhances iron deficiency tolerance - Li Cheng; Tong Zhao; Yu-Xia Wu; Hai Wang; Zhong-Xing Zhang; De Zhang; Shuang-Cheng Wang; Yan-Xiu Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Contrasted effects of temperature during defoliation vs. refoliation periods on the infection of rubber powdery mildew (Oidium heveae) in Xishuangbanna, China - De-Li Zhai; Jing Wang; Philippe Thaler; Yiqi Luo; Jianchu Xu (International Journal of Biometeorology, 2020)

Modeling trophic interactions and impacts of introduced icefish (Neosalanx taihuensis Chen) in three large reservoirs in the Yangtze River basin, China - Geng Huang; Qidong Wang; Xue Du; Kai Feng; Shaowen Ye; Jing Yuan; Jiashou Liu; Zhongjie Li; Sena S. De Silva (Hydrobiologia, 2020)

Transcriptome analysis of rice leaves in response to Rhizoctonia solani infection and reveals a novel regulatory mechanism - De Peng Yuan; Xiao Feng Xu; Woo-Jong Hong; Si Ting Wang; Xin Tong Jia; Yang Liu; Shuang Li; Zhi Min Li; Qian Sun; Qiong Mei; Shuai Li; Ki-Hong Jung; et al. (Plant Biotechnology Reports, 2020)

Potential Benefits of Potato Yield at Two Sites of Agro-Pastoral Ecotone in North China Under Future Climate Change - Jianzhao Tang; Dengpan Xiao; Huizi Bai; Bin Wang; De Li Liu; Puyu Feng; Yuan Zhang; Jun Zhang (International Journal of Plant Production, 2020)

Nonstationary signal inversion based on shaping regularization for random noise attenuation - Wu-Yang Yang; Wei Wang; Guo-Fa Li; Xin-Jian Wei; Wan-Li Wang; De-wu Chen (Applied Geophysics, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Demography and adaptation promoting evolutionary transitions in a mammalian genus that diversified during the Pleistocene - Menno J. de Jong; Zhipeng Li; Yanli Qin; Erwan Quéméré; Karis Baker; Wen Wang; A. Rus Hoelzel (Molecular Ecology, 2020)
Species that evolved in temperate regions during the Pleistocene experienced periods of extreme climatic transitions. Consequent population fragmentation and dynamics had the potential to generate small, isolated populations where the influence of genetic drift would be expected to be strong. We use comparative genomics to assess the evolutionary influence of historical demographics and natural selection through a series of transitions associated with the formation of the genus Capreolus , speciation within this genus during the Quaternary and during divergence among European roe deer ( C. capreolus ) populations. Our analyses were facilitated by the generation of a new high‐coverage reference genome for the Siberian roe deer ( C. pygargus ). We find progressive reductions in effective population size ( N e ), despite very large census sizes in modern C. capreolus populations and show that low N e has impacted the C. capreolus genome, reducing diversity and increasing linkage disequilibrium. Even so, we find evidence for natural selection shared among C. capreolus populations, including a historically documented founder population that has been through a severe bottleneck. During each phylogenetic transition there is evidence for selection (from dN/dS and nucleotide diversity tests), including at loci associated with diapause (delayed embryonic development), a phenotype restricted to this genus among the even‐toed ungulates. Together these data allow us to assess expectations for the origin and diversification of a mammalian genus during a period of extreme environmental change.

New 2-(2-phenylethyl)chromone derivatives from agarwood and their inhibitory effects on tumor cells - Yang-Yang Liu; De-Li Chen; Zhang-Xin Yu; Wang Can-Hong; Jian Feng; Yu Meng; Jian-He Wei (Natural Product Research, 2020)

Epidemiological survey and genetic evolution of H3N2 subtype influenza viruses from stray dogs in Shanghai, China - Hai-Xiao Shen; Fei-Fei Ge; Xin Li; Jian Liu; Hou-Bing Ju; De-Quan Yang; Xian-Chao Yang; Jian Wang; Hong-Jin Zhao (Virus Genes, 2020)

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Tide-Surge Interaction in the Pearl River Estuary: A Case Study of Typhoon Hato - Peng Zheng; Ming Li; Caixia Wang; Judith Wolf; Xueen Chen; Michela De Dominicis; Peng Yao; Zhan Hu (Frontiers in Marine Science, 2020)

Coix seed oil prolongs lifespan and enhances stress resistance in Caenorhabditis elegans - Xin-Yan Chen; De-Chun Liao; Ying-Ting Yu; Cong-Min Wei; Ling-Yan Xuan; Shan Li; Hong-Bing Wang (Biogerontology, 2020)

Expression profiles of three crustin-like genes in Litopenaeus vannamei under Vibrio harveyi infection - Mao-Cang Yan; Yao-Hua Wang; De-Wei Ji; Fang Li; Li-Hua Hu; Min Zhang (Aquaculture International, 2020)

The implication of spatial interpolated climate data on biophysical modelling in agricultural systems - De Li Liu; Fei Ji; Bin Wang; Cathy Waters; Puyu Feng; Rebecca Darbyshire (International Journal of Climatology, 2020)
Spatial modelling of agricultural production has been more frequently analysed to assist with regional and long‐term planning. Typically, point‐scale crop models are used to construct these analyses with researchers using various sources of input data, including observed and interpolated gridded climate data. Understanding the implication of data choice on production estimates is crucial to appreciate the consequences of selecting methodological approaches for agricultural model outputs. In this study, we compared site observed climate data and gridded data sets interpolated from site observations that are commonly used the Australian climate data set. We assessed the consequences of the differences in climate variables (biases) to the modelled outputs. Our results showed that the major differences between gridded and observed climate data sets were for rainfall variables. Interpolated gridded data tended to have larger rainfall frequency and smaller rainfall intensity, leading to lower surface runoff and higher soil evaporation that caused less plant water uses and less nitrogen uptake, and ultimately resulted in biases in simulated crop biomass and yield. In addition, the results indicated that agricultural models implemented with gridded data could produce similar overall model outputs as those driven by observed climate data, but can result in more uncertainties in simulated spatial outputs. This is particularly evident in regions with high rainfall. Our results showed that applying agricultural models with observed data and then interpolating these results spatially might be the optimal approach to minimize the biases in production modelling outputs and reduce computing time and storage.

Aliphatic suberin confers salt tolerance to Arabidopsis by limiting Na+ influx, K+ efflux and water backflow - Pei Wang; Chun-Mei Wang; Li Gao; Yan-Nong Cui; Hai-Li Yang; Nayana D. G. de Silva; Qing Ma; Ai-Ke Bao; Timothy J. Flowers; Owen Rowland; Suo-Min Wang (Plant and Soil, 2020)

Separating and imaging diffractions in dip domain on the basis of slope analysis - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2020)

Volatile‐mediated antagonism of soil bacterial communities against fungi - Xiaogang Li; Paolina Garbeva; Xiaojiao Liu; Paulien J. A. klein Gunnewiek; Anna Clocchiatti; Maria P. J. Hundscheid; Xingxiang Wang; Wietse de Boer (Environmental Microbiology, 2020)
Summary Competition is a major type of interaction between fungi and bacteria in soil and is also an important factor in suppression of plant diseases caused by soil‐borne fungal pathogens. There is increasing attention for the possible role of volatiles in competitive interactions between bacteria and fungi. However, knowledge on the actual role of bacterial volatiles in interactions with fungi within soil microbial communities is lacking. Here, we examined colonization of sterile agricultural soils by fungi and bacteria from non‐sterile soil inoculums during exposure to volatiles emitted by soil‐derived bacterial communities. We found that colonization of soil by fungi was negatively affected by exposure to volatiles emitted by bacterial communities whereas that of bacteria was barely changed. Furthermore, there were strong effects of bacterial community volatiles on the assembly of fungal soil colonizers. Identification of volatile composition produced by bacterial communities revealed several compounds with known fungistatic activity. Our results are the first to reveal a collective volatile‐mediated antagonism of soil bacteria against fungi. Given the better exploration abilities of filamentous fungi in unsaturated soils, this may be an important strategy for bacteria to defend occupied nutrient patches against invading fungi. Another implication of our research is that bacterial volatiles in soil atmospheres can have a major contribution to soil fungistasis.

Enhanced stability of a rumen-derived xylanase using SpyTag/SpyCatcher cyclization - Ye-Bo Zhou; Jia-Wen Cao; Xiao-Bao Sun; Huan Wang; De-Ying Gao; Yang-Nan Li; Kai-Yue Wu; Jia-Kun Wang; Guo-Ying Qian; Qian Wang (World Journal of Microbiology and Biotechnology, 2020)

Two new species of Encyrtidae (Hymenoptera: Chalcidoidea) from China, parasitoid of Antecerococcus roseus (Green) (Hemiptera: Cerococcidae) on Boehmeria nivea (L.) Gaud - Guo-Hao Zu; Ze-Ning Yang; Xin-Sheng Cao; Yuan-Hong Wang; Cheng-De Li (Phytoparasitica, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Biallelic INTS1 Mutations Cause a Rare Neurodevelopmental Disorder in Two Chinese Siblings - Xuemin Zhang; Yajian Wang; Fang Yang; Jiulai Tang; Xiaoyan Xu; Li Yang; Xiu-An Yang; De Wu (Journal of Molecular Neuroscience, 2020)

Using GPS and InSAR data to assess the cumulative damage of an underground utility tunnel - Shuan hu Li; Chi Li; De Yao; Chun xiao Wang (Arabian Journal of Geosciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

A changed post‐flood management strategy enables the culture‐based fishery of the Liangzi Lake, Yangtze River Basin, China, to remain economically and environmentally viable - Qidong Wang; Zhongjie Li; Mingli Lin; Shaowe Ye; Wei Li; Chuanbo Guo; Geng Huang; Jing Yuan; Jiashou Liu; Sena S. De Silva (Fisheries Management and Ecology, 2019)
The culture‐based fishery of Liangzi Lake, Yangtze River Basin, established in 1992, yielded 2,652 t/year (±167) between 2005 and 2015, dominated by stocked carps [ Hypophthalmichthys molitrix (Val.) and Hypophthalmichthys nobilis (Richardson)] and mitten crab Eriocheir sinensis (Milne Edwards), accounting for 53% and 23% of the production and 20% and 52% in value, respectively. The lake had a macrophyte cover dominated by Vallisneria natans (Lour.) Hara with a cumulative biomass of 10,647 g/m 2 that disappeared after a major flood in 2010 and changed its ecology. Management changes in stocking strategies introduced in the post‐flood period enabled the culture‐based fishery to maintain viability and sustainability to combat the major ecological change in the lake. The stocked species contributed significantly to nutrient removal of 24.71 ± 5.12 t/yr and 6.29 ± 0.87 t/yr of total nitrogen and total phosphorus, respectively.

An endophytic Kocuria palustris strain harboring multiple arsenate reductase genes - Tania Zacaria Vital; Brenda Román-Ponce; Flor N. Rivera Orduña; Paulina Estrada de los Santos; M. Soledad Vásquez-Murrieta; Yue Deng; Hong Li Yuan; En Tao Wang (Archives of Microbiology, 2019)

Modelling and evaluating the impacts of climate change on three major crops in south-eastern Australia using regional climate model simulations - Bin Wang; De Li Liu; Jason P. Evans; Fei Ji; Cathy Waters; Ian Macadam; Puyu Feng; Kathleen Beyer (Theoretical and Applied Climatology, 2019)

Rhizobium sophorae, Rhizobium laguerreae, and two novel Rhizobium genospecies associated with Vicia sativa L. in Northwest China - Junjie Zhang; Yimin Shang; Shanshan Peng; Wenfeng Chen; Entao Wang; Philippe de Lajudie; Benyin Li; Chen Guo; Chunzeng Liu (Plant and Soil, 2019)

A Further Study on the Simulation of Cloud-Radiative Feedbacks in the ENSO Cycle in the Tropical Pacific with a Focus on the Asymmetry - Lin Chen; De-Zheng Sun; Lu Wang; Tim Li (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Front Cover - Lu Lu; Peter W. Fritsch; Nicholas J. Matzke; Hong Wang; Kathleen A. Kron; De‐Zhu Li; John J. Wiens (Global Ecology and Biogeography, 2019)

Why is fruit colour so variable? Phylogenetic analyses reveal relationships between fruit‐colour evolution, biogeography and diversification - Lu Lu; Peter W. Fritsch; Nicholas J. Matzke; Hong Wang; Kathleen A. Kron; De‐Zhu Li; John J. Wiens (Global Ecology and Biogeography, 2019)
Aim Are different fruit colours related to large‐scale patterns of dispersal, distribution and diversification? Here, we investigate this question for the first time, using phylogenetic approaches in the tribe Gaultherieae (Ericaceae). We test relationships between fruit colour and (a) biogeographic dispersal, (b) elevational and latitudinal species distributions and (c) rates of diversification. Location Global. Time period Recent to 30 million years ago. Major taxa studied The plant tribe Gaultherieae in the family Ericaceae (blueberries and relatives). Methods We estimated a new time‐calibrated phylogeny for Gaultherieae. Data on fruit colours and geographic distributions for each species were compiled from published sources and field observations. Using phylogenetic methods, we estimated major dispersal events across the tree and the most likely fruit colour associated with each dispersal event, and tested whether dispersal between major biogeographic regions was equally likely for different fruit colours, and whether dispersal distances were larger for certain colours. We then tested the relationships between fruit colours and geographic variables (latitude, elevation) and diversification rates. Results Large‐scale dispersal events were significantly associated with red‐fruited lineages, even though red‐fruited species were relatively uncommon. Further, different fruit colours were associated with different elevations and latitudes (e.g. red at lower elevations, violet at lower latitudes, white at higher elevations). Violet colour was related to increased diversification rates, leading to more violet‐fruited species globally. Main conclusions Overall, we show that different fruit colours can significantly impact the large‐scale dispersal, distribution and diversification of plant clades. Furthermore, the interplay between biogeography and fruit‐colour evolution seems to generate “taxon cycles” in fruit colour that may drive variation in fruit colour over macroevolutionary time‐scales.

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Temporal–spatial distribution of synthetic pyrethroids in overlying water and surface sediments in Guangzhou waterways: potential input mechanisms and ecological risk to aquatic systems - Wen-Gai Li; De-Yin Huang; Dong Chen; Cong Wang; Gao-Ling Wei (Environmental Science and Pollution Research, 2019)

An Outbreak of Gastroenteritis Associated with GII.17 Norovirus-Contaminated Secondary Water Supply System in Wuhan, China, 2017 - Xuan Zhou; De-Guang Kong; Jing Li; Bei-Bei Pang; Ying Zhao; Jun-Bo Zhou; Ting Zhang; Jun-Qiang Xu; Nobumichi Kobayashi; Yuan-Hong Wang (Food and Environmental Virology, 2019)

Correction to: A new species of Microterys (Hymenoptera: Encyrtidae) from Northeast China, parasitoid of Parthenolecanium corni (Bouché) (Hemiptera: Coccidae) - Guo-Hao Zu; Cheng-De Li; Yuan-Hong Wang (Phytoparasitica, 2019)

Lipid accumulation in grass carp (Ctenopharyngodon idellus) fed faba beans (Vicia faba L.) - Jing-jing Tian; Hong Ji; Yi-fei Wang; Jun Xie; Guang-jun Wang; Zhi-fei Li; Er-meng Yu; De-guang Yu; Kai Zhang; Wang-bao Gong (Fish Physiology and Biochemistry, 2019)

Evaluation of a traditional method for peak flow discharge estimation for floods in the Wenchuan Earthquake area, Sichuan Province, China - Xiao-jun Guo; Peng Cui; Yong Li; Jin-feng Liu; Yong-gang Ge; Ci-de Wang (Journal of Mountain Science, 2019)

A predictive deconvolution method for non-white-noise reflectivity - De-Ying Wang; Xue Kong; Lie-Qian Dong; Li-Hua Chen; Yong-Jun Wang; Xiao-Chen Wang (Applied Geophysics, 2019)

Sex difference in the association of body mass index and BDNF levels in Chinese patients with chronic schizophrenia - Fang Yang; Keming Wang; Xiangdong Du; Huiqiong Deng; Hanjing Emily Wu; Guangzhong Yin; Yuping Ning; Xingbing Huang; Antonio L. Teixeira; João de Quevedo; Jair C. Soares; Xiaosi Li; et al. (Psychopharmacology, 2019)

Correction to: A new species of Anagyrus (Hymenoptera: Encyrtidae) from China, parasitoid of Phenacoccus solani Ferris (Hemiptera: Pseudococcidae) on Lycoris radiata (L’Her.) Herb. - Guo-Hao Zu; Yuan-hong Wang; Yan-Zhou Zhang; Cheng-De Li; Xu Zhang (Phytoparasitica, 2019)

3D stability of partially saturated soil slopes after rapid drawdown by a new layer-wise summation method - Long Wang; De’an Sun; Lin Li (Landslides, 2019)

Projected changes in drought across the wheat belt of southeastern Australia using a downscaled climate ensemble - Puyu Feng; De Li Liu; Bin Wang; Cathy Waters; Mingxi Zhang; Qiang Yu (International Journal of Climatology, 2019)
Drought is viewed as a naturally recurring phenomenon in many Australian agricultural systems. Identifying regional changes in frequency and severity of drought induced by climate change is required to develop regionally specific adaptation strategies. In this study, we provided a first look at the impacts of climate change on 21st century drought characteristics over the New South Wales wheat belt of southeastern Australia. These impacts were assessed from an ensemble of 28 statistical downscaled global climate models under representative concentration pathway (RCP8.5). A modified relative standardized precipitation and evapotranspiration index (rSPEI) at the seasonal scale (3 months) was used to analyse temporal and spatial changes in drought. Results indicated that there was a tendency towards more frequent and severe winter–spring droughts over the study area. Moreover, winter–spring drought prone areas were expected to expand from west to east. Until the end of the 21st century, more than half the wheat belt would be vulnerable to winter–spring drought. The combined effects of reduced precipitation and increased temperature during future winter and spring seasons were the main reasons causing these changes of drought. In addition, summer and autumn droughts would have both slight temporal and spatial changes across the study region. This study also revealed that traditionally dry areas would likely experience an increased frequency of drought compared to wetter areas when subjected to a same increase in temperature or decrease in precipitation. Furthermore, the western part of the wheat belt might be unsuitable for winter crops in the future, or at least exposed to an increased risk of variable yield and would require a gradual transformation which might include summer crops or pastures. Investments in cropping land should be focused on the east part of the wheat belt to achieve more consistent financial returns.

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

The influence of porcine epidemic diarrhea virus on pig small intestine mucosal epithelial cell function - Xing-Ye Wang; Tai-Qiang Zhao; De-Peng Xu; Xue Zhang; Cheng-Jie Ji; De-Li Zhang (Archives of Virology, 2019)

Identification of a novel strain, Streptomyces blastmyceticus JZB130180, and evaluation of its biocontrol efficacy against Monilinia fructicola - Mi Ni; Qiong Wu; Hong-li Wang; Wei-cheng Liu; Bin Hu; Dian-peng Zhang; Juan Zhao; De-wen Liu; Cai-ge Lu (Journal of Zhejiang University-SCIENCE B, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Propagation of climate model biases to biophysical modelling can complicate assessments of climate change impact in agricultural systems - De Li Liu; Bin Wang; Jason Evans; Fei Ji; Cathy Waters; Ian Macadam; Xihua Yang; Kathleen Beyer (International Journal of Climatology, 2019)
Regional climate model (RCM) simulations are being increasingly used for climate change impact assessments, but their application is challenging due to considerable biases inherited from global climate model (GCM) simulations and generated from dynamical downscaling processes. This study assesses the biases in NARCliM (NSW and ACT regional climate modelling) simulations and quantifies the consequence of the climate biases in the downstream assessment of climate change impact on wheat crop system, using the Agricultural Production System sIMulator (APSIM). Results showed that post‐processing bias‐corrected temperature and rainfall data from NARCliM had small annual mean biases but large biases in the crop growing season (CGS). During the CGS, the mean bias error of rainfall was generally positive for rainfall probability and negative for intensity, which subsequently resulted in APSIM simulating negative biases for runoff and deep drainage and positive bias in soil evaporation. Bias in soil water balance and water availability resulted in less plant transpiration and less N uptake, ultimately, leading to large negative biases in crop yields. A simple bias correction of the simulated crop yield driven by RCMs could result in a largely consistent distribution with those generated with APSIM simulations forced by observed climate. Our results showed that RCM simulation biases could confound with the climate change signal and produced an unreliable estimate of the effects of the changes in climate and farm management variables on crop yields. The results suggested that RCM simulations with the current bias correction on the RCM‐simulated outputs applied on an annual basis were inadequate for climate change assessments which involve biophysical models. Our study highlights the need for improved RCM simulations by eliminating the systemic biases associated with rainfall characteristics, although suitable post‐processing bias correction on a seasonal or monthly basis may result in improved RCM simulations for agricultural impacts of climate change.

Mesorhizobium jarvisii sv. astragali as predominant microsymbiont for Astragalus sinicus L. in acidic soils, Xinyang, China - Junjie Zhang; Yimin Shang; Entao Wang; Wenfeng Chen; Philippe de Lajudie; Benyin Li; Chen Guo; Xu Yang; Jianqiang Zheng; Chunzeng Liu (Plant and Soil, 2018)

MHC class IIA polymorphisms and their association with resistance–susceptibility to Streptococcus agalactiae in Nile tilapia, Oreochromis niloticus - Feng‐Ying Gao; Dong Zhang; Mai‐Xin Lu; Jian‐Meng Cao; Zhi‐Gang Liu; Xiao‐Li Ke; Miao Wang; De‐Feng Zhang; Meng‐Meng Yi (Journal of Fish Biology, 2018)
The association between major histocompatibility complex (MHC) class IIA polymorphisms and the severity of infection by Streptococcus agalactiae was investigated using 40 susceptible and 40 resistant individuals of Nile tilapia Oreochromis niloticus . Twenty‐five alleles were identified from 80 individuals, which belong to 22 major allele types. High polymorphism of mhcIIa gene and at least two loci were discovered in O. niloticus . In peptide‐binding region (PBR) and non‐PBR, the ratio of nonsynonymous substitution ( dN ) to synonymous substitution ( dS ) was 1.294 (>1) and 1.240 (>1), suggesting that the loci are evolving under positive balancing selection. Association analysis showed that the allele, orni‐daa*0501 , was significantly associated with resistance to S. agalactiae , while the alleles, orni‐daa*1101 , orni‐daa*1301 , orni‐daa*1401 and orni‐daa*1201 , were associated with susceptibility to S. agalactiae . To confirm these correlations, another independent challenge experiment was performed in the Huizhou population of the O. niloticus . The frequency distribution showed that the orni‐daa*1101 allele was significantly more frequent in the Huizhou‐Susceptible group (HZ‐SG) than in the Huizhou‐Resistant group (HZ‐RG) ( P orni‐daa*0501 did not present in HZ‐SG and HZ‐RG and the distribution frequencies of the orni‐daa*1201 , orni‐daa*1301 and orni‐daa*1401 alleles were not significantly more frequent in HZ‐SG than in HZ‐RG. These results indicate that the orni‐daa*1101 allele confers susceptibility to S. agalactia infection. These results suggest that the diversity of exon 2 of mcaIIa alleles could be used to explore the association between disease susceptibility or resistance and the multiformity of mcaIIa and to achieve the molecular‐assisted selection of O. niloticus with enhanced disease resistance.

A new species of Microterys (Hymenoptera: Encyrtidae) from Northeast China, parasitoid of Parthenolecanium corni (Bouché) (Hemiptera: Coccidae) - Guo-Hao Zu; Cheng-De Li; Yuan-Hong Wang (Phytoparasitica, 2018)

Quantifying sources of uncertainty in projected wheat yield changes under climate change in eastern Australia - Bin Wang; De Li Liu; Cathy Waters; Qiang Yu (Climatic Change, 2018)

The relative importance of space compared to topography increases from rare to common tree species across latitude - Yue‐Hua Hu; Daniel J. Johnson; Xiang‐Cheng Mi; Xu‐Gao Wang; Wan‐Hui Ye; Yi‐De Li; Ju‐Yu Lian; Min Cao (Journal of Biogeography, 2018)
Aim Understanding how spatial distributions of rare and common species are associated with environmental and spatial processes is essential to understanding community assembly. We addressed the following questions: (a) does the relative importance of space and topography vary from rare to common tree species? (b) Are the contributions of topography and space equal? (c) Are the variances explained by topography or space correlated with elevational ranges (ER) at the local scale? (d) Does cell‐size influence those postulated associations? Location China and the Americas. Major taxa studied Tree species. Methods We partitioned the variation in species richness and composition of rare and common tree species by topography and space across a range of extents and grain sizes in eight communities. We calculated contribution ratio ( CR ) between space and topography to quantify their relative importance. We employed Kendall's rank correlation to determine the relation between CR and commonness. Mixed effect models were used to identify the influence of cell‐size on the results. Results The majority of CR values were positively related to increasing commonness, especially for composition. The explained variances by space were always higher than that by topography regardless of commonness. At local scale, variances explained by space or topography were not correlated with ER. Main conclusions Our results indicate that the relative importance of space compared to topography increases from rare to common species across forests. We suggest that future studies of community assembly need to account for both space and topography to adequately describe differences in rare and common species assembly mechanisms at range of spatial extents and grain sizes.

Using multi‐model ensembles of CMIP5 global climate models to reproduce observed monthly rainfall and temperature with machine learning methods in Australia - Bin Wang; Lihong Zheng; De Li Liu; Fei Ji; Anthony Clark; Qiang Yu (International Journal of Climatology, 2018)
Global climate models (GCMs) are useful tools for assessing climate change impacts on temperature and rainfall. Although climate data from various GCMs have been increasingly used in climate change impact studies, GCMs configurations and module characteristics vary from one to another. Therefore, it is crucial to assess different GCMs to confirm the extent to which they can reproduce the observed temperature and rainfall. Rather than assessing the interdependence of each GCM, the purpose of this study is to compare the capacity of four different multi‐model ensemble (MME) methods (random forest [RF], support vector machine [SVM], Bayesian model averaging [BMA] and the arithmetic ensemble mean [EM]) in reproducing observed monthly rainfall and temperature. Of these four methods, the RF and SVM demonstrated a significant improvement over EM and BMA in terms of performance criteria. The relative importance of each GCM based on the RF ensemble in reproducing rainfall and temperature could also be ranked. We compared the GCMs importance and Taylor skill score and found that their correlation was 0.95 for temperature and 0.54 for rainfall. Our results also demonstrated that the number of GCMs ensemble simulations could be reduced from 33 to 25 in RF model while maintaining predictive error less than 2%. Having such a representative subset of simulations could reduce computational costs for climate impact modelling and maintain the quality of ensemble at the same time. We conclude that machine learning MME could be efficient and useful with improved accuracy in reproducing historical climate variables.

Characterization, tissue distribution of apela and periprandial, fasting and refeeding changes of apela mRNA in Siberian sturgeon Acipenser baerii - Ni Tang; Jin Hao; Xin Zhang; Yuan B. Wu; Shu Y. Wang; Jin W. Qi; Zhen Z. Tian; Bin Wang; Hu Chen; De F. Chen; Zhi Q. Li (Journal of Fish Biology, 2018)
Apela identified from zebrafish Danio rerio for the first time in 2013 is a novel endogenous peptide ligand for the apelin receptor. To study the role of apela in regulating fish feeding, the complementary (c) DNA sequence of apela of Siberian sturgeon Acipenser baerii was cloned for the first time. The apela cDNA fragment of 836 bp was obtained by cloning. The open reading frame (ORF) of apela was 165 bp encoding a 54 amino acid, including 22 amino acids signal peptide and two proteolytic sites. Phylogenetic tree analysis showed that A. baerii apela was clustered with mammalian and amphibian sequences. A. baerii apela messeger (m)RNA was widely distributed in 11 tissues related to feeding, with high expressions in brain, oesophagus and stomach, especially in the brain. The level of apela mRNA in brain increased significantly after feeding. On the first day of fasting, apela expression in brain was significantly lower than that of the fed group, but after fasting for 3–15 days, the expression of apela in A. baerii brain was significantly higher than that in the fed group. After refeeding apela mRNA expression was obviously reduced. These results suggest that apela plays a bidirectional role in feeding regulation of A. baerii , which may serve as a short‐term satiation factor and a long‐term hunger factor.

Testing Darwin's transoceanic dispersal hypothesis for the inland nettle family (Urticaceae) - Zeng‐Yuan Wu; Jie Liu; Jim Provan; Hong Wang; Chia‐Jui Chen; Marc W. Cadotte; Ya‐Huang Luo; Bruno S. Amorim; De‐Zhu Li; Richard I. Milne (Ecology Letters, 2018)
Dispersal is a fundamental ecological process, yet demonstrating the occurrence and importance of long‐distance dispersal ( LDD ) remains difficult, having rarely been examined for widespread, non‐coastal plants. To address this issue, we integrated phylogenetic, molecular dating, biogeographical, ecological, seed biology and oceanographic data for the inland Urticaceae. We found that Urticaceae originated in Eurasia c . 69 Ma, followed by ≥ 92 LDD events between landmasses. Under experimental conditions, seeds of many Urticaceae floated for > 220 days, and remained viable after 10 months in seawater, long enough for most detected LDD events, according to oceanographic current modelling. Ecological traits analyses indicated that preferences for disturbed habitats might facilitate LDD . Nearly half of all LDD events involved dioecious taxa, so population establishment in dioecious Urticaceae requires multiple seeds, or occasional selfing. Our work shows that seawater LDD played an important role in shaping the geographical distributions of Urticaceae, providing empirical evidence for Darwin's transoceanic dispersal hypothesis.

A unique genetic lineage at the southern coast of China in the agar-producing Gracilaria vermiculophylla (Gracilariales, Florideophyceae) - Zi-Min Hu; Ruo-Yu Liu; Jie Zhang; De-Lin Duan; Gao-Ge Wang; Wen-Hong Li (Algae, 2018)

Screening wheat genotypes for better performance on reduced phosphorus supply by comparing glasshouse experiments with field trials - De-Yong Zhao; Shu-Song Zheng; Muhammad Kashif Naeem; Jian-Qing Niu; Ning Wang; Zhong-Jian Li; Hui-Lan Wu; Hong-Qing Ling (Plant and Soil, 2018)

Multi-model ensemble projections of future extreme heat stress on rice across southern China - Liang He; James Cleverly; Bin Wang; Ning Jin; Chunrong Mi; De Li Liu; Qiang Yu (Theoretical and Applied Climatology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Proteomic analysis of human umbilical vein endothelial cells exposed to PM2.5 - Ji Zhu; Lin-wen-si Zhu; Jin-huan Yang; Ying-ling Xu; Cui Wang; Zhuo-yu Li; Wei Mao; De-zhao Lu (Journal of Zhejiang University-SCIENCE B, 2018)

A revisit to fishmeal usage and associated consequences in Chinese aquaculture - Dong Han; Xiujuan Shan; Wenbing Zhang; Yushun Chen; Qingyin Wang; Zhongjie Li; Guofan Zhang; Pao Xu; Jiale Li; Shouqi Xie; Kangsen Mai; Qisheng Tang; et al. (Reviews in Aquaculture, 2018)
China has dominated global aquaculture production for more than two decades. Aquaculture production in China increased from 24.6 million metric tons (mmt) in 2000 to 47.5 mmt in 2014, an increment of 93.1%. Along with the fast‐growing aquaculture industry, aquafeed production in China increased from 5.1 mmt in 2000 to 19.0 mmt in 2014, an increment of 272.5%. However, despite the rapid increase in aquafeed production, the fishmeal usage in aquafeeds in China has remained stable over the years. Fishmeal imports into China remained relatively steady at 1.0–1.5 mmt per annum from 2000 to 2014. An often unacknowledged fact is that China contributes more than 60% to the world aquaculture production at a cost of only 25–30% of the world fishmeal output. This review attempts to explain why the fishmeal usage has not increased proportionately with the increasing aquafeed production in China from several angles: (i) the current status of fishmeal usage in Chinese aquaculture; (ii) the relationship between the decreasing dietary inclusions of fishmeal and improved feed techniques, especially the use of alternative protein sources for fishmeal; (iii) the dominance of Chinese aquaculture by low trophic level species of plants, filter feeders, herbivores and omnivores and consequent low demands for fishmeal; and (iv) the increasing price of fishmeal and the management of exploitation of wild fisheries in the main fishmeal exporting countries to China. The trends and prospects of fishmeal usage in the future in Chinese aquaculture and the associated consequences are also addressed. Like other countries, China is now actively developing both resource conservation‐based capture fisheries and environment‐friendly freshwater and marine aquaculture systems. Aquaculture will be the main source of aquatic food in the future and will also indirectly contribute to save the world wild fisheries, and China will be main player that will continue to contribute towards this end.

A new species of Anagyrus (Hymenoptera: Encyrtidae) from China, parasitoid of Phenacoccus solani Ferris (Hemiptera: Pseudococcidae) on Lycoris radiata (L’Her.) Herb. - Guo-Hao Zu; Yuan-hong Wang; Yan-Zhou Zhang; Cheng-De Li; Xu Zhang (Phytoparasitica, 2018)

Impacts of rainfall extremes on wheat yield in semi-arid cropping systems in eastern Australia - Puyu Feng; Bin Wang; De Li Liu; Hongtao Xing; Fei Ji; Ian Macadam; Hongyan Ruan; Qiang Yu (Climatic Change, 2018)

Forecasting industrial water demand in Huaihe River Basin due to environmental changes - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; Shou-hai Bi; Amgad Elmahdi; Chuan-hua Liao; You-de Li (Mitigation and Adaptation Strategies for Global Change, 2018)

Structures and bioactivities of seven flavonoids from Osmanthus fragrans ‘Jinqiu’ essential oil extraction residues - Jiang-Lian Zhou; Xian-Ying Fang; Jing-Qiu Wang; Lin-Guo Zhao; Yi Li; Feng Tang; Yong-De Yue (Natural Product Research, 2018)

Co-treatment of flotation waste, neutralization sludge, and arsenic-containing gypsum sludge from copper smelting: solidification/stabilization of arsenic and heavy metals with minimal cement clinker - De-Gang Liu; Xiao-Bo Min; Yong Ke; Li-Yuan Chai; Yan-jie Liang; Yuan-Cheng Li; Li-Wei Yao; Zhong-Bing Wang (Environmental Science and Pollution Research, 2018)

Exchange fluxes of VOSCs between rice paddy fields and the atmosphere in the oasis of arid area in Xinjiang, China - Wei Wen Jing; Ning Li; Xiao Fang Li; De Qiang Li; Li Ling Wang (Journal of Atmospheric Chemistry, 2018)

RNA-seq analysis provides insight into reprogramming of culm development in Zizania latifolia induced by Ustilago esculenta - Zhi-Dan Wang; Ning Yan; Zheng-Hong Wang; Xiao-Huan Zhang; Jing-Ze Zhang; Hui-Min Xue; Li-Xia Wang; Qi Zhan; Ying-Ping Xu; De-Ping Guo (Plant Molecular Biology, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Paradigm changes in freshwater aquaculture practices in China: Moving towards achieving environmental integrity and sustainability - Qidong Wang; Zhongjie Li; Jian-Fang Gui; Jiashou Liu; Shaowen Ye; Jing Yuan; Sena S. De Silva (Ambio, 2017)

Walnut anthracnose caused by Colletotrichum siamense in China - Qing-Hai Wang; Kun Fan; De-Wei Li; Shan-Guang Niu; Li-Qun Hou; Xiao-Qin Wu (Australasian Plant Pathology, 2017)

Effects of different climate downscaling methods on the assessment of climate change impacts on wheat cropping systems - De Li Liu; Garry J. O’Leary; Brendan Christy; Ian Macadam; Bin Wang; Muhuddin R. Anwar; Anna Weeks (Climatic Change, 2017)

Time dependent pharmacokinetics of pembrolizumab in patients with solid tumor and its correlation with best overall response - Hongshan Li; Jingyu Yu; Chao Liu; Jiang Liu; Sriram Subramaniam; Hong Zhao; Gideon M. Blumenthal; David C. Turner; Claire Li; Malidi Ahamadi; Rik de Greef; Manash Chatterjee; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Diffraction separation by plane-wave prediction filtering - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2017)

Anti-hepatocellular carcinoma activity of tormentic acid derived from suspension cells of Eriobotrya japonica (Thunb.) Lindl. - Hui-Hua Li; Ming-Hua Su; De-Heng Yao; Bi-Yu Zeng; Qiang Chang; Wei Wang; Jian Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Global variation in the beta diversity of lake macrophytes is driven by environmental heterogeneity rather than latitude - Janne Alahuhta; Sarian Kosten; Munemitsu Akasaka; Dominique Auderset; Mattia M. Azzella; Rossano Bolpagni; Claudia P. Bove; Patricia A. Chambers; Eglantine Chappuis; John Clayton; Mary de Winton; Frauke Ecke; et al. (Journal of Biogeography, 2017)
Aim We studied global variation in beta diversity patterns of lake macrophytes using regional data from across the world. Specifically, we examined (1) how beta diversity of aquatic macrophytes is partitioned between species turnover and nestedness within each study region, and (2) which environmental characteristics structure variation in these beta diversity components. Location Global. Methods We used presence–absence data for aquatic macrophytes from 21 regions distributed around the world. We calculated pairwise‐site and multiple‐site beta diversity among lakes within each region using Sørensen dissimilarity index and partitioned it into turnover and nestedness coefficients. Beta regression was used to correlate the diversity coefficients with regional environmental characteristics. Results Aquatic macrophytes showed different levels of beta diversity within each of the 21 study regions, with species turnover typically accounting for the majority of beta diversity, especially in high‐diversity regions. However, nestedness contributed 30–50% of total variation in macrophyte beta diversity in low‐diversity regions. The most important environmental factor explaining the three beta diversity coefficients (total, species turnover and nestedness) was elevation range, followed by relative areal extent of freshwater, latitude and water alkalinity range. Main conclusions Our findings show that global patterns in beta diversity of lake macrophytes are caused by species turnover rather than by nestedness. These patterns in beta diversity were driven by natural environmental heterogeneity, notably variability in elevation range (also related to temperature variation) among regions. In addition, a greater range in alkalinity within a region, likely amplified by human activities, was also correlated with increased macrophyte beta diversity. These findings suggest that efforts to conserve aquatic macrophyte diversity should primarily focus on regions with large numbers of lakes that exhibit broad environmental gradients.

A novel synthetic derivative of squamosamide FLZ inhibits the high mobility group box 1 protein-mediated neuroinflammatory responses in murine BV2 microglial cells - De-Chuan Li; Xiu-Qi Bao; Xiao-Liang Wang; Hua Sun; Dan Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Responses of nitrous oxide emissions from crop rotation systems to four projected future climate change scenarios on a black Vertosol in subtropical Australia - Yong Li; De Li Liu; Graeme Schwenke; Bin Wang; Ian Macadam; Weijin Wang; Guangdi Li; Ram C Dalal (Climatic Change, 2017)

Improving the resolution of seismic traces based on the secondary time–frequency spectrum - De-Ying Wang; Jian-Ping Huang; Xue Kong; Zhen-Chun Li; Jiao Wang (Applied Geophysics, 2017)

Astragaloside IV, a Natural PPARγ Agonist, Reduces Aβ Production in Alzheimer’s Disease Through Inhibition of BACE1 - Xu Wang; Yue Wang; Jiang-Ping Hu; Song Yu; Bao-Kun Li; Yong Cui; Lu Ren; Li-De Zhang (Molecular Neurobiology, 2017)

Plastomes of Mimosoideae: structural and size variation, sequence divergence, and phylogenetic implication - Yin-Huan Wang; Xiao-Jian Qu; Si-Yun Chen; De-Zhu Li; Ting-Shuang Yi (Tree Genetics & Genomes, 2017)

Characteristics of low altitude ionospheric electric field over Hainan Island, China - RenKang Li; Tao Chen; Feng Man; XiuJie Jiang; Jing Luo; ZhaoHai He; HuiMing Zhang; LinFeng Wang; Cheng Liu; Francisco Carlos de Meneses; GuoJun Wang; JiYao Xu (Science China Earth Sciences, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Measurement and modeling of nitrous and nitric oxide emissions from a tea field in subtropical central China - Dan Chen; Yong Li; Cong Wang; Xiaoqing Fu; Xinliang Liu; Jianlin Shen; Yi Wang; Runlin Xiao; De Li Liu; Jinshui Wu (Nutrient Cycling in Agroecosystems, 2017)

Effect of different sulfadimidine addition methods on its degradation behaviour in swine manure - Tian-Tian Ren; Xiao-Yang Li; Yan Wang; Yong-De Zou; Xin-Di Liao; Juan-Boo Liang; Yin-Bao Wu (Environmental Science and Pollution Research, 2017)

Suppression of mTOR signaling pathway promotes bone marrow mesenchymal stem cells differentiation into osteoblast in degenerative scoliosis: in vivo and in vitro - Yu Wang; Xiao-Dong Yi; Chun-De Li (Molecular Biology Reports, 2017)

Petrogenesis and metallogenic potential of the Jurassic porphyries in the northwest Zhejiang Province, South China: insights from SHRIMP zircon geochronology, geochemistry, and Sr–Nd–Hf isotopes of the Huangbaikeng ore-bearing porphyries - Yu-Di Zhu; De-Hui Zhang; Li-Li Wang; Yan-Pei Dai; Ai-Hua Xi (International Geology Review, 2017)

CglCUT1 gene required for cutinase activity and pathogenicity of Colletotrichum gloeosporioides causing anthracnose of Camellia oleifera - Yixun Wang; Jingyuan Chen; De-Wei Li; Lu Zheng; Junbin Huang (European Journal of Plant Pathology, 2017)

Identification of aberrant DNA methylation involved in chemoradiation-resistant HCT116 cells via methylation-specific microarray - Wei Xiong; Yun-Feng Li; Shan Liu; Ting Chen; Hong-Tao Zhang; Zhi-Bin Yang; Ying-Ying Ding; De-Pei Gao; Guan-Shun Wang; Jian Dong (Molecular & Cellular Toxicology, 2016)

Antioxidant and antidiabetic properties of tartary buckwheat rice flavonoids after in vitro digestion - Tao Bao; Ye Wang; Yu-ting Li; Vemana Gowd; Xin-he Niu; Hai-ying Yang; Li-shui Chen; Wei Chen; Chong-de Sun (Journal of Zhejiang University-SCIENCE B, 2016)

Copper chelation by trientine dihydrochloride inhibits liver RFA-induced inflammatory responses in vivo - Ji-ming Yin; Li-bo Sun; Jia-sheng Zheng; Xin-xin Wang; De-xi Chen; Ning Li (Inflammation Research, 2016)

The regional impact of Land-Use Land-cover Change (LULCC) over West Africa from an ensemble of global climate models under the auspices of the WAMME2 project - Aaron Anthony Boone; Yongkang Xue; Fernando De Sales; Ruth E. Comer; Samson Hagos; Sarith Mahanama; Kathleen Schiro; Guoqiong Song; Guiling Wang; S. Li; Carlos R. Mechoso (Climate Dynamics, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

Multi-model ensemble projections of future extreme temperature change using a statistical downscaling method in south eastern Australia - Bin Wang; De Li Liu; Ian Macadam; Lisa V. Alexander; Gab Abramowitz; Qiang Yu (Climatic Change, 2016)

Identification of loci contributing to maize drought tolerance in a genome-wide association study - Nan Wang; Zhen-ping Wang; Xiao-ling Liang; Jian-feng Weng; Xiang-ling Lv; De-gui Zhang; Jie Yang; Hong-jun Yong; Ming-shun Li; Feng-hai Li; Li-yan Jiang; Shi-huang Zhang; et al. (Euphytica, 2016)

Soil heavy metal contamination related to roasted stone coal slag: a study based on geostatistical and multivariate analyses - De’an Li; Jianguo Jiang; Tianran Li; Jiaming Wang (Environmental Science and Pollution Research, 2016)

Downregulation of Glutamate Transporter EAAT4 by Conditional Knockout of Rheb1 in Cerebellar Purkinje Cells - Nan-Wei Jiang; De-Juan Wang; Ya-Jun Xie; Liang Zhou; Li-Da Su; Huashun Li; Qin-Wen Wang; Ying Shen (The Cerebellum, 2016)

Effect of Nitric Oxide on the Antifungal Activity of Oxidative Stress and Azoles Against Candida albicans - De-Dong Li; Chang-Chun Yang; Ping Liu; Yan Wang; Yan Sun (Indian Journal of Microbiology, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

The pseudorabies virus DNA polymerase processivity factor UL42 exists as a monomer in vitro and in vivo - Yi-Ping Wang; Li-Ping Huang; Wen-Juan Du; Yan-Wu Wei; De-Li Xia; Hong-Li Wu; Li Feng; Chang-Ming Liu (Archives of Virology, 2016)

Sustainable farming practices of the Chinese mitten crab (Eriocheir sinensis) around Hongze Lake, lower Yangtze River Basin, China - Qidong Wang; Jiashou Liu; Shengyu Zhang; Yuxi Lian; Huaiyu Ding; Xue Du; Zhongjie Li; Sena S. De Silva (Ambio, 2016)

Functional polymorphisms in the gene encoding macrophage migration inhibitory factor (MIF) are associated with active pulmonary tuberculosis - Shou-Gang Kuai; Qin-Fang Ou; De-Hong You; Zhong-Bo Shang; Jun Wang; Jun Liu; Xi-Ke Zhou; Hao Pei; Li-Hua Huang (Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Large-scale comparative phosphoprotein analysis of maize seedling leaves during greening - De-Li Ning; Ke-Hui Liu; Chang-Cai Liu; Jin-Wen Liu; Chun-Rong Qian; Yang Yu; Yue-Feng Wang; Ying-Chun Wang; Bai-Chen Wang (Planta, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Brevibacterium metallicus sp. nov., an endophytic bacterium isolated from roots of Prosopis laegivata grown at the edge of a mine tailing in Mexico - Brenda Román-Ponce; Yong Hua Li; María Soledad Vásquez-Murrieta; Xin Hua Sui; Wen Feng Chen; Paulina Estrada-de los Santos; En Tao Wang (Archives of Microbiology, 2015)

Freshwater aquaculture in PR C hina: trends and prospects - Qidong Wang; Lin Cheng; Jiashou Liu; Zhongjie Li; Shouqi Xie; Sena S. De Silva (Reviews in Aquaculture, 2015)
It is acknowledged that China is the mainstay in global aquaculture, contributing for example, 65.7 (of 76 321 310 t) and 63.6 (of 38 994 913 t) per cent to total global and freshwater aquaculture production, respectively, in 2011, significantly increasing the corresponding contributions from 36.1 and 38.5% of the global total (7 359 881 t) and global freshwater (2 342 706 t) aquaculture production in 1980. Overall, aquaculture production in China in turn has enabled to reduce our dependence on food fish supplies from a hunted to a farmed origin, like all the other staples. However, there are very few accounts on different subsectors of aquaculture in China and even less on variations in aquaculture developments within the country. This review attempts to trace the development trends in inland aquaculture in China in time and space and includes aspects on production, types and modes of culture, species cultured and marketing. It is evident that though inland aquaculture is practised in most provinces of China, the great bulk of it occurs in the area that lies approximately between 110 and 120 °E and 19 and 35 °N, in the Yangtze and Pearl River basins. The review also addresses emerging issues on freshwater aquaculture and possible ways of achieving sustainability in the long term.

Automated rapid iterative negative geotaxis assay and its use in a genetic screen for modifiers of Aβ42-induced locomotor decline in Drosophila - Haiyan Liu; Meng Han; Qingyi Li; Xiao Zhang; Wen-An Wang; Fu-De Huang (Neuroscience Bulletin, 2015)

Simultaneous detection of IgG and IgM antibodies against a recombinant polyprotein PstS1-LEP for tuberculosis diagnosis - Jun-Li Li; Xiang-Yu Huang; Hong-Bing Chen; Xin-Jing Wang; Chuan-Zhi Zhu; Ming Zhao; Qing-De Song; Hai-Yan Huang; Li Xiao; Xiu-Yun He (Infectious Diseases, 2015)

Investigating the MicroRNAomes of Two Developmental Phases of Dendrocalamus latiflorus (Poaceae: Bambusoideae) Inflorescences - Xu-Yao Zhao; Xiao-Yan Wang; Lei Zhao; Xue-Mei Zhang; Si-Yun Chen; Peng-Fei Ma; Xiang-Yang Hu; De-Zhu Li; Zhen-Hua Guo (Plant Molecular Biology Reporter, 2015)

Characterisation of the dark green islands of cucumber mosaic virus infected Nicotiana tabacum - Li-Juan Chen; Jian Liu; Fei-Fei Zhao; Jing-Yi Li; Sheng-Xuan Wang; Hong-Hui Lin; De-Hui Xi (Plant Cell Reports, 2015)

Identifying and managing risk factors for salt-affected soils: a case study in a semi-arid region in China - De Zhou; Jianchun Xu; Li Wang; Zhulu Lin; Liming Liu (Environmental Monitoring and Assessment, 2015)

The soybean gene, GmMYBJ2, encodes a R2R3-type transcription factor involved in drought stress tolerance in Arabidopsis thaliana - Lian-Tai Su; Ying Wang; De-Quan Liu; Xiao-Wei Li; Ying Zhai; Xin Sun; Xu-Yan Li; Ya-Jing Liu; Jing-Wen Li; Qing-Yu Wang (Acta Physiologiae Plantarum, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Identification of Mycobacterium tuberculosis PPE68-Specific HLA-A*0201-Restricted Epitopes for Tuberculosis Diagnosis - Zhi-liang Duan; Qiang Li; Sina Wang; Xin-yu Chen; Hui-fang Liu; Bo-kun Chen; De-zhou Li; Xi Huang; Jin-sheng Wen (Current Microbiology, 2015)

Molecular cloning and expression of a nitrite reductase gene from mulberry (Morus L.) - Xi-ling Wang; Ya-sheng Yu; Yan Yang; Chang-ying Liu; Jun Li; Mao-de Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Phytoextraction of uranium from contaminated soil by Macleaya cordata before and after application of EDDS and CA - Chang-wu Li; Nan Hu; De-xin Ding; Jin-song Hu; Guang-yue Li; Yong-dong Wang (Environmental Science and Pollution Research, 2015)

The decreased frequency of SIGIRR-positive CD4+ T cells in peripheral blood of patients with SLE and its correlation with disease activity - Dao-Yang Wang; Chao Su; Gui-Mei Chen; Hai-Feng Pan; Feng-Mei Wang; Gui-Ling Liu; Li Hao; De-Guang Wang; Dong-Qing Ye (Molecular Biology Reports, 2015)

Advanced glycation end products induce oxidative stress and mitochondrial dysfunction in SH-SY5Y cells - Xu Wang; Song Yu; Chun-Yan Wang; Yue Wang; Hai-Xing Liu; Yong Cui; Li-De Zhang (In Vitro Cellular & Developmental Biology - Animal, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Greenhouse gas intensity of three main crops and implications for low-carbon agriculture in China - Wen Wang; Liping Guo; Yingchun Li; Man Su; Yuebin Lin; Christian de Perthuis; Xiaotang Ju; Erda Lin; Dominic Moran (Climatic Change, 2015)

Removal and Recovery of U(VI) from Low Concentration Radioactive Wastewater by Ethylenediamine-Modified Biomass of Aspergillus niger - De Xin Ding; Xin Xin; Le Li; Nan Hu; Guang Yue Li; Yong Dong Wang; Ping Kun Fu (Water, Air, & Soil Pollution, 2014)

Paenibacillus abyssi sp. nov., isolated from an abyssal sediment sample from the Indian Ocean - Xiao-Fang Huang; Fa-Zuo Wang; Wei Zhang; Jie Li; Juan Ling; Jian Yang; Jun-De Dong; Xin-Peng Tian (Antonie van Leeuwenhoek, 2014)

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

Two new truffles species, Tuber alboumbilicum and Tuber pseudobrumale from China - Shu-Hong Li; Lin-Yong Zheng; Cheng-Yi Liu; Yun Wang; Lin Li; Yong-Chang Zhao; Xiao-Lei Zhang; Mei Yang; Hai-Kuan Xiong; Yuan Qing; Li Wang; De-Qun Zhou (Mycological Progress, 2014)

Epidemiological situation and genetic analysis of H7N9 influenza viruses in Shanghai in 2013 - Fei-Fei Ge; Hou-Bin Ju; De-Quan Yang; Jian Liu; Jian Wang; Jun Lu; Xin Li; Wei-Yi Zhang; Pei-Hong Liu; Jin-Ping Zhou (Archives of Virology, 2014)

Development of proteomic technology of shotgun and label free combined with multiple reaction monitoring to simultaneously detect southern rice black-streaked dwarf virus and rice ragged stunt virus - Zhuo Chen; Qin Guo; Bing-Hua Chen; Xiang-Yang Li; Zhen-Chao Wang; Peng He; Fei Yan; De-Yu Hu; Song Yang (VirusDisease, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

RETRACTED ARTICLE: Effects of Osteopontin on Expression of IL-6 and IL-8 Inflammatory Factors in Human Knee Osteoarthritis Chondrocytes - Weiwu Yao; Xiaodong Chen; De Li; Peng Wang; Hanlong Xin; Jianhua Wang (Cell Biochemistry and Biophysics, 2014)

Targeting IL-10 in Auto-immune Diseases - Guo Tian; Jiao-Long Li; De-Guang Wang; Dian Zhou (Cell Biochemistry and Biophysics, 2014)

Assessment of the Iodine Status of the Wa National Boarding School Students in Southwest China - Jian-Zhong Yin; Yue-Mei Feng; Shao-Xiong Wu; Xue-Hui Zhang; Song-Mei Wang; Qi Wang; Yuan Li; De-Li Qi (Biological Trace Element Research, 2014)

Identification and characterization of six cytochrome P450 genes belonging to CYP4 and CYP6 gene families in the silkworm, Bombyx mori - Bing Li; Hua Zhang; Min Ni; Bin-bin Wang; Fan-chi Li; Kai-zhun Xu; Wei-de Shen; Qing-you Xia; Ping Zhao (Molecular Biology Reports, 2014)

Rickettsia raoultii, the predominant Rickettsia found in Dermacentor silvarum ticks in China–Russia border areas - Jing Wen; Dan Jiao; Jian-hua Wang; De-hai Yao; Zhi-xiang Liu; Gang Zhao; Wen-dong Ju; Cheng Cheng; Yi-jing Li; Yi Sun (Experimental and Applied Acarology, 2014)

An innovative approach for iodine supplementation using iodine-rich phytogenic food - Huan-Xin Weng; Hui-Ping Liu; De-Wang Li; Mingli Ye; Lehua Pan; Tian-Hong Xia (Environmental Geochemistry and Health, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of QTLs for seedling vigor in winter wheat - Xing-Mao Li; Xin-Min Chen; Yong-Gui Xiao; Xian-Chun Xia; De-Sen Wang; Zhong-Hu He; Hua-Jun Wang (Euphytica, 2014)

Profiles, sources, and transport of polycyclic aromatic hydrocarbons in soils affected by electronic waste recycling in Longtang, south China - De-Yin Huang; Chuan-Ping Liu; Fang-Bai Li; Tong-Xu Liu; Cheng-Shuai Liu; Liang Tao; Yan Wang (Environmental Monitoring and Assessment, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Cloning and analysis of bile salt hydrolase genes from Lactobacillus plantarum CGMCC No. 8198 - Xiang-Chao Gu; Xue-Gang Luo; Chong-Xi Wang; De-Yun Ma; Yan Wang; Ying-Ying He; Wen Li; Hao Zhou; Tong-Cun Zhang (Biotechnology Letters, 2014)

Elevational patterns of endogenous hormones and their relation to resprouting ability of Quercus aquifolioides plants on the eastern edge of the Tibetan Plateau - Wan-Ze Zhu; San-Gen Wang; De-Zhen Yu; Yong Jiang; Mai-He Li (Trees, 2014)

Expression analysis and RNA interference of BmCarE-10 gene from Bombyx mori - Guo-dong Zhao; Ming-xia Huang; Yi-ling Zhang; Xue-cen Wang; Jie Du; Bing Li; Yu-hua Chen; Ya-xiang Xu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

Variations in nitrogen-15 natural abundance of plant and soil systems in four remote tropical rainforests, southern China - Ang Wang; Yun-Ting Fang; De-Xiang Chen; Keisuke Koba; Akiko Makabe; Yi-De Li; Tu-Shou Luo; Muneoki Yoh (Oecologia, 2014)

Functional study on the mutations in the silkworm (Bombyx mori) acetylcholinesterase type 1 gene (ace1) and its recombinant proteins - Ju-mei Wang; Bin-bin Wang; Yi Xie; Shan-shan Sun; Zhi-ya Gu; Lie Ma; Fan-chi Li; Yi-fan Zhao; Bin Yang; Wei-de Shen; Bing Li (Molecular Biology Reports, 2014)

Proteomic Analysis Points to a Role for RAD23 in Apical Dominance in Pinus sylvestris var. Mongolica - De-Li Ning; Tian-Chong Lu; Gui-Feng Liu; Chuan-Ping Yang; Bai-Chen Wang (Plant Molecular Biology Reporter, 2013)

Seed morphological diversity of Pedicularis (Orobanchaceae) and its taxonomic significance - Min-Lu Liu; Wen-Bin Yu; De-Zhu Li; Robert R. Mill; Hong Wang (Plant Systematics and Evolution, 2013)

Effects of diethylhexyl phthalate (DEHP) given neonatally on spermatogenesis of mice - Xi-Feng Zhang; Teng Zhang; Liu Wang; Hong-Ying Zhang; Yong-De Chen; Xun-Si Qin; Yan-Min Feng; Yan-Ni Feng; Wei Shen; Lan Li (Molecular Biology Reports, 2013)

Stachybotrys from soil in China, identified by morphology and molecular phylogeny - Chun-Yu Jie; Kun Geng; Yu-Lan Jiang; Jun-Jie Xu; Kevin D. Hyde; Eric H. C. McKenzie; Tian-Yu Zhang; Ali H. Bahkali; De-Wei Li; Yong Wang (Mycological Progress, 2013)

The Protective Effect of Salvianolic Acid B on Blood–Spinal Cord Barrier After Compression Spinal Cord Injury in Rats - Zhong-kai Fan; Gang Lv; Yan-feng Wang; Gang Li; De-shui Yu; Yan-song Wang; Yu-qiang Zhang; Xi-fan Mei; Yang Cao (Journal of Molecular Neuroscience, 2013)

The effects of biotic and abiotic factors on the spatial heterogeneity of alpine grassland vegetation at a small scale on the Qinghai–Tibet Plateau (QTP), China - Lu Wen; Shi Kui Dong; Yuan Yuan Li; Ruth Sherman; Jian Jun Shi; De Mei Liu; Yan Long Wang; Yu Shou Ma; Lei Zhu (Environmental Monitoring and Assessment, 2013)

Quantitative evaluation of environmental risks of flotation tailings from hydrothermal sulfidation–flotation process - Xian-De Xie; Xiao-Bo Min; Li-Yuan Chai; Chong-Jian Tang; Yan-Jie Liang; Mi Li; Yong Ke; Jie Chen; Yan Wang (Environmental Science and Pollution Research, 2013)

The expression and phylogenetic analysis of four AP3-like paralogs in the stamens, carpels, and single-whorl perianth of the paleoherb Asarum caudigerum - Yin-He Zhao; Zachary Larson-Rabin; De-Zhu Li; Guo-Ying Wang; Seng Peng; Cheng-Yun Li (Molecular Biology Reports, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Label-free quantitative proteomics analysis of dormant terminal buds of poplar - De-Li Ning; Chang-Cai Liu; Jin-Wen Liu; Zhuo Shen; Su Chen; Feng Liu; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2013)

Retrograde cPLA2α/Arachidonic Acid/2-AG Signaling Is Essential for Cerebellar Depolarization-Induced Suppression of Excitation and Long-Term Potentiation - Li-Da Su; De-Juan Wang; Dong Yang; Ying Shen; Ying-Hong Hu (The Cerebellum, 2013)

Mutational Screening of PARKIN Identified a 3′ UTR Variant (rs62637702) Associated with Parkinson’s Disease - Lorena de Mena; LLuís Samaranch; Eliecer Coto; Lucía F. Cardo; René Ribacoba; Oswaldo Lorenzo-Betancor; Pau Pastor; Li Wang; Jaione Irigoyen; Ignacio F. Mata; Marta Díaz; Germán Moris; et al. (Journal of Molecular Neuroscience, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Estimating primaries by sparse inversion of the 3D curvelet transform and the L1-norm constraint - Fei Feng; De-Li Wang; Heng Zhu; Hao Cheng (Applied Geophysics, 2013)

Cutaneous and Mucosal Phaeohyphomycosis Caused by Exophiala spinifera in a Pregnant Patient: Case Report and Literature Review - Le Wang; Xiaodong She; Guixia Lv; Yongnian Shen; Qing Cai; Rong Zeng; Caixia Li; Yiping Ge; Shuwen Deng; G. S. de Hoog; Min Li; Weida Liu (Mycopathologia, 2013)

Simulated microgravity alters the metastatic potential of a human lung adenocarcinoma cell line - De Chang; Huiwen Xu; Yinghua Guo; Xuege Jiang; Yan Liu; Kailong Li; Chunxiao Pan; Ming Yuan; Junfeng Wang; Tianzhi Li; Changting Liu (In Vitro Cellular & Developmental Biology - Animal, 2013)

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Fluid evolution of the Jiawula Ag–Pb–Zn deposit, Inner Mongolia: mineralogical, fluid inclusion, and stable isotopic evidence - De-Gao Zhai; Jia-Jun Liu; Jian-Ping Wang; Mei-Juan Yao; Sheng-Hua Wu; Chao Fu; Zhen-Jiang Liu; Shou-Guang Wang; Yu-Xi Li (International Geology Review, 2013)

Cervical cancer with polymorphism in MTHFR C677T gene: a systematic review and meta-analysis - Xiao-juan Xu; Li-wei Zou; De-bin Wang (Molecular Biology Reports, 2013)

Molecular phylogeography of Fagus engleriana (Fagaceae) in subtropical China: limited admixture among multiple refugia - Ming Lei; Qun Wang; Zhen-Jian Wu; Jordi López-Pujol; De-Zhu Li; Zhi-Yong Zhang (Tree Genetics & Genomes, 2012)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Association study of ACE polymorphisms and systemic lupus erythematosus in Northern Chinese Han population - Ai-min Gong; Xin-yuan Li; Yi-qin Wang; Hai-xia Yan; Zhao-xia Xu; Zhao Feng; Yi-qiang Xie; De-hui Yin; Shi-zhong Yang (Molecular Biology Reports, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Perifosine as potential anti-cancer agent inhibits proliferation, migration, and tube formation of human umbilical vein endothelial cells - Feng Ze Wang; Hong Rong Fei; Xiao Qian Li; Renjiu Shi; De Cai Wang (Molecular and Cellular Biochemistry, 2012)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Loss of floral polymorphism in heterostylous Luculia pinceana (Rubiaceae): a molecular phylogeographic perspective - WEI ZHOU; SPENCER C. H. BARRETT; HONG WANG; DE‐ZHU LI (Molecular Ecology, 2012)
Both deterministic and stochastic forces determine the representation and frequency of floral morphs in heterostylous plant populations. Phylogeographic analysis of molecular variation can provide information on the role of historical factors, including founder events, in affecting population morph structure. Here, we investigate geographical patterns of floral morph variation in a distylous shrub Luculia pinceana (Rubiaceae) by examining the relations between floral polymorphism and molecular ( cp DNA and microsatellite) variation in 25 populations sampled throughout the distribution of the species in southwest China and adjacent countries. In 19 of the 25 populations, the frequency of floral morphs was not significantly different from the expected 1:1 ratio. The remaining populations were either L‐morph biased (2) or monomorphic (4) for this form and were morphologically differentiated from the remaining populations in several floral traits, that is, corolla tube length, sex organ position and stigma‐anther separation. Phylogeographic analysis supports the hypothesis that L. pinceana was initially split into west‐central and eastern lineages in the Early Pleistocene (∼1.982 Mya). A centrally located lineage composed of morph‐biased and monomorphic populations appears to have been subsequently derived from the west‐central lineage, perhaps by a founder event after the last glacial maximum. Hypotheses to explain why these populations have not returned to equilibrium morph frequencies are considered.

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Effect of alkalized magnesic salinity on soil respiration changes with substrate availability and incubation time - Xiao Gang Li; Xiao Ming Shi; De Jian Wang; Wei Zhou (Biology and Fertility of Soils, 2012)

Effect of Selenium on the Interaction Between Daunorubicin and Cardiac Myosin - Yang Liu; Bu-hai Li; Xiao-mei Sun; Ai-hua Lin; De-bin Wang (Biological Trace Element Research, 2012)

Scattering spectrum properties and their relationship to biogeochemical parameters: a case study in Taihu Lake - Chang-Chun Huang; Yun-Mei Li; Qiao Wang; De-Yong Sun; Cheng-Feng Le; Kun Shi (Limnology, 2012)

Phylogenetic relationships of Chinese Adiantum based on five plastid markers - Jin-Mei Lu; Jun Wen; Sue Lutz; Yi-Ping Wang; De-Zhu Li (Journal of Plant Research, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

Lysosomal membrane permeabilization is involved in curcumin-induced apoptosis of A549 lung carcinoma cells - Qing-Yong Chen; Jian-Guo Shi; Qing-Hua Yao; De-Min Jiao; Yan-Yi Wang; Hui-Zhen Hu; Yu-Quan Wu; Jia Song; Jie Yan; Li-Jun Wu (Molecular and Cellular Biochemistry, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Nm23-H1 Protein Binds to APE1 at AP Sites and Stimulates AP Endonuclease Activity Following Ionizing Radiation of the Human Lung Cancer A549 Cells - Zhi-Min Zhang; Xue-Qin Yang; Dong Wang; Ge Wang; Zhen-Zhou Yang; Yi Qing; Zhi-Xiang Yang; Meng-Xia Li; De-Bing Xiang (Cell Biochemistry and Biophysics, 2011)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Fenvalerate induces germ cell apoptosis in mouse testes through the Fas/FasL signaling pathway - Xian-Feng Zhao; Qun Wang; Yan-Li Ji; Hua Wang; Ping Liu; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2011)

A neural-network model to retrieve CDOM absorption from in situ measured hyperspectral data in an optically complex lake: Lake Taihu case study - De Yong Sun; Yun Mei Li; Qiao Wang; Heng Lu; Cheng Feng Le; Chang Chun Huang; Shao Qi Gong (International Journal of Remote Sensing, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Modelling the impacts of climate change on wheat yield and field water balance over the Murray–Darling Basin in Australia - Jing Wang; Enli Wang; De Li Liu (Theoretical and Applied Climatology, 2011)

Alkaline-stress response in Glycine soja leaf identifies specific transcription factors and ABA-mediated signaling factors - Ying Ge; Yong Li; De-Kang Lv; Xi Bai; Wei Ji; Hua Cai; Ao-Xue Wang; Yan-Ming Zhu (Functional & Integrative Genomics, 2011)

Screening of Plant Species for Phytoremediation of Uranium, Thorium, Barium, Nickel, Strontium and Lead Contaminated Soils from a Uranium Mill Tailings Repository in South China - Guang-yue Li; Nan Hu; De-xin Ding; Ji-fang Zheng; Yu-long Liu; Yong-dong Wang; Xiao-qin Nie (Bulletin of Environmental Contamination and Toxicology, 2011)

Highly efficient plant regeneration and in vitro polyploid induction using hypocotyl explants from diploid mulberry (Morus multicaulis Poir.) - Wang Xi-Ling; Zhou Jin-Xing; Yu Mao-De; Li Zhen-Gang; Jin Xiao-Yun; Li Qi-You (In Vitro Cellular & Developmental Biology - Plant, 2011)

Molecular identification of endophytic fungi from medicinal plant Huperzia serrata based on rDNA ITS analysis - Xu Yu Chen; Yao Dong Qi; Jian He Wei; Zheng Zhang; De Li Wang; Jin Dong Feng; Bing Chun Gan (World Journal of Microbiology and Biotechnology, 2011)

Cloning and Expression Analysis of Wheat Cytokinin Oxidase/Dehydrogenase Gene TaCKX3 - Xin Ma; De-Shun Feng; Hong-Gang Wang; Xing-Feng Li; Ling-Rang Kong (Plant Molecular Biology Reporter, 2011)

Maslinic acid induces apoptosis in salivary gland adenoid cystic carcinoma cells by Ca2+-evoked p38 signaling pathway - Dong-Mei Wu; Dan Zhao; De-Zhi Li; Dong-Yang Xu; Wen-Feng Chu; Xiao-Feng Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Seasonal and Spatial Variations of Air Concentrations of Polycyclic Aromatic Hydrocarbons in Northeastern Chinese Urban Region - Wan-li Ma; Hong Qi; Yi-fan Li; Li-yan Liu; De-zhi Sun; De-gao Wang; Zhi Zhang; Chong-guo Tian; Ji-min Shen (Bulletin of Environmental Contamination and Toxicology, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Erratum to: Biosorption of Copper by Cyanobacterial Bloom-Derived Biomass Harvested from the Eutrophic Lake Dianchi in China - Kan Wang; Giovanni Colica; Roberto De Philippis; Yongding Liu; Dunhai Li (Current Microbiology, 2010)

An iterative curvelet thresholding algorithm for seismic random noise attenuation - De-Li Wang; Zhong-Fei Tong; Chen Tang; Heng Zhu (Applied Geophysics, 2010)

Novel 1-alkyl-tryptophan derivatives downregulate IDO1 and IDO2 mRNA expression induced by interferon-gamma in dendritic cells - Ting Sun; Xiang-Hua Chen; Zheng-De Tang; Jiong Cai; Xiao-Yan Wang; Shih-Chen Wang; Zhao-Long Li (Molecular and Cellular Biochemistry, 2010)

Combined migration velocity model-building and its application in tunnel seismic prediction - Xiang-Bo Gong; Li-Guo Han; Jian-Jun Niu; Xiao-Pei Zhang; De-Li Wang; Li-Zhi Du (Applied Geophysics, 2010)

Flower heliotropism of Anemone rivularis (Ranunculaceae) in the Himalayas: effects on floral temperature and reproductive fitness - Shu Zhang; Hong-Lian Ai; Wen-Bin Yu; Hong Wang; De-Zhu Li (Plant Ecology, 2010)

Recombinant mouse beta-defensin 2 inhibits infection by influenza A virus by blocking its entry - Tianxiang Gong; Yan Jiang; Yueling Wang; De Yang; Wanyi Li; Qiang Zhang; Wei Feng; Baoning Wang; Zhonghua Jiang; Mingyuan Li (Archives of Virology, 2010)

Molecular cloning, characterization and expression analysis of PtrHOS1, a novel gene of cold responses from trifoliate orange [Poncirus trifoliata (L.) Raf.] - De-Chun Liu; Li-Gang He; Hui-Liang Wang; Miao Xu; Zhong-Hai Sun (Acta Physiologiae Plantarum, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Erratum to: Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

Comparative proteomic analysis of apomictic monosomic addition line of Beta corolliflora and Beta vulgaris L. in sugar beet - Hong Zhu; Ying-Dong Bi; Li-Jie Yu; De-Dong Guo; Bai-Chen Wang (Molecular Biology Reports, 2009)

Combined Effects of Repeated Administration of 2,3,7,8-Tetrachlorodibenzo-p-dioxin and Polychlorinated Biphenyls on Kidneys of Male Rats - Chun-Feng Lu; Yi-Mei Wang; Shuang-Qing Peng; Li-Bo Zou; De-Hong Tan; Gang Liu; Ze Fu; Qiao-Xu Wang; Jing Zhao (Archives of Environmental Contamination and Toxicology, 2009)

Isolation and characterization of 13 microsatellite loci from Incarvillea mairei (Bignoniaceae), an endemic species to the Himalaya-Hengduan mountains region - Hong-Lian Ai; Hong Wang; De-Zhu Li; Jun-Bo Yang (Conservation Genetics, 2009)

Metal Pollution in Huayuan River in Hunan Province in China by Manganese Sulphate Waste Residue - Nan Hu; Ji-Fang Zheng; De-Xin Ding; Jun Liu; Lu-Qing Yang; Jie Yin; Guang-Yue Li; Yong-Dong Wang; Yu-Long Liu (Bulletin of Environmental Contamination and Toxicology, 2009)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Isolation and Evolution Mode Analysis of NBS–LRR Resistance Gene Analogs from Hexaploid Wheat - De-Shun Feng; Yan Li; Hong-Gang Wang; Xing-Feng Li; Ju-Rong Gao (Plant Molecular Biology Reporter, 2009)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Molecular alteration of Cav1.2 calcium channel in chronic myocardial infarction - Ping Liao; Guang Li; De Jie Yu; Tan Fong Yong; Jue Jin Wang; Jing Wang; Tuck Wah Soong (Pflügers Archiv - European Journal of Physiology, 2009)

Identification and characterization of the duck enteritis virus UL51 gene - Chan-Juan Shen; An-Chun Cheng; Ming-Shu Wang; Yu-Fei Guo; Li-Chan Zhao; Ming Wen; Wei Xie; Hong-Yi Xin; De-Kang Zhu (Archives of Virology, 2009)

Sixteen novel microsatellite loci developed for the giant panda (Ailuropoda melanoleuca) - He-Min Zhang; Yang Guo; De-Sheng Li; Peng-Yan Wang; Sheng-Guo Fang (Conservation Genetics, 2009)

Purification and characterization of novel antifungal peptide, mouse beta defensin-1, in Escherichia coli - Yueling Wang; Yan Jiang; De Yang; Wanyi Li; Tianxiang Gong; Yan Feng; Zhonghua Jiang; Mingyuan Li (World Journal of Microbiology and Biotechnology, 2009)

Expression of EGFP driven by BmNPV orf4 promoter, a novel immediate early promoter - Wu-Jie Su; Bing Li; Wei-De Shen; Yan Wu; Shan-Ying Zhu; Ying Sun; Wen-Bing Wang (Biologia, 2009)

Expression of mouse beta-defensin-3 in MDCK cells and its anti-influenza-virus activity - Yan Jiang; Yueling Wang; Yu Kuang; Baoning Wang; Wanyi Li; Tianxiang Gong; Zhonghua Jiang; De Yang; Mingyuan Li (Archives of Virology, 2009)

Polycyclic Aromatic Hydrocarbons in Urban Street Dust and Surface Soil: Comparisons of Concentration, Profile, and Source - De-Gao Wang; Meng Yang; Hong-Liang Jia; Lei Zhou; Yi-Fan Li (Archives of Environmental Contamination and Toxicology, 2009)

Using an Inverse PCR Method to Clone the Wheat Cytokinin Oxidase/Dehydrogenase Gene TaCKX1 - De-Shun Feng; Hong-Gang Wang; Xian-Sheng Zhang; Ling-Rang Kong; Ji-Chun Tian; Xing-Feng Li (Plant Molecular Biology Reporter, 2008)

Large litter size increases maternal energy intake but has no effect on UCP1 content and serum-leptin concentrations in lactating Brandt’s voles (Lasiopodomys brandtii) - Xue-Ying Zhang; Yu-Lian Li; De-Hua Wang (Journal of Comparative Physiology B, 2008)

Accumulation of pinitol and other soluble sugars in water‐stressed phyllodes of tropical Acacia auriculiformis in northern Australia - Li‐Xia Liu; Shou‐Mtn Xu; De‐Li Wang; K. C. Woo (New Zealand Journal of Botany, 2008)
The effect of water stress on leaf sugars and photosynthesis was examined in clones of Acacia auriculiformis in Darwin, northern Australia. Compared with the wet season or irrigated or watered‐site plants, phyllodes of plants grown in the dry season on unirrigated or water‐stressed sites had significantly higher contents of pinitol and total sugars. The pinitol content constituted 50% of the phyllode total sugars content compared with 17% for fructose, 20% for glucose, and A. auriculiformis accumulated more pinitol but less sucrose than seedlings grown in the shade‐house. Under water‐stress conditions, phyllode total sugars decreased 15% in seedlings but increased 30% in trees in the field. These differences probably reflect the different developmental stages and different light levels between seedlings and trees. Thus, the contents of different sugars may be involved in osmotic adjustment during water stress in A. auriculiformis .

Characterization of cDNAs associated with lignification and their expression profiles in loquat fruit with different lignin accumulation - Lan Lan Shan; Xian Li; Ping Wang; Chong Cai; Bo Zhang; Chong De Sun; Wang Shu Zhang; Chang Jie Xu; Ian Ferguson; Kun Song Chen (Planta, 2008)

Increased expression of hLRH-1 in human gastric cancer and its implication in tumorigenesis - Shui-Liang Wang; De-Zhu Zheng; Feng-Hua Lan; Xiao-Jun Deng; Jian Zeng; Cheng-Jin Li; Rong Wang; Zhong-Yong Zhu (Molecular and Cellular Biochemistry, 2008)

Bioremediation of Oil Sludge in Shengli Oilfield - Shi De-qing; Zhang Jian; Gui Zhao-long; Dong Jian; Wang Tian-li; Valentina Murygina; Sergey Kalyuzhnyi (Water, Air, & Soil Pollution, 2007)

Cellular and molecular responses in progressive pseudorheumatoid dysplasia articular cartilage associated with compound heterozygous WISP3 gene mutation - Hou-De Zhou; Yan-Hong Bu; Yi-Qun Peng; Hui Xie; Min Wang; Lin-Qing Yuan; Yi Jiang; Duo Li; Qi-You Wei; Yu-Ling He; Tao Xiao; Jiang-Dong Ni; et al. (Journal of Molecular Medicine, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Ultradian rhythms and the nutritional importance of caecotrophy in captive Brandt’s voles (Lasiopodomys brandtii) - Quan-Sheng Liu; Ji-Yuan Li; De-Hua Wang (Journal of Comparative Physiology B, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

The Effect of Plant Growth Regulators and Sucrose on the Micropropagation and Microtuberization of Dioscorea nipponica Makino - Feng-Qing Chen; Yang Fu; De-Li Wang; Xiang Gao; Li Wang (Journal of Plant Growth Regulation, 2007)

Dose-dependant radiation-induced apoptosis in a cochlear cell-line - Wong-Kein Low; Michelle G. K. Tan; Li Sun; Alvin W. C. Chua; Lip-Kai Goh; De-Yun Wang (Apoptosis, 2006)

A novel bieremophilanolide from Ligularia lapathifolia - Yun-Sen Li; Shao-Shun Li; Zheng-Tao Wang; Shi-De Luo; Da-Yuan Zhu (Natural Product Research, 2006)

Subcellular localization, expression patterns, SNPs and association analyses of the porcine HUMMLC2B gene - Huan L. Wang; Heng Wang; Zheng M. Zhu; Chen F. Wang; Meng J. Zhu; De L. Mo; Shu L. Yang; Kui Li (Molecular Genetics and Genomics, 2006)

Sensitized photooxidation of furanoeremophilane with singlet oxygen and their biogenetic relationship - Yun-Sen Li; Zheng-Tao Wang; Shi-De Luo; Shao-Shun Li; Da-Yuan Zhu (Natural Product Research, 2006)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)

Construction of introgression lines carrying wild rice (Oryza rufipogon Griff.) segments in cultivated rice (Oryza sativa L.) background and characterization of introgressed segments associated with yield-related traits - Feng Tian; De Jun Li; Qiang Fu; Zuo Feng Zhu; Yong Cai Fu; Xiang Kun Wang; Chuan Qing Sun (Theoretical and Applied Genetics, 2006)

Cloning and Characterization of a Second form of the Rice Adenine Phosphoribosyl Transferase Gene (OsAPT2) and its Association with TGMS - Chun-Jiang Zhou; Jun Li; Ji-Cheng Zou; Feng-Shan Liang; Chun-Jiang Ye; De-Min Jin; Man-Li Weng; Bin Wang (Plant Molecular Biology, 2006)

Effect of gemfibrozil on the pharmacokinetics of pioglitazone - Li-Jing Deng; Feng Wang; Huan-De Li (European Journal of Clinical Pharmacology, 2005)

Seasonal adjustments in body mass and thermogenesis in Mongolian gerbils (Meriones unguiculatus): the roles of short photoperiod and cold - Xing-Sheng Li; De-Hua Wang (Journal of Comparative Physiology B, 2005)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Evaluation of genetic diversity and germ plasm identification of 44 species, clones, and cultivars from 5 sections of the genusPopulus based on amplified fragment length polymorphism analysis - Chun Jiang Zhou; Hong Zhu Song; Jin Hua Li; Jian Wei Sun; Min De Jin; Qi Wen Zhang; Bin Wang (Plant Molecular Biology Reporter, 2005)

Construction and characterization of a bacterial artificial chromosome library of marine macroalgaPorphyra yezoensis (Rhodophyta) - Dai Yong Deng; Ge Zhao; Jin Song Xuan; Ji Liang Yang; Lin De Duan; Man Li Weng; Bin Wang (Plant Molecular Biology Reporter, 2004)

Multi-Person Multiobjective Fuzzy Decision-Making Model for Reservoir Flood Control Operation - Yi-bin Yu; Ben-de Wang; Guo-li Wang; Wei Li (Water Resources Management, 2004)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)

Paradoxical effects of a stress signal on pro- and anti-apoptotic machinery in HTLV-1 tax expressing cells - Cynthia de la Fuente; Lai Wang; Dai Wang; Longwen Deng; Kaili Wu; Hong Li; Dana Stein; Thomas Denny; Frederick Coffman; Kylene Kehn; Shanese Baylor; Anil Maddukuri; et al. (Molecular and Cellular Biochemistry, 2003)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

In vitro assay for 2,4-D resistance in transgenic cotton - Bao-Hong Zhang; Hong-Mei Wang; Fang Liu; Yun-Hai Li; Zheng-De Liu (In Vitro Cellular & Developmental Biology - Plant, 2001)

Aluminum content of tea leaves and factors affecting the uptake of aluminum from soil into tea leaves - Zhong-lei Xie; De-ming Dong; Guo-zhang Bao; Sheng-tian Wang; Yao-guo Du; Li-min Qiu (Chinese Geographical Science, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)